Identification of chloroplast transit peptides inDunaliella salina and their application for heterologous astaxanthin production - Jv-Liang Dai; Ling Xiao; Yue-Li Yuan; Ming-Hua Liang; Jian-Guo Jiang (Bioresource Technology, 2027)

Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

A bibliometrics review of non-CO2 greenhouse gas reduction strategies - Yi-Ming Wei; Si-Yu Liu; Li-Jing Liu; Lan-Cui Liu; Qiao-Mei Liang; Xiao-Chen Yuan; Hong-Dian Jiang; Pallav Purohit; Felix Creutzig; Hua Liao; Biying Yu (Energy and Climate Change, 2026)

Paternal vitamin D deficiency is associated with offspring testicular developmental abnormalities, fibrosis, and altered sperm miRNA profiles - Yu-Ming Chen; Zhi-Hong Tian; Shi-Yuan Li; Juan Dai; Xing-Ru Wang; Guo-Ying Sun; Min Liu; Berthold Hocher; Mei Tian (Molecular Biology Reports, 2026)

Precise dual-gene knockout of MSTN and SOCS2 via cytidine base editing enhances muscling and growth in goats - Ling Li; Ming-Xing Cao; Muhammad Farhab; Paing Oo Kyaw; Shu-Qi Zhao; Yi Zhao; Feng-Lei Chen; Tariq Sohail; Ejaz Ahmad; Shao-Xian Cao; Yu-Guo Yuan (Functional & Integrative Genomics, 2026)

Unlocking the hidden carbon pool: Refractory organic matter drives superior chain elongation in sludge alkaline fermentation liquid - Dingkang Qian; Ziming Xu; Mengjiao Yuan; Zhen Li; Qian Zhu; Ming Peng; Jianyu Gong; Jiakuan Yang; Jingping Hu; Huijie Hou (Water Research, 2026)

Beyond gastroenteritis: first evidence of systemic biochemical disturbances, predominantly coagulation dysfunction, in Neoboletus poisoning - Jia Li; Yuan-Tian Lu; Xiu-Juan Li; Ming Li; Ping Wei; Tai-Jie Yu; Yu-Xian Gao; Ting Li; Yuan-Yuan Xiong; Yi Liu; Li-Ping Tang (Toxicon, 2026)

Fracture-controlled reactive transport and fractal permeability evolution during CO₂ + O₂ in situ leaching of uranium-bearing sandstone - Tong Zhang; Bingzhang Li; Xin Yang; Ming Tang; Junlin Mao; Xuebin Su; Liang Yuan (Hydrometallurgy, 2026)

Computational study on the hydrothermal cracking routes of N-cyclohexylnaphthalen-1-amine based on density functional theory - Shao-Xuan Zhong; Wei Li; Jia-Wei Qu; Ming-Lan Ge; Yuan-Liang Yang; Jian-Qiang Tao; Jing Wang (Fuel, 2026)

Seismic performance evaluation of concrete-encased steel tubular bridge columns with ductile flange connections - Jia-Ming Zhang; Qing-Hua Li; Jing-Zhong Tong; Yun-Long Chen; En-Yuan Zhang; Wei Gao; Shi-Lang Xu (Engineering Structures, 2026)

A deep learning and generative modeling pipeline for mining and engineering alkaline-stsable xylanases - Ruohan Zhang; Yiyang Zhang; Zhonghao Deng; Pengtao Wang; Lingxi Fan; Feng Guo; Huiying Luo; Yuan Wang; Tao Tu; Bin Yao; Jian Tian; Huoqing Huang; et al. (Bioresource Technology, 2026)

A Lab-in-Tube platform based on Ag+-coupled hairpin aptamer and gold nanoparticles-immobilized DNA hydrogel for portable and ultrasensitive biosensing - Zhaoying Liu; Yuan Kong; Kan Yang; Guangyun Chen; Ming Li (Analytica Chimica Acta, 2026)

A chiral metal-organic cage Al-CMOC for high-resolution gas chromatographic separation - Xiao-Fang Shu; An-Xu Ma; Fu Li; Chang-Xiu Ma; Jin Liu; Xu-Xu Jin; Sheng-Ming Xie; Bang-Jin Wang; Jia-Ni Yang; Jun-Hui Zhang; Li-Ming Yuan (Analytica Chimica Acta, 2026)

Forestation enhances soil organic carbon sequestration with divergent coupling mechanisms along aridity gradients - Nan Huang; Jie Yu Wang; Yuan Chen; Wen Ke Qin; Jia Xie Huang; Chang Ming Zhao; Jin Hua Li (Soil Biology and Biochemistry, 2026)

The GmCYCLOPS paralogs regulate soybean nodulation and exhibit signatures during domestication - Yuanting Lei; Zhi Liu; Qiang Chen; Xintong Wu; Ming Li; Fulong Liu; Yuzhen Liu; Zhitong Yin; Siyuan Zhao; Pengshuo Shen; Yuan Zhao; Sobhi F. Lamlom; et al. (Plant Science, 2026)

Caged xanthones with cytotoxic activity from the leaves and twigs of Garcinia oligantha - Xiao-Hui Peng; Sha Chen; Si-Yu Wang; Jin-Yuan Yang; Hao-Nan Li; Bin Lin; Hui-Ming Hua; Da-Hong Li (Phytochemistry, 2026)

A salt-tolerant dual-network hydrogel based on tea waste biochar for efficient seawater desalination - Kun-Xiu Liu; Yi-Bin Li; Lei Xu; Cai-Hua Liu; Zhu-Long Yu; Wen-Bo Guo; Ming-Lai Fu; Baoling Yuan (Journal of Environmental Chemical Engineering, 2026)

Evaluation of perfluorinated alkyl substance contamination of infant formula using covalent organic framework - Ming Yang; Yuan Yang; Han Xiao; Shoudao Li; Jun Yi; Zong Yang; Liuqing Zhao; Jia Xu (Food Research International, 2026)

Technological innovation: Aspergillus niger single-strain-fermented Pu-erh tea significantly regulates lipid metabolism and obesity in C57BL/6J mice - Bai-Yu Xie; Lan Cai; Xiao-Qin Zhu; Ming-Gang Li; Jiang-Yuan Zhao; Zhang-Gui Ding (Food Bioscience, 2026)

Constructing core-shell Si@C anodes via in-situ liquid-phase precipitation for high-performance lithium-ion batteries - Yuanjiang Dong; Yujie Zhang; Dan An; Baoqiang Li; Huacheng Jin; Xiaohong Ma; Zongxian Yang; Ming-Shui Yao; Fangli Yuan (Chemical Engineering Journal, 2026)

Highly selective NO2 sensing for mobile on-site monitoring enabled by a dual-sensitization mechanism in palladium sulfide-based nanocomposites - Yongjing Guo; Hangshuo Feng; Qiuni Zhao; Shenghui Guo; Renminxi Ou; Shunping Zhang; Zaihua Duan; Yi Xia; Zhen Yuan; Ming Hou; Li Yang; Huiling Tai (Chemical Engineering Journal, 2026)

Advanced oxidation and reduction processes for degradation of refractory organic pollutants: Mechanisms, catalysts, and redox coupling strategies - Xiaoyu Zhang; Xia Li; Le Fang; Shaoqing Liu; Jie Tang; Yuan Gao; Danfeng Yu; Yudong Sun; Yun Wang; Ming Zhou; Cheng Zhang; Wei Ouyang (Chemical Engineering Journal, 2026)

Unlocking the carbon sequestration potential of agricultural soils: Stoichiometric control of mineral-associated organic carbon saturation - Xiaopeng Shi; Tao Feng; Jianjun Yang; Xulong Zhang; Ming Zhang; Feng Zhang; Xiaojing Zhang; Anming Yuan; Feng-Min Li (CATENA, 2026)

Consistent functional genes in methanogens along soil profiles in a temperate marshland - Yuling Tan; Nannan Wang; Kexin Li; Yunjiang Zuo; Jianzhao Liu; Ziyu Guo; Ming Yang; Wenwen Tan; Yuedong Guo; Yanyu Song; Fenghui Yuan; Xiaofeng Xu; et al. (Soil Ecology Letters, 2026)

Dynamics and drivers of CO2 emissions in agricultural river-ditch networks: management and wetland degradation effects - Xia Li; Xiao-Dong Li; Si-Liang Li; Shi-Yuan Ding; Wan-Fa Wang; Li Bai; Min Xiao; Ming-Guo Wang; Xiao-Long Liu (Applied Geochemistry, 2026)

A lyophilized RPA–CRISPR/Cas13d one-pot platform for rapid detection of porcine circovirus type 3 - Li-Na Shao; Zheng-Luo; Bao-Ling Liu; Tong-Xu; Yuan-Meng Wang; Jia-Qi Duan; Lei-Zhao; You-You Li; Yang-Ming Dai; Qin-Rui Jia; Le-Yi Zhang; Ling-Zhu; et al. (Analytica Chimica Acta, 2026)

Kosakonia oryziphila KC516 mediated growth promotion of Cosmos bipinnatus in phosphogypsum by modulating rhizosphere geochemistry and root transcriptome - Jing Zhang; Hao-Tian Dong; Yuan-Chun Yang; Rui Liu; Shuai Wang; Ao-Li Zhang; Yuan Su; Ming-Hua Dong; Yan-Ru Cao; Hua-Li Zhang (Environmental Geochemistry and Health, 2026)

Coupled effects of water saturation and spatial heterogeneity on CO2 hydrate formation for safe and sustainable carbon storage - Yanfang Li; Tong Zhang; Ming Tang; Ruilong Li; Liang Yuan; Mingchao Wang (Process Safety and Environmental Protection, 2026)

Isodonoids A–L: Ent-kauranoid diterpenoid-flavanone conjugates from Isodon rubescens - Can-Can Wang; Meng-Yu Bao; Hui-Ying Li; Hao-Ming Xiong; Kei-Fong Ng; Li-Ping Bai; Wei Zhang; Zhi-Hong Jiang; Guo-Yuan Zhu (Phytochemistry, 2026)

Spatiotemporal magmatic records of Permian–Jurassic tectonism in the central-southern Tibetan Plateau: Reconstructing linkages and tectonic evolution between the Paleo- and Neo-Tethys Oceans - Cai-Cai Li; Wei Wang; Qing-Guo Zhai; Pei-Yuan Hu; Yue Tang; Yi-Ming Liu (Lithos, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

Unraveling the fruity aroma in soy sauce aroma Baijiu by pinpointing key aroma compounds and evaluating their sensory impact - Yu-Jie Li; Xiao-Juan Zhang; Lan Wu; Zhen-Ming Lu; Lu-Qin Tian; Yun-Hao Lu; Li-Juan Chai; Hong-Yu Xu; Xiao-Long You; Yuan-Long Chi; Feng Hu; Zheng-Hong Xu (Food Chemistry, 2026)

An implicit stabilized smoothed particle finite element method for dynamic large-deformation analysis in geomechanics - Wei-Hai Yuan; Chun-Jiang Li; Ming Liu; Ao-Xi Zhang; Wei Zhang (Computers and Geotechnics, 2026)

High-stability active thermal control for nanosatellite payload under multi-timescale disturbances via temperature response decomposition and energy-adaptive error fusion - Qi-Yuan Liu; Yun-Ze Li; Yan-Ao-Ming Xi; Kai-Feng Chang; Ya-Hui Chen; Ran Wei; Yu-Peng Zhou; Xin Zhao (Advances in Space Research, 2026)

Gut microbial dysbiosis in a Southern Chinese cohort of patients with Parkinson's disease - Yi Ming Li; Qiu Zhi Shao; Chih-Yuan Ko; Yunfei Chen; Donald Robert Haley; Hanadi Y. Hamadi; Mei Zhao (Antonie van Leeuwenhoek, 2026)

Unsaturated lactones from Aspergillus ochraceopetaliformis - Jing-Jie Bai; Hong-Qian Pan; Qiong Liu; Duo-Xiu Li; Bai-Chuan Zhu; Ying-Ming Zhang; Ai-Hong Zhao; Cheng-Shan Yuan (Natural Product Research, 2026)

SMART: Structured multimodal agricultural retrieval-augmented transformer for plant disease diagnosis - Yuan-Chia Chan; Yao-Chung Fan; Hung-Chung Li; Ming-Der Yang (Computers and Electronics in Agriculture, 2026)

Calcium-mediated catalytic ozonation for water purification: Synergistic interplay among surface acid-base sites, alkaline interfacial microenvironment and dynamic oxygen supplementation - Hong-Guang Li; Cheng Chen; Zhi-Hang Wu; Ai-Yong Zhang; Rui-Gang Zhang; Shao-Wei Yuan; Ming Du; Jing-Yu Zhang (Water Research, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Unexpected V-shaped temperature dependence of methane fluxes informing its sources in a megacity of China - Ruilin Zhang; Yibo Huangfu; Bin Yuan; Xiaoxiao Zhang; Xianjun He; Thomas Karl; Yang Ding; Hongjuan Li; Kyung-Eun Min; Ying Xiong; Xiao-Bing Li; Zhe Peng; et al. (Science Bulletin, 2026)

Electrochemical chlorination byproducts (ECBPs): A potential blind spot in electrochemical treatment of waste activated sludge - Dingkang Qian; Qian Zhu; Mengjiao Yuan; Ziming Xu; Jinwen Zhang; Na Li; Ming Peng; Liqiong Cao; Jianyu Gong; Jingping Hu; Huijie Hou; Jiakuan Yang; et al. (Journal of Hazardous Materials, 2026)

Spatial metabolomic profiling of ripening pepper fruit (Capsicum annuum L.) by MALDI-MSI: Decoding metabolic heterogeneity and its role in quality attribute regulation - Yuanling Yang; Chaochao Liu; Zhuping Yao; Chenxu Liu; Meiying Ruan; Rongqing Wang; Hongjian Wan; Qingjing Ye; Zhimiao Li; Ming Diao; Yuan Cheng (Food Chemistry, 2026)

Differential volatile-omics analysis for tamarind (Tamarindus indica L.) and aroma-active compounds identification via DMU-SPME-GC-MS method - Rui-Hua Jin; Ling Zhang; Li-Bo Qi; Chun-Mei Yuan; Zi-Bo Song; Jia-Teng Chen; Ming Du; Xian-Bing Xu (Food Chemistry, 2026)

Associations of residential green and blue space with risk of esophageal squamous cell carcinoma and gastric cancer: Mediating roles of air pollution - Xiaolin Yin; Zhen Li; Aiying Teng; Xiaorong Yang; Weimin Ye; Xingdong Chen; Yuan Zhang; Tongchao Zhang; Ming Lu (Environmental Research, 2026)

A heterotrophic nitrification and aerobic denitrification strain capable of antibiotic degradation: From function to mechanism - Jia-Ying Li; You-Wei Cui; Yuan Sui; Ji-Tao Yan; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Ze-You Lu (Environmental Pollution, 2026)

Citric acid treatment and bamboo-derived holocellulose nanofibers balance strength, flexibility, and barrier performance in PVA composite films - Yuan Liu; Chen-Xi Li; Jia-Xuan Long; Ming-Fei Li; Jing Bian; Feng Pen (Carbohydrate Polymers, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

A novel passive external surface heat flow balance strategy for high-temperature-stability nano CubeSat thermal design: concepts, models and thermal control effect evaluations - Yan-Ao-Ming Xi; Yun-Ze Li; Qi-Yuan Liu; Kai-Feng Chang; Xin Zhao; Yu-Peng Zhou; Ran Wei (Advances in Space Research, 2026)

Intermittent aeration-driven iron cycling for the remediation of waste pit-sealing mud: metabolic mechanisms and model evaluation - Xiangshan Zeng; Xinyi Wu; Dandan Yan; Changhui Hu; Jinlai Yuan; Ruiqi Li; Yan Wang; Ming Dou; Yafei Yang (Environmental Geochemistry and Health, 2026)

A Protective Role for Melatonin: Enhancing Heat Tolerance in Alisma plantago-aquatica Seedlings - Wen-hui Chen; Jiao Wang; Ke-yu Wang; De-qiang Li; Zi-zhong Tang; Yang-er Chen; Shu Yuan; Lu Zhang; Ming Yuan (Journal of Plant Growth Regulation, 2026)

Crowning the King of Fruits: Genomic Evidence of Population Structure and Relatedness in Malaysian Durians - Hung-Hui Chung; Li Yuan Liew; Adriana Batrisyia Mohd Faisal; Leonard Whye Kit Lim; Han Ming Gan (Tropical Plant Biology, 2026)

Postoperative Impairment of GluA2 Trafficking in CA3 Induces Memory Consolidation Deficits in Aged Mice by Disrupting SPW-R in CA1 - Zi-Qing Xu; Xiao-Wei Li; Gui-Cheng Wang; Xu Wang; Jiang-Nan Wu; Ming-Yu Wu; Ming-Hui Wu; Gong-Ming Wang; Meng-Yuan Zhang (Journal of Molecular Neuroscience, 2026)

IL-8-expressing recombinant Bacillus subtilis: A novel immunostimulant for improving production efficiency and disease resilience in Sebastes schlegelii aquaculture - Qing Yang; Hong-Yu Jiang; Ming-Tao Li; Bin-Tong Yang; Shu Li; Wei Cong; Yuan-Huan Kang (Aquaculture, 2026)

Cenozoic plant macrofossils and remains in Taiwan: A review of the literature and fossil record - Yuan-Po Lo; Ching-Yao Li; Jer-Ming Hu (Review of Palaeobotany and Palynology, 2026)

Persistent testicular glycogenolysis and active lipid metabolism during torpor in hibernating Siberian chipmunks - Zhe Wang; Lu-Fan Li; Yu-Jing Yan; Ming-Yan Yuan; Xiang-Yu Zhao; Li-Na Jiang; Xian-Feng Yi (Journal of Thermal Biology, 2026)

A new pathway to enhance the oceanic carbon sink: inorganic carbonate precipitation driven by calcium–alkali coupling - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Lei Li; Bao Xiao Qu; Qi Dong Wang; Jun Ma; Jian Wei Xing; Zhi Bo Wang; Rui Wang; et al. (Journal of Environmental Management, 2026)

A novel mitochondrial OMA1-DELE1-HRI axis mediates polystyrene microplastics-induced blood-testis barrier dysfunction - Rong Wang; Zhen Tian; Chen Chen; Ming-Ming Zhang; Ding-Qiang Peng; Ke-Xin Liu; Yu-Tong Ren; Shuai Lin; Qiang Hong; Yan-Li Ji; Yuan-Hua Chen (Journal of Environmental Sciences, 2026)

Short anti-aging peptides from edible microalgae using a multi-targets virtual screening strategy combined with Caenorhabditis elegans model - Yan-yan Yuan; Xin Li; Ming-hui Han; Xue An; Yong-Qiang Lin; Hong-Bing Liu (Food Research International, 2026)

Synergistic effects of sequential ultrasound and autoclaving treatments on the structure, functionality, and digestibility of chestnut starch varieties - Yuan-Yuan Zhang; Can Xu; Ming-Xue Tu; Yin-Ping Zhang; Cong-Hu Li; Liang-Liang Zhu; Ting Hu (Food Chemistry, 2026)

TCEP flame retardant linked to prostate cancer progression: Integrative analysis and novel biomarker discovery - Xin-Yang Li; Zi-Ming Wang; Si-Yuan Hu; Jia-Chun Sun (Environmental Pollution, 2026)

Experimental investigation·of damage constitutive model for granite under triaxial compression: Insights from acoustic emission technology and fractal theory - Yang Zhao; Yan-long Li; Lei She; Yuan Yao; Xiao-jing Li; Hao-teng Wang; Xin-jian Sun; Ming-ming He (Engineering Geology, 2026)

Discrete element insights into passive failure mechanisms and Non-Limit earth pressure development - Hao-Biao Chen; Ming-Guang Li; Zhou-Jun Ma; Qing-Yun Yuan; Jin-Jian Chen (Computers and Geotechnics, 2026)

Exploring primate immune responses to SLA-I/II knockdown pig xenografts in humanized mice and rhesus monkeys - Ming-Hui Fang; Hao Feng; Kai Xu; Tang Hai; Song Chen; Ji-Long Ren; Wei-Gang Wang; Yuan-Tao Wang; Jun Zou; Fei Xu; Zi-Yue Wang; Yi-Wei Yao; et al. (Science China Life Sciences, 2026)

Chrysophanol is associated with reduced inflammation and oxidative stress in sepsis-associated acute kidney injury - Xiaoxiao Li; Bingqing Ouyang; Mengdi Zhang; Haoran Sun; Hui Ye; Lijiao You; Weifang Yuan; Haikuo Wang; Hainan Yang; Kailang Xu; Ming Lei (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Temporal transcriptomic profiling identifies core regulators in cytokine-induced gut barrier disruption in differentiated Caco-2 cells - Hyo Shin Yoon; Shining Ma; Matt Kanke; Wan-Jung Wu; Uyen Hoang; Jessica A. Tan; Alex Wilks; Priyanka Patel; Sundeep Chandra; Xin Luo; Daniel Lu; Scott Martin; et al. (Inflammation Research, 2026)
Objective The intestinal epithelial barrier maintains gut homeostasis, and its disruption contributes to inflammatory diseases such as Inflammatory Bowel Diseases (IBD). Although barrier restoration is a promising therapeutic strategy, most current approaches target immune responses rather than epithelial function. Since barrier injury and repair progress through discrete phases, this study aimed to define time-resolved epithelial transcriptional programs and identify candidate regulatory nodes for barrier-focused therapeutic intervention. Methods Differentiated Caco-2 epithelial monolayers were used to model cytokine-induced barrier disruption and profiled by time-resolved bulk RNA-seq. Transcriptional dynamics and candidate regulators were identified using pairwise differential expression, likelihood-ratio testing, pathway enrichment, and upstream-regulator inference. Candidate nodes were tested by pharmacologic perturbation, and disease relevance was assessed by qPCR and histology in human IBD colon tissues. Results Time-resolved profiling revealed dynamic epithelial programs involving the Rho GTPase cycle, sirtuin signaling, non-canonical WNT signaling, and junction/EMT-associated pathways. Upstream-regulator inference highlighted JAK2, TNF, gasdermin D, and β-estradiol, and pharmacologic perturbation of these nodes mitigated cytokine-induced barrier loss. HNF4A emerged as a gut epithelial transcriptional hub regulating targets including SATB2 and SLC26A3. Notably, SLC26A3 was markedly reduced in IBD colon tissues. Conclusions This study provides a time-resolved epithelial framework and highlights therapeutic opportunities for barrier-focused interventions.

Climate stability shaped fire regimes over the past ∼1400 years in northeastern China - Yufeng Yuan; Xin Zhou; Yong Luo; Anze Chen; Lize Meng; Changchun Huang; Lian Liu; Xiaoyan Liu; Hongfei Zhao; Shiwei Jiang; Xuanqiao Liu; Ming Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Deep eutectic solvent-based three-phase partitioning of flaxseed cake meal polysaccharides for enzymatic production of bioactive oligosaccharides - Ruixue Hu; Jiayang Xu; Jie Mi; Kangning Li; Mingyang Yuan; Ruijie Liu; Ming Chang (Food Bioscience, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Effect of ether oxygen atom distribution in the polymer main and side chains on the lithium-ion conductivity of PEG-based polymer electrolytes - Zhiyu Chen; Hao Lei; Zhaoyang Wei; Weiwei Lei; Ke Wang; Jun You; Qunchao Zhang; Robert K.Y. Li; Ming Zhou; Qiang Yuan; Dean Shi (Chemical Engineering Journal, 2026)

New mesoporous UiO-66-OH framework with in-situ grown CsPbBr3 perovskite nanocrystals as a multifunctional sensor for the discrimination and instrument-free detection of three natural food additives - Hou-Qun Yuan; Qian-Wen Yang; Ling-Yi Guo; Yao-Hong Wang; Guan-Qun Li; Qiong-Yue Cui; Zhen-Chong Dou; Zhi-Qiang Cai; Yi-Fan Xia; Guang-Ming Bao (Chemical Engineering Journal, 2026)

Coupled influence of Western Pacific moisture anomalies and mid-tropospheric humidity on October precipitation in Yunnan Province Southwest China - Wen-Jun Sun; Zhen-Peng Tao; Zi-Yang Zhang; Tian-Qing Lan; Taohui Li; Peng Zi; Jian Zhang; Yao Wu; Ming-Qiang Liang; Chao-Jun Chen; Yuan-Yuan Mu; Jun-Yun Li; et al. (Atmospheric Research, 2026)

Improved eradication of apple stem grooving virus and apple chlorotic leaf spot virus in apple rootstocks by combining thermotherapy with electrotherapy - Xiao-Yan Ma; Qing Li; Zhi-Wei Kang; Ming-Yuan Jing; Ya-Ting Zhang; Min-Rui Wang; Dong Zhang; Lu Bao; Juan-Juan Ma (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Hydrodynamic impacts of floating-raft aquaculture in the northern yellow sea: modeling and field experiments - Xiaomeng Fu; Jie Tian; Ming Li; Yuan Zhang; Junru Guo; Jun Song; Yang Ding; Congcong Bi (Ocean Dynamics, 2026)

BLNN-based predefined-time control for spacecraft close-range proximity operations with actuator faults and unknown nonlinearities - Ming Li; Yuan Zhu; Lanjie Niu; Ke Zhang; Wang Li; Mingxuan Ren; Xin Ning (Advances in Space Research, 2026)

Metabolic inflexibility across heart failure phenotypes: mechanisms and type-specific therapeutic implications - Li Chen; Xin-Rui Yang; Yan Jiang; Shi-Qi Cheng; Zhen-Xun Wan; Jin-Wen Wu; Ming-Tai Chen; Yuan-Yuan Li; Gang Luo; Meng-Nan Liu (Apoptosis, 2026)

Microsphazaphilones H–Y: new azaphilone pigments with HIV latency reversal activity from the marine-derived fungus Microsphaeropsis arundinis P1B - Qing-Ren Lu; Xian-Yuan Yang; Lei Li; Lei-Ming Wu; Lu-Xiang Wan; Yi-Fan Fu; Xian-An Chen; Xin-Xiang Xu; Tao Yuan; Xin Chen; Abrar Ahmed; Nirmal Malik; et al. (Marine Life Science & Technology, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Distribution pattern and influencing factors of dehydrated sterols: processing degradation of phytosterol - Jie Mi; Mengyuan Zhou; Mingyang Yuan; Qidong Xue; Kangning Li; Ruijie Liu; Ming Chang (Food Chemistry, 2026)

Characterization of volatile aroma profiles and identification of key stale odorants in albino green tea during accelerated shelf-life storage - Yi-Ming Yang; Bin-Hui Liao; Jin-Miao Zhao; Ying-Gou Zhao; Xiao-Gan Chen; Wen-Han Fan; Li-Qing Mei; Si-Qi Zhang; Hao-Wei Guo; Shu-Ying Gong; Jing-Fei Zhang; Fang-Yuan Fan (Food Control, 2026)

Exploring biogeochemical processes through untargeted screening of solvent-extracted molecular signatures - Zhe-Xuan Zhang; Julian P. Sachs; Zhao Liang Chen; Ming Yuan; Zekun Zhang; Chen Zhao; Yuanbi Yi; Jiying Li; Ding He (Chemical Geology, 2026)

Engineering of Azotobacter chroococcum enables potential replacement of synthetic nitrogen fertilizer and mitigation of nitrogen pollutants release under medium-fertility field conditions - Ping Tian; Jun-Feng Wang; Dao-Yuan Wang; Yu-Dian Xun; Xiao-Hui Shi; Ming-Zhu Chen; Yun-Ying Liang; Mei-Ting Yang; Qu-Sheng Li (Bioresource Technology, 2026)

Influence of aerosols and clouds on diffuse radiation under complex sky conditions based on MFRSR - Huaping Li; Yaxin Wang; Ming Zhang; Lunche Wang; Chen Yuan (Atmospheric Research, 2026)

Herbiconiux dendrobii sp. nov., a Novel Bacterium Isolated from Dendrobium devonianum Sawdust Substrate - Hao Liang; Fang Zhao; Hong-Bo Zha; Zhang-Gui Ding; Le-Le Li; Jiang-Yuan Zhao; Zhi-Ran Zhao; Min Zheng; Jian-Sheng Cheng; Hui-Cheng Deng; Shu-Kun Tang; Ming-Gang Li (Current Microbiology, 2026)

The combination of Astragalus membranaceus and Lycium barbarum polysaccharides is superior to either alone in enhancing growth and health of grass carp (Ctenopharyngodon idellus) - Wei Zhang; Lin Ma; Yi-Geng Meng; Ke-Ming Liu; Hong-Qing Sun; Chao Cai; Ming-Ze Li; Yuan-Yuan Dai; Wen-Wen Li; Xin Luo; Nan Li (Animal Feed Science and Technology, 2026)

Development and evaluation of an antisense PCR assay for Toxoplasma gondii detection in domestic cats - Yu-Yuan Li; Shao-Yuan Bai; Hai-Qiong Yu; Li-Zhi Fu; Jia-Fu Zhu; Shi-Jie Fan; Ming Pan; Wei He; Si-Yang Huang (Veterinary Parasitology, 2026)

Effects of suspended sediment on the survival and settlement of Crassostrea ariakensis and Crassostrea sikamea larvae: Results from lab experiments - Nan-nan Li; Yu Han; Yuan-ge Chen; Wei-liang Dong; Long-ling Ouyang; Rui-liang Fan; Wei Jiang; Jia-feng Fang; Nian Wei; Jin-ming Wang; Wei-min Quan; Jian Zeng (Regional Studies in Marine Science, 2026)

Mechanism of antifungal protein extracts from Bacillus mojavensis against Penicillium expansum and its application in controlling blue mold of apple - Yuan Wang; Jingxuan Zhang; Wei Wang; Fan Chen; Yunle Guo; Ming Yang; Jiaoyang Li; Xing Guo; Yahong Yuan; Kewei Feng; Tianli Yue (Postharvest Biology and Technology, 2026)

Driving factors on bacterial community of heterotrophic nitrification and aerobic denitrification in real wastewater treatment plants: Evidence from different latitudinal gradients in warm season - Rui-Chun Yang; You-Wei Cui; Zhen-Ying Li; Yuan Sui; Tong Ren; Xin-Yu Gu; Ming-Xin Su; Ze-You Lu (Journal of Water Process Engineering, 2026)

Discovery and mechanistic insights into ACE inhibitory peptides from the gastrointestinal digest of royal jelly proteins: peptidomics, bioactivity profiling, in silico screening, and in vitro validation - Wanyu Yang; Xiaodi Hu; Tianrong Zhang; Ming Zhao; Qiongmin Li; Mengnan Sang; Jinling Fan; Yuan Zhao; Bin Zhang (Food Research International, 2026)

Pharmacokinetics, excretion and biotransformation of 3,5,6,7,8,3′,4′-heptamethoxyflavone and its mono-demethylated metabolites in rats - Konglong Feng; Ming Yuan; Guo Liu; Meng Kang; Xiaoqing Li; Chi-Tang Ho; Yong Cao (Food Research International, 2026)

Mitochondrial stress primed cGAS-STING activation synergized with NF-κB signaling for enhanced antitumor immunotherapy - Chengzhilin Li; Fanyu Yuan; LiHang Lou; Ziang Xu; Nianlei Zhang; Changshun Huang; Xinyu Wang; Wenyu Zhang; Tingjian Zu; Ming Xia; Runxiao Zheng (Chemical Engineering Journal, 2026)

Three-dimensional network binder achieves strong adhesion and rapid lithium-ion transport for practical Si/C composite electrode - Bowen Chang; Yuan Xiao; Tianmin Wang; Mengjia Wang; Mingui Li; Fu-Ming Wang; Qunjie Xu; Qiaoxia Li (Chemical Engineering Journal, 2026)

Cold Atmospheric Plasma as a Non-Thermal and Biocompatible Disinfection Strategy for Ultrasound Transducers - Ching-Yuan Lin; Kuan-Yi Lee; Dong-Jin Li; Mohd Yaqub Khan; Ming-Chen Wang (Journal of Medical and Biological Engineering, 2026)

Daphnoretin as a potent sortase A inhibitor effectively disarms drug-resistant Staphylococcus aureus infections - Yun Sun; Tong Zhao; Dongbin Guo; Peitong Jiang; Xinyao Liu; Zhangyu Du; Luanbiao Sun; Yuan Gao; Han Gao; Li Wang; Bingmei Wang; Ming Yan (World Journal of Microbiology and Biotechnology, 2026)

Numerical investigation on hydrodynamic characteristics of floating breakwater with wings using a coupled SPH method - Xin Chen; Ming-yuan Li; Peng-cheng Shi; Hong-lei Lyu; Jie Cui (Marine Georesources & Geotechnology, 2026)

Trace carbonyls in water reuse: Structure-dependent multi-barrier penetration and enhanced deep mineralization via dual-radical oxidation synergism - Yun-Peng Wu; Qian-Yuan Wu; Zi-Bo Jing; Yu-Ming Tian; Jiang-Lei Xiong; Mu-Da Han; Sheng-Mei Li; Er-Dong Wang; Wen-Long Wang (Water Research, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

Comprehensive evaluation on potentiality and key bacterial community of heterotrophic nitrification and aerobic denitrification in real wastewater treatment plants - Rui-Chun Yang; You-Wei Cui; Zhen-Ying Li; Ming-Teng Li; Yuan Sui (Process Safety and Environmental Protection, 2026)

A review of transcriptional control and adaptive functions in terpenoid biosynthesis: Focus on MYB regulatory networks - Sihui Guan; Zhuping Yao; Chenxu Liu; Rongqing Wang; Meiying Ruan; Hongjian Wan; Qingjing Ye; Zhimiao Li; Ming Diao; Yuan Cheng (Plant Science, 2026)

Chronological and climatic insights from Karst Cave Silt Sediment in Southwest China - Yuan-Yuan Mu; Qing-Duo Wang; Chang-Sheng Wang; Tian-Zhou Zhang; Shao-Qin Ma; Jing-Ming Yang; Hai-Cheng; Wen-Jun Sun; Jun-Yun Li; Yan-Min Dong; Lu-Peng Yu; Ting-Yong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Static magnetic field coupled with control of sludge retention time enhancing nitrogen removal via heterotrophic nitrification-aerobic denitrification - Ming-Xin Su; You-Wei Cui; Rui-Chun Yang; Yuan Sui; Xin-Yu Gu; Jia-Ying Li; Ze-You Lu (Journal of Water Process Engineering, 2026)

Three-dimensional WFAM for unsaturated hydraulic conductivity measurement: Theoretical derivation and numerical validation - Xiao-kang Li; Yuan-ming Lai; Xu Li; Wen-zhen Tang; Qin-guo Ma; Xiao-xiao Luo; Lun-yang Zhao (Journal of Hydrology, 2026)

Low doses of chlorothalonil cause testicular impairment in mammals through the antimicrobial-like mechanism - Han-Zhang Wang; Yi-Ming Xiong; Shi-Lin Song; Qian-Cheng Zhao; Xuan-Yue Chen; Jing-Ran Gao; Yuan-Yuan Li; Zhan-Fen Qin (Journal of Hazardous Materials, 2026)

Wolframite and cassiterite geochemistry deciphers W–Sn ore formation: A case study from the Zuoba quartz-vein tungsten deposit, South China - Kai-Han Zhang; Jun-Yi Pan; Pei Ni; Gen-Wen He; Lin-Lin Peng; Ming-Sen Fan; Yuan-Long Zhang; Wen-Sheng Li (Journal of Asian Earth Sciences, 2026)

Side-deep placement of controlled-release urea combined with alternate wetting and drying irrigation achieves sustainable intensification of rice production in the rice–wheat system - Yuan Wang; Li Zhang; Kai Ming; Lin Cao; Song Guo; Jiaming Lu; Ziwei Li; Weiling Wang; Can Zhao; Fengping Yang; Ke Xu; Hongcheng Zhang; et al. (Field Crops Research, 2026)

Decoupling detoxification from resource recovery: Mechanisms of organic electromigration control in bipolar membrane electrodialysis - Hao-Ran Yang; Zhi-Hua Yuan; Chang-Jiang Li; Yan-Fang Guan; Jiuyang Lin; Mohammad Younas; Xinfei Dong; Yi-Hong Jiang; Yu-Ming Zheng (Chemical Engineering Journal, 2026)

Oligosaccharide mapping analysis through UPLC-Orbitrap-HRMS and enzymatic hydrolysis from Polygonatum odoratum (Mill.) Druce - Qing-Hua Liu; Liu Yang; Yue Wang; Hao-Ming Xiong; Cai-Yun Wang; Guo-Yuan Zhu; Li-ping Bai; Zhi-Hong Jiang; Wei Zhang (Carbohydrate Polymers, 2026)

Optimizing hybrid breeding in Roscoea: heterosis and inheritance patterns with R. cautleoides as a key parent - Yuan-Yue Zhang; Ming-Chao Chen; Yi-Guo Li; Feng-Juan Mou (Euphytica, 2026)

The yield-biomass-water-environment nexus model unravels the plastic mulching film dilemma: Yield gains vs. environmental cascades in China’s cotton systems - Yifan Gu; Zixin Bian; Qianqian Shi; Ziyi Zhao; Haixia Li; Rui Li; He Peng; Ming Yang; Qingbin Yuan; Yufeng Wu (Agricultural Systems, 2026)

Reliable Rock Mass Classification for Tunneling: Hole-Level MWD Data Modeling with Cost-Sensitive Bagging - Yue-ming Yuan; Jin-rui Duan; Zhao Han; Yi-guo Xue; Zhi-ping Sun; Fan-meng Kong; Chuan-gui Li (Applied Geophysics, 2026)

Large Potential for CH 4 Mitigation and Yield Improvement in China's Paddies Through Locally Optimized N Management - Haoyu Qian; Zhengqi Yuan; Xiangcheng Zhu; Yuanfa Huang; Min Li; Jiarui Li; Yuxin Ren; Jinfei Feng; Shan Huang; Wenjun Dong; Feng Jin; Jiping Gao; et al. (Global Change Biology, 2026)
Nitrogen (N) management is critical for ensuring food security and mitigating greenhouse gas (GHG) emissions. In rice paddies, the effectiveness of N management in maximizing yields and minimizing N losses is highly dependent on local environmental conditions and thus varies widely across regions. However, the influence of optimized, site‐specific N management on methane (CH 4 ) emissions remains poorly quantified and is not reflected in current IPCC Tier 1 methodologies. Here, we synthesize data from multiregional field experiments and conduct a meta‐analysis to show that locally optimized N management practices—such as delayed fertilizer application, reduced N input, and deep placement—reduce CH 4 emissions from rice paddies by 16%–21%. The experiments further show that these practices suppress CH 4 emissions by lowering soil N availability and organic matter decomposition, thereby limiting substrates for methanogenesis. Combining survey data from 155 counties with machine learning models, we estimate that implementing optimized N strategies across China's rice‐growing regions could reduce CH 4 emissions by 16% while simultaneously increasing rice yields by 7%. These findings underscore the dual benefits of locally optimized N management for agricultural productivity and climate change mitigation, and provide a foundation for improving CH 4 emission estimates under diverse management regimes.

DEHP induces hepatic fibrosis through STAT3-SLC7A11-ROS axis - Siqin Liang; Zhiliang Xu; Xiaoxiang You; Tinghao Yuan; Jun He; Lei Mao; Anan Jin; Xinwen Zhou; Bo Yi; Ming Li; Qiang Tu; Bin Xu (Toxicology and Applied Pharmacology, 2026)

Suspensaditerpenes A–Q, anti-inflammatory labdane and nor-labdane diterpenoids from the seeds of Forsythia suspensa - Hui-Ying Li; Meng-Yu Bao; Hao-Ming Xiong; Can-Can Wang; Li-Ping Bai; Wei Zhang; Cheng-Yu Chen; Zhi-Hong Jiang; Guo-Yuan Zhu (Phytochemistry, 2026)

Alkalinity change induces succession of heterotrophic and autotrophic nitrifying bacterial communities: Comprehensive insights on the mechanism - Yuan Sui; You-Wei Cui; Rui-Chun Yang; Ya-Nan Mi; Xin-Yu Gu; Jia-Ying Li; Ming-Xin Su (Journal of Environmental Management, 2026)

Advanced composting simulation technologies: A systematic review of methodological frameworks and applications - Ming-xiao Li; Ning Wang; Yuan-yuan Xie; Mei-ying Ye; Bei-dou Xi; Wang-mi Chen; Qi Zhou; Jian-long Hu; Jia-qi Hou (Journal of Environmental Management, 2026)

A methionine sulfoxide reductase A homolog gene(msrA1)deficiency significantly attenuates the virulence of Nocardia seriolae - Su-Ming Zhou; Yu Liu; Li-Yun Jin; Yuan Gao; Fei Yin (Fish & Shellfish Immunology, 2026)

Multiple resonance thermally activated delayed fluorescence emitters containing novel S-based acceptor with narrowed FWHM and enhanced EQE - Xiao-Xue Xia; Guo Yuan; Feng-Ming Xie; Qiang Zhang; Yan-Qing Li; Ze Hua; Jian-Xin Tang; Xin Zhao (Chemical Engineering Journal, 2026)

Divergent roles of three glycerol-3-phosphate dehydrogenase isoforms in glycerol and lipid metabolism of Dunaliella salina and their implications for biodiesel production - Jv-Liang Dai; Ling Xiao; Yue-Li Yuan; Ming-Hua Liang; Jian-Guo Jiang (Bioresource Technology, 2026)

Experimental and numerical investigation of a thermal diode double phase change wall for energy-efficient building envelopes - Yahui Gao; Tingzhen Ming; Hanbing Xiong; Jiyuan Zhou; Xitong Yuan; Wenyu Li; Wenting Lin; Yongjia Wu (Building and Environment, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Psychromicrobium ferritrahens sp. nov., A Novel Actinobacterium Isolated from Decayed Wood in Shizong County, China - Lin-Bo Zhang; Jiang-Yuan Zhao; Yong-Jie Zeng; Hong-Bo Zha; Lin Gong; Pei-Wen Yang; Zhang-Gui Ding; Ming-Gang Li; Shun-Bo Gao; Le-Le Li; Shu-Kun Tang (Current Microbiology, 2026)

Characterization and production optimization of genistein by the novel endophytic fungus Aspergillus sydowii J11 isolated from pigeon pea (Cajanus cajan) and its antibacterial and antioxidant properties - Bin-bin Li; Xuexia Gao; Min Lv; Wen-juan Ning; Jing-tao Liang; Xin-yu Fan; Xin-ming Lv; Jin-feng Song; Xiao-han Yuan; Cheng-bo Gu (Biotechnology Letters, 2026)

Benazepril Promotes the Proliferation and Differentiation of Urine-Derived Stem Cells from Children with Nephrotic Syndrome During the Chronic Kidney Disease Stage - Chengqiang Huang; Yuan Yang; Cheng Li; Ling Guo; Ming Liu; Geng Xiong (Biochemical Genetics, 2026)

Genetic origins and climate‐induced erosion in economically important Asian walnuts - Peng‐Zhen Fan; Guang‐Fu Zhu; Moses C. Wambulwa; Richard I. Milne; Zeng‐Yuan Wu; Ya‐Huang Luo; Robabeh Shahi Shavvon; Alistair S. Jump; Debabrata Maity; Lian‐Ming Gao; Hai‐Ling Qi; Hong‐Yu Wu; et al. (Conservation Biology, 2026)
The global climate is undergoing unprecedented changes, posing significant threats to species persistence. However, the spatiotemporal impacts on genetic diversity remain poorly understood, hindering species conservation and management. Walnuts, generally referred to as Juglans regia and J. sigillata , are economically vital in Asia, but little is known about their genetic origins and how the species will be affected by future climate change. Using 31 microsatellites, we genotyped 5282 individuals from 233 populations of walnuts in Asia. We assessed genetic diversity patterns and demographic history and investigated potential future genetic erosion risks. Genetic diversity of walnuts was high in the Himalaya and Hengduan Mountains. The 2 species diverged during the Pleistocene (around 1.41 Ma BP), and J. regia contained 2 genetic groups (JR1 and JR2). The JR2 group had the lowest diversity and likely arrived in northern China around 9.77 ka BP, perhaps via human transport. The Western Himalaya likely served both as a glacial refugium and the center of origin for J. regia , and the Eastern Himalaya appears to have been the refugium for J. sigillata . The 2 species appear to have hybridized in the Central Himalaya and the Sichuan basin and surroundings, forming two distinct hybrid zones. Our results indicate that genetic diversity will be reduced by up to 9.03% due to range loss under future climate change and dramatic genetic structure turnover in the Himalaya and Hengduan Mountains. In situ conservation in the Himalaya is essential for safeguarding genetic diversity and adaptive potential in Asian walnuts, while ex situ preservation of genetically unique wild germplasm, coupled with its integration into breeding programs, will enhance climate resilience. The findings advance our understanding of the origin of Asian walnuts and how future climatic change may affect their genetic diversity, offering a model for conservation and breeding strategies in other tree species facing similar threats.

Study on Hydrodynamics and Water Exchange Capacity in the Changhai Sea Area Based on the FVCOM Model - Minghao Yang; Jun Song; Congcong Bi; Dawei Jiang; Ming Li; Yuan Zhang; Junru Guo; Jie Tian; Qian Sun (Journal of Marine Science and Engineering, 2026)
Water exchange capacity is critical for maintaining marine environmental quality and supporting the sustainable development of aquaculture. This study applies a high-resolution three-dimensional FVCOM hydrodynamic model coupled with the DYE-RELEASE module. The model was validated against tidal, current, and thermohaline observations. Water residence time (Tre) was used as the primary evaluation metric, supplemented by analyses of residual circulation, material diffusion, and regional variability, to systematically quantify the water exchange mechanisms and seasonal variations in the coastal waters of Changhai County under the combined influence of tides, wind forcing, and thermohaline conditions. Results show that overall residual currents in Changhai County are weak (average velocity: 0.032 m s−1). However, local circulations and stagnation zones frequently develop near islands and channels, strongly influencing material diffusion. In summer, water exchange is primarily controlled by thermohaline effects, which strengthen density stratification, suppress vertical mixing, and modify circulation patterns, thereby reducing the efficiency of tide-driven exchange. Water exchange is weakest near Guanglu Island (46.6–48.6 d) and strongest near Haiyang Island (13–14 d). In winter, wind forcing dominates, enhancing vertical mixing and accelerating water renewal. Residence time in the Changshan Archipelago–Guanglu Island region decreases by 30–50% compared with summer. Overall, winter water renewal is 15–25% more efficient than in summer. This study demonstrates that water exchange in Changhai County is regulated by the combined effects of tides, wind forcing, and thermohaline dynamics. The identified spatial heterogeneity and seasonal characteristics provide a scientific basis for optimizing aquaculture planning and mitigating marine environmental risks.

Structural characterisation of a novel polysaccharide from pseudostellaria heterophylla fibrous root and its anti-inflammatory and antioxidant activities in vitro - Meng-Yu Li; Hai-Tian Deng; Ming-Zhu Ye; Li-Li Lu; Hong-Yuan Chen; Wen Rui (Natural Product Research, 2026)

Carboxymethyl cellulose-stabilized microbial synthesis of FeS-based biocomposite materials: Synthesis, characterization and photocatalytic reduction of hexavalent chromium - Ming Fan; Xilin Li; Ling Liu; Meini Wu; Shuhua Wang; Wei Ji; Yuan Gao (Water Research, 2026)

Cloud numerical computing: Informative support calculation for railway tunnels using data-driven numerical simulation and blocking sub-threaded HTTP protocol - Shuo Yuan; Li Yu; Hao Zhong; Ming-Nian Wang; Si-Ming Tian (Tunnelling and Underground Space Technology, 2026)

A persistently active fast radio burst source embedded in an expanding supernova remnant - Chen-Hui Niu; Di Li; Yuan-Pei Yang; Yuhao Zhu; Yongkun Zhang; Jia-Heng Zhang; Zexin Du; Jumei Yao; Xiaoping Zheng; Pei Wang; Yi Feng; Bing Zhang; et al. (Science Bulletin, 2026)

Pan-Arctic winter sea ice classification using Sentinel-1 dual-polarized SAR images - Yan Dai; Xiao-Ming Li; Haotian Yuan (Remote Sensing of Environment, 2026)

Enhancement role of corncob slow-release carbon source on heterotrophic nitrification and aerobic denitrification process in low C/N wastewater treatment - Xin-Yu Gu; You-Wei Cui; Yuan Sui; Jia-Ying Li; Ming-Xin Su; Ze-You Lu; Rui-Chun Yang (Journal of Environmental Management, 2026)

Endogenous metabolism and electricity conversion of organic clogging substances in constructed wetland microbial fuel cell - Chao Li; Dongxu He; Quan Yuan; Jiashun Cao; Jingyang Luo; Ming Xu; Hongqiang Ren (Environmental Research, 2026)

Accurate prediction and screening of Ni-based bimetallic catalysts for hydrogen production from biogas reforming: An interpretable machine learning study - Wen-ming Zhang; Bin Hu; Bo-yuan Zheng; Ji Liu; Qi Niu; Kai Li; Zhi-mo Fang; Bing Zhang; Qiang Lu (Chemical Engineering Journal, 2026)

Self-amplifying tumor-targeting nanoreactor for enhanced Immuno-Ferroptosis therapy in triple-negative breast cancer - Jiayin Li; Yazhou Wang; Hao Li; Zhongyue Yuan; Qin Wei; Lei Yang; Yan-ming Xia; Xiaofei Xin; Lisha Liu; Chao Teng; Chao Qin; Xiaopeng Han; et al. (Chemical Engineering Journal, 2026)

Numerical investigation of hill shape on flow characteristics in hilly cities - Hao Zhu; Jianhan Yu; Theodore Potsis; Ming Li; Yuan Jiang; Shaopeng Li (Building and Environment, 2026)

Advancing high-resolution hourly PM2.5 forecasting with a hybrid framework integrating numerical simulation and machine learning - Yuan Liu; Zizheng Li; Pablo E. Saide; Ming Zhang; Qingqing He (Atmospheric Research, 2026)

Microscopic probing into plasmodesmata (PD) and PD-derived intercellular gateways (PdIGs): Beyond morphology - Ming-fang Lv; Wei-na Shang; Yuan-xing Dai; Jun-ying Li; Yi Li; Shuai Fu; Jian Hong; Li Xie; Heng-Mu Zhang (Protoplasma, 2026)

Single-Cell RNA Sequencing Reveals Impaired CHIP-Mediated Heat Stress Response in SCA3 Pathogenesis - Mi-bo Tang; Shi-feng Sheng; Zheng-wei Hu; Hai-yang Luo; Meng-jie Li; Shuo Zhang; Xiao-yan Hao; Cheng-yuan Mao; Shao-hua Li; Hui-fang Sun; Zhi-hua Yang; Yi Song; et al. (Molecular Neurobiology, 2026)

Enhanced DNA cryogel platform: Dual-RCA-Driven coloration in situ for portable biosensing - Yuan Kong; Zhaoying Liu; Guizhu Wu; Xiaoyong Liu; Song Fang; Kun Zeng; Zhen Zhang; Ming Li (Analytica Chimica Acta, 2026)

Performance of heavy metals in the intertidal zone surface sediments of the Yellow River Estuary under water-sediment regulation scheme - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Ma; Feng Min Pan; Jian Wei Xing; Chen Long Feng; De Tong Tian; Zhi Bo Wang; Rui Wang (Marine Pollution Bulletin, 2025)

Spatial-interaction-context and temporal-attention U-Net model for spatio-temporal prediction of Sea Surface Temperature field - Jiaming Ma; Jun Song; Junru Guo; Yanzhao Fu; Yu Cai; Yuan Zhang; Jie Tian; Ming Li (Regional Studies in Marine Science, 2025)

Dynamic characteristics of a novel floating offshore photovoltaic system with flexible rope-net connection - De-Qing Zhang; Hong-Wei Tian; Zhi-Ming Yuan; Shuang-Rui Yu; Jun-Feng Du; Hua-Jun Li (Ocean Engineering, 2025)

Rapid electrochemical fabrication of MOF-coated mesh membranes with complementary wettability for high-efficiency oil-water separation - Yi-Le Chen; Wei Shao; Xiao-Feng Zhong; Si-Yuan Yang; Zi-Meng Xu; Jia-Jun Sun; Gang-Jun Chen; Pan-Pan Zhang; Yi Li; Ming Xue (Journal of Hazardous Materials, 2025)

Optimizing molecular distillation film scraper by CFD and experiment: VE extraction from SODD - Mengyuan Zhou; Ziwei Yu; Qidong Xue; Peng Zhang; Zhengzhang Wu; Jie Mi; Kangning Li; Mingyang Yuan; Ruijie Liu; Ming Chang (Innovative Food Science & Emerging Technologies, 2025)

Experimental study on reinforcement and remediation of nickel-contaminated sludge using grouting vacuum preloading combined with electroosmosis - Peng Wang; Ming Li; Zhuoxuan Wu; Jun Wang; Guohui Yuan; Xianfeng Huang; Jianfeng Wu (Geotextiles and Geomembranes, 2025)

Influence mechanism of fixation on the development of green tea flavor and related non-volatile and volatile metabolites by objective quantification, widely targeted metabolomics, and aroma metabolomics - Jinjie Hua; Xiwang Li; Chun Zou; Liyue Yang; Wen Ouyang; Ming Chen; Xinxin Lv; Fenglan Zhang; Xizhe Zhu; Ting An; Jinjin Wang; Jiayi Zhu; et al. (Food Chemistry, 2025)

Effects of geographical origin, processing and their interaction on stable isotopes in Pu-erh tea for traceability - Yanlong Li; Hai-Dan Zou; Xiao-Li Wang; Ming-Ming Chen; Bo-Wen Zhang; Wen-Fang Wang; Jie Li; He-Yuan Jiang; Li-Li Qian; Hong-Yan Liu (Food Chemistry, 2025)

Peptide profiling and antioxidant characterization of the simulated gastrointestinal digest of hemp seed proteins - Mengyuan Zhang; Tianrong Zhang; Chen Chen; Wanyu Yang; Ming Zhao; Qiongmin Li; Jiayuan Tian; Yuan Zhao; Bin Zhang (Food Chemistry, 2025)

Flux measurements of NOx, O3 and Ox: Emission characteristics, inventory validation and titration effects - Xiaoxiao Zhang; Bin Yuan; Yibo Huangfu; Huizhi Liu; Thomas Karl; Ming Chang; Shiyi Chen; Tao Song; Jintai Lin; Guannan Geng; Hongjuan Li; Eran Tas (Environmental Pollution, 2025)

Effects of UHPC age and interfacial treatment on structural behavior of post-cast UHPC joints in prefabricated wall-base slab assemblies - Ding-Li Jin; Yong Yuan; Shou-Ming Zheng; Giovanni Muciaccia; János Lógó; Jiao-Long Zhang (Engineering Structures, 2025)

Machine learning-aided design of adapted water treatment adsorbents: Advances, challenges, and opportunities - Ling Yuan; Sheng Li; Yujia Ma; Han Zhang; Chen Chen; Weiming Zhang; Yanyang Zhang; Ming Hua; Lu Lv; Bingcai Pan (Chemical Engineering Journal, 2025)

The effect of sulfamethoxazole on the performance of four types of constructed wetlands: Insights into microbial response characteristics, enzyme activities, and functional genes - Ming Xu; Heng Zhang; Chuan Li; Zhi-yuan Chen; Xiao-xiao Shen (Chemical Engineering Journal, 2025)

Trend in chemical components and sources of PM2.5 and its relationship with ozone in central PRD, China (2018–2023) - Jianfan Yin; Shan Huang; Yunqian Liao; Zihan Li; Bin Yuan; Ming Chang; Weiwen Wang; Xiongzhou Lv; Xihua Li; Shuzhen Su; Xuemei Wang; Min Shao (Atmospheric Environment, 2025)

Genome-Wide Identification and Expression Analysis of β-Ketoacyl-CoA Synthase Family in Sugarcane (Saccharum spontaneum) - An-zi Li; Xin Peng; Yuan Huang; Zhao-fu Bi; Ming-jing Liao; Mu-qing Zhang; Sheng-hua Xiao (Tropical Plant Biology, 2025)

Association of Serum Neurofilament Light and Glial Fibrillary Acidic Protein with Cerebral Small Vessel Disease in Nondemented Middle-to-Old Aged Population - Xiao-Hong Huang; Feng Gao; Jing Yuan; Ding-Ding Zhang; Mei-Jun Shu; Fei-Fei Zhai; Fei Han; Ming-Yu Tang; Ming-Li Li; Li-Xin Zhou; Jun Ni; Ming Yao; et al. (Translational Stroke Research, 2025)

Conditional QTL/QTN mapping for seed width and mining candidate genes based on soybean FW-RIL population - Xu Wang; Bo Hu; Hong Xue; Ming Yuan; Quanzhong Dong; Wen-Xia Li; Zhimin Dong; Hailong Ning (Molecular Genetics and Genomics, 2025)

Satb2 Ablation Impairs Hippocampus-Based Long-Term Spatial Memory and Short-Term Working Memory and Immediate Early Genes (IEGs)-Mediated Hippocampal Synaptic Plasticity - Ying Li; Qiang-Long You; Sheng-Rong Zhang; Wei-Yuan Huang; Wen-Jun Zou; Wei Jie; Shu-Ji Li; Ji-Hong Liu; Chuang-Ye Lv; Jin Cong; Yu-Ying Hu; Tian-Ming Gao; et al. (Molecular Neurobiology, 2025)

Self-repair mechanisms of spiking neuron–astrocyte networks in working memory under diverse injury conditions - Bingyi Mo; Xiaoqian Liu; Lin Li; Shanshan Cheng; Yuan Zhu; Ming Yi; Lulu Lu (Cognitive Neurodynamics, 2025)

A standard for geological evaluation of urban underground space resources in the Beijing plain - Han-han He; Cheng-shan Wang; Jing He; Yuan-xin Zhou; Lei Wang; Stuart Marsh; Chao Li; Tong-ming Fang; Fang-zhen Li; Sheng-li Cao; Jing Liu; Yi-ting Zhao (Bulletin of Engineering Geology and the Environment, 2025)

A Review of Paleoenvironmental Reconstruction Using Crater Lake Sediments in Monsoonal China - Xuanqiao Liu; Shiwei Jiang; Luyao Tu; Dorcas B. Oyebanji; Xiaoyan Liu; Yufeng Yuan; Xiangzhong Li; Ming Ji; Guangcheng Zhang; Xin Zhou (Journal of Earth Science, 2025)

Transforming residual biomass of Irish red seaweed Asparagopsis taxiformis and Palmaria palmata into biosorbents for methylene blue adsorption - Weihao Meng; Ruipeng Zhang; Siwei Gu; Ming Zhao; Jiani Luo; Colm P. O'Donnell; Yuan Li; Hongnan Sun; Taihua Mu; Marco Garcia-Vaquero (Algal Research, 2025)

Plumbagin disrupts the mature biofilm of Staphylococcus aureus - Hui Yuan; Ming Lu; Chen Shi; Chunshuang Li; Ze Yao; Hui Shang; Xiang Li; Heshui Yu; Songtao Bie (Biofouling, 2025)

Neuroprotective Effects of Glucosamine in Huntington’s Disease Through NLRP3 Inflammasome Inhibition - Lichieh Julie Chu; Yi-ting Hsu; Yu Aoh; Chih-Yuan Cheng; Hui-Hsuan Wang; Ming-Tse Wu; Hao-Hsuan Li; Xiu-Yuan Lai; Kuo-Feng Hua; Chiung-Mei Chen; Tz-Chuen Ju (Journal of Neuroimmune Pharmacology, 2025)

Decoding impact of antibiotics stress to nitrogen removal in constructed wetlands: Overestimated? - Jianghui Feng; Zhikun Zou; Zhiyong Zhang; Haiyan Li; Baoling Yuan; Ming-Lai Fu (Water Research, 2025)

Structural insight into GPR155-mediated cholesterol sensing and signal transduction - Delin Li; Xiaokang Zhang; Jie Feng; Yufeng Xie; Pu Han; Ming He; Lin Hao; Tianling Guo; Xiaoyi Bai; Kai Yuan; Junqing Sun; Xuefei Pang; et al. (Science Bulletin, 2025)

CO2 hydrate sequestration in unsealed submarine sediments: A 4D pore-scale experimental investigation - Yanfang Li; Tong Zhang; Liang Yuan; Ming Tang; Ruilong Li; Yongqiang Chen; Wen Luo; Chuanjiu Zhang (Gas Science and Engineering, 2025)

Positively correlated singlet and triplet hybridization governed by excited-state energy alignment in organic photovoltaics - Yue Ren; Li-Yuan Peng; Hou Tong; Ming-Yang Li; Xue Wu; Guang-Yan Sun (Chemical Engineering Journal, 2025)

Intermediate-entropy metal hexagonal nanoplates for high-performance and durable formic acid electrooxidation - Shengming Li; Hu Yang; Xin Cheng; Jie Zheng; Yuan Liu; Chengwei Deng; Feng Ji; Sisi Liu; Ming Ge; Xiaolei Yuan (Chemical Engineering Journal, 2025)

Signal molecule-mediated algae-bacteria interactions and membrane-enabled separation synergize wastewater bioremediation - Kai-Yuan Li; Jin-Long Zhou; Ashiwin Vadiveloo; Jia-Nan Li; Dan Zhou; Jia-Ming Wang; Ci Zhang; Yi-Lin Xie; Dong-Zhi Chen; Feng Gao (Chemical Engineering Journal, 2025)

Waste biomass-derived organic matter for sustainable soil remediation: Enhancing heavy metal removal and eluent reuse in agricultural application - Shuai Yang; Chen Tu; Guo-ming Liu; Yuan Li; Yi Wang; Xia Zhu; Shao-cheng Si; Run-lai Luo; Zhong-yuan Li; Yong-ming Luo (Bioresource Technology, 2025)

Dysfunction of cerebrospinal fluid circulation and neurovascular decoupling in end-stage renal disease patients with mild cognitive impairment - Zhaoyao Luo; Lurui Bo; Xinyi Zhu; Qiange Zhu; Huijie Yuan; Wen Gu; Peng Li; Yihao Peng; Xiang Chen; Ming Zhang; Shaohui Ma; Junya Mu (GeroScience, 2025)
End-stage renal disease (ESRD) patients frequently experience mild cognitive impairment (MCI), which significantly affects their quality of life. Although dysfunctions in cerebrospinal fluid (CSF) circulation and neurovascular coupling (NVC) have been implicated in cognitive impairment, their interrelationship remains unclear. This study aimed to investigate the association between CSF circulation dysfunction and NVC disruption in ESRD patients with MCI. We enrolled 68 ESRD patients with MCI and 65 healthy controls (HCs). CSF circulation was assessed using choroid plexus volume (CPV), the diffusion tensor imaging along the perivascular space (DTI-ALPS) index, and perivascular space volume fraction (PVSVF). NVC was evaluated using coupling metrics between cerebral blood flow (CBF) and resting-state functional magnetic resonance imaging (MRI) indicators: amplitude of low-frequency fluctuation (ALFF), fractional ALFF (fALFF), and regional homogeneity (ReHo). Cognitive performance was measured using a battery of neuropsychological tests. Compared to HCs, ESRD patients showed significantly increased CPV ( P < 0.001) and enlarged PVSVF ( P < 0.05), along with a decreased DTI-ALPS index ( P < 0.01). Global and regional NVC metrics were significantly reduced in ESRD patients ( P < 0.001). Moreover, regional NVC metrics were negatively correlated with CPV. Mediation analysis further revealed that CBF-ReHo coupling in the left cingulate gyrus pregenual area 32 mediated the relationship between elevated LCPV and cognitive decline. These findings suggest that CSF circulation dysfunction and impaired NVC are interrelated in ESRD-MCI. Disruption of CSF circulation may contribute to cognitive decline by impairing NVC, highlighting both as potential targets for early diagnosis and intervention in ESRD-related cognitive impairment.

NR4A1 mediates PRRSV-induced ileal injury in piglets by transcriptional regulation of NLRP3 - Fanfan Meng; Chuyang Zhu; Cuipeng Zhu; Long Yuan; Chenhui Li; Ming'an Sun; Demin Cai (Veterinary Microbiology, 2025)

Efficacy of a non-recombinant NADC34-like PRRSV-2 vaccine candidate against a recombinant NADC34-like PRRSV-2 isolate - Ming Qiu; Shuai Li; Meng Cui; Shuai Yang; Xiaoyang Zhu; Yifan Meng; Yanhan Lin; Hong Lin; Zhe Sun; Yuan Wang; Sen Jiang; Wanglong Zheng; et al. (Veterinary Microbiology, 2025)

Strategies for smoke control in tunnel fires: Approaches from numerical and experimental studies - Chin-Feng Chen; Hsin-Hsiu Ho; Ping-Jung Li; Yuan-Ming Chiu; Chih-Yuan Weng; Yu-Jen Chen (Process Safety and Environmental Protection, 2025)

Eleven undescribed sesquiterpenoids with multiple skeleton types and cytotoxicity from the South China Sea soft coral Lemnalia sp. - Yuan Zong; Jun-jie Yang; Hui-ming Zhang; Lin-lin Li; Ping-lin Li (Phytochemistry, 2025)

Discovery of the rare dimeric guaianes and their monomers from the Daphne penicillata Rehd - Tian-Ming Lv; Zhi‐Yuan Li; Li-Li Lou; Le Chen; Xiao‐Xiao Huang; Shao‐Jiang Song (Phytochemistry, 2025)

Two new compounds from the root bark of Acanthopanax gracilistylus and their inhibitory effects on neutrophil elastase, cyclooxygenase-1, and cyclooxygenase-2 in vitro - Jin-Yuan Duan; Shu-Ming Li; Hao-Dong Yang; Yuan-Gui Yang; Jiao-Feng Wu; Jing-Yu Weng; Hong-Bo Liu; Hong-Bo Xu (Phytochemistry Letters, 2025)

Uncertainty-based assessment of ice loads for ship navigation in ice floe environments - Ji-Ming Luo; Xing-Hui Li; Ze-Wen Yang; Yu-Chao Yuan; Wen-Yong Tang (Ocean Engineering, 2025)

SIRT3 promotes mitophagy to attenuate fumonisin B1-induced chicken hepatocyte senescence and antagonism of lycopene - Yuan-Hang Chang; Ming-Shan Chen; Hong-Mei Zhu; Rui-Qi Liu; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yue Cheng; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Overshoot, potential air pollution co-benefits and food shortages - Li-Jing Liu; Qiao-Mei Liang; Felix Creutzig; Hua Tong; Yu-Xuan Xiao; Xiang-Yan Qian; Hao Wang; Si-Yi Wei; Xiao-Chen Yuan; Biying Yu; Lan-Cui Liu; Yi-Ming Wei (Global Environmental Change, 2025)

Corrigendum to “Visualizing the spatial distribution of metabolites in tomato fruit at different maturity stages by matrix-assisted laser desorption/ionization mass spectrometry imaging” [Food Res. Int. 206 (2025) 115973] - Sihui Guan; Chaochao Liu; Zhuping Yao; Chenxu Liu; Meiying Ruan; Rongqing Wang; Qingjing Ye; Hongjian Wan; Zhimiao Li; Guozhi Zhou; Ming Diao; Yuan Cheng (Food Research International, 2025)

Corrigendum to “Dynamic changes in volatile organic compounds of cherry tomato fruits during storage at different temperatures using HS-GC-IMS” [Food Res. Int. 218 (2025) 116790] - Sihui Guan; Fei Yang; Jinxiao Yao; Chaochao Liu; Rongqing Wang; Meiying Ruan; Zhuping Yao; Chenxu Liu; Hongjian Wan; Zhimiao Li; Ming Diao; Yuan Cheng (Food Research International, 2025)

Dynamic changes in volatile organic compounds of cherry tomato fruits during storage at different temperatures using HS-GC-IMS - Sihui Guan; Fei Yang; Jinxiao Yao; Chaochao Liu; Rongqing Wang; Meiying Ruan; Zhuping Yao; Chenxu Liu; Hongjian Wan; Zhimiao Li; Ming Diao; Yuan Cheng (Food Research International, 2025)

A ratiometric fluorescent probe for sensitive detection of benzoyl peroxide and hypochlorite in food - Shun-Qiang Cui; Xin-Yi Liang; Zhi-Qiang Cai; Hou-Qun Yuan; Qiu-Yu Zhang; Yi-Fan Xia; A.K.I.M.A.N.A. Sandra; Ling-Yi Guo; Ran Wang; Shi-Yu Zhao; Yan-Xia Li; Guang-Ming Bao (Food Chemistry, 2025)

Polyacrylic acid promotes anti-passivation and electron-donation of boronized nanoscale zero-valent iron during groundwater remediation - Zelong Zheng; Lihang Ma; Xiaobin Liao; Ming-Lai Fu; Baoling Yuan; Xiao-yan Li; Yi-bo Hu (Chemical Engineering Journal, 2025)

Selectively passivated core-satellite cobalt-iron bimetallic phosphide with optimized ⁎OH adsorption for boosting oxygen evolution reaction - Baoshan Liu; Wangshu Zheng; Zhaoxi Zhang; Jiarui Yang; Yanqi Yuan; Feng Li; Jing Liu; Liping Zhao; Ming Wen; Han Chen; Peng Zhang; Lian Gao (Chemical Engineering Journal, 2025)

Proteome Profiling of Serum Reveals Pathological Mechanisms and Biomarker Candidates for Cerebral Small Vessel Disease - Yun-chao Wang; Hang-hang Zhu; Liu-Chang He; Ya-ting Yao; Lei Zhang; Xin-li Xue; Jing-yi Li; Li Zhang; Bo Song; Chang-he Shi; Yu-sheng Li; Yuan Gao; et al. (Translational Stroke Research, 2025)

Recessive variants in TWNK cause syndromic and non-syndromic post-synaptic auditory neuropathy through MtDNA replication defects - Xue Gao; Ying Ma; Wei-Qian Wang; Guo-Jian Wang; Kun Yang; Jin-Cao Xu; Sha-Sha Huang; Xiang Wang; Li-Min Hu; Xi Wang; Qiu-Quan Wang; Zhen-Dong Wang; et al. (Human Genetics, 2025)

Precise Prediction and Tiered Mitigation Strategies for Thermal Hazards in Deep Mines: A Data-Driven Approach Applied to Shicaocun Coal Mine - Feng-yuan Lv; Hao-nan Li; Qi-ming Wei; Yan-zi Lei; Long Chen; Yan-bin Yang; Biao Zhao; Yu-liang Sun (Applied Geophysics, 2025)

The effects of pond purification system on intestinal function of channel catfish (Ictalurus punctatus): a focus on intestinal development, digestion and absorption, and junction integrity - Zhong-Bing Zheng; Yu Yang; Jun Liu; Ming-Cheng Zhou; Ju-Hua Li; Long-Jiang Tang; Hai-Long Nie; Kang-Sheng Chen; Feng Liu; Xiang-Ning He; Zhi-Yuan Lu (Frontiers in Marine Science, 2025)
Pond purification system (PPS) is an outdoor aquaculture system designed based on recirculating aquaculture system (RAS) principles, utilizing recirculating water technology, which can achieve large-scale fish farming in the recirculating water system. The purpose of this experiment is to investigate the alterations in growth performance, intestinal histology, digestion-absorption function, and structural integrity of channel catfish raised in PPS. The findings indicated a significant optimization in water quality indicators pertinent to aquaculture, including total nitrogen, total phosphorus, chemical oxygen demand (COD), ammonia nitrogen, nitrite, and dissolved oxygen. Additionally, the growth performance of channel catfish reared in the PPS group was markedly improved. The intestinal morphology of these channel catfish exhibited increased villus height and a reduced number of mucus cells. Furthermore, serum levels of diamine oxidase and D-lactic acid were significantly decreased in channel catfish raised in the PPS group, while the expression of genes related to the apical junction complex was significantly upregulated, suggesting improved intestinal structural integrity. Moreover, the activities of digestive and absorptive enzymes, such as trypsin, amylase, lipase, and Na + -K + -ATPase, were elevated, indicating enhanced digestive and absorptive functions. In conclusion, based on the conditions of this experiment, the pond purification system module used in this study can effectively improve the quality of the aquaculture water, enhance fish growth performance and improve their intestinal health.

Genome-wide association and genomic selection studies on feed efficiency with fishmeal-free feed in large yellow croaker (Larimichthys crocea) - Gongsi Wang; Yingbo Yuan; Xiaotong Li; Ranxin Fu; Xingcheng Zhu; Zhenye Zhao; Yuhan Jin; Sen Zhang; Peng Ren; Lining Zhang; Qinghui Ai; Ming Fang; et al. (Aquaculture, 2025)

Regime difference trigger the regulation of mineralization progress of organic phosphorus in lake sediments - Hezhong Yuan; Qianhui Yuan; Tong Guan; Yiwei Cai; Enfeng Liu; Ming Ji; Jianghua Yu; Bin Li; Qiang Li; Qingfei Zeng; Yu Wang (Water Research, 2025)

Non-crystal freezing storage assisted by alternating electric field on fresh yak meat quality - Hengxun Lin; Yiping Yang; Qiuyao Xu; Yuan Li; Xiaojia Hu; Xia Li; Christophe Blecker; Guangyu Wu; Chuan Yang; Yanzhen Zhang; Ming Chi; Chunhui Zhang (Meat Science, 2025)

Targeted and non-targeted analyses reveal trophic biomagnification of rubber-derived chemicals in an estuarine food web near China's largest rubber production region - Yuan Liu; Jia-Ming Zhou; Nian-Nian Wu; Shan Liu; Xiao-Liang Liao; Haijiang Wu; Lin Zhu; Heng-Xiang Li; Lang Lin; Rui Hou; Zhi-Hua Li; Xiang-Rong Xu; et al. (Journal of Hazardous Materials, 2025)

Role of circular RNAs in formaldehyde-induced lung Injury: Insights into expression and regulatory pathways - Pan Ge; Xiang Zhang; Yan-qi Yang; Jia-ming Xie; Mo-qi Lv; Ying Sun; Ya-zhao Li; Yuan-yuan Geng; Jian Zhang; Dang-xia Zhou (Food and Chemical Toxicology, 2025)

Genetically engineered bacteria outer membrane vesicles coated small-molecule organic dye facilitates cDC1s-mediated antitumor immune cascade response for NIR-II tumor photoimmunotheranostics - Yuhao Chen; Xiaorui Geng; Ganipisetti Hanumantha Rao; Wei-Chih Wei; Addanki Venkateswararao; Tzu-Ming Liu; Ken-Tsung Wong; Yun Li; Pu Chun Ke; Zhen Yuan (Chemical Engineering Journal, 2025)

Biomimetic Ti3C2 nanosheets for synergistically overcoming chemoresistance and boosting immunotherapy via enhanced cuproptosis in cancer - Shuaiyin Zhang; Xinran Xie; Ming Liu; Zhixin Li; Yang Ye; Liang Peng; Kexing Lyu; Xiaomei Sun; Yuan Yuan; Zhijun Zhang; Weiping Wen; Zhaoxu Tu (Chemical Engineering Journal, 2025)

PHB/PBAT blended melt-blown micro-nano fiber carbon source for efficient solid-phase denitrification: Insights into low-carbon treatment and enhanced mechanism - Hao Yuan; Liang Tang; Ziwei Yang; Xiang Pi; Jinxiang Zhao; Rongshen Luo; Ming Tang; Zuwen Liu; Zhendong Lei; Shiyang Li (Chemical Engineering Journal, 2025)

The revolutionizing osteosarcoma therapy of carbon monoxide and doxorubicin synergy via mesoporous silica nanoparticles - Yating Lian; Junyi Zhou; Wei Li; Zhijie Yuan; Minghui Zhong; Tian Wei; Huishan Liang; Shicong Yang; Li Ding; Li-Ming Zhang; Fen Wang (Chemical Engineering Journal, 2025)

Mechanism of Actinidia chinensis Planch in the treatment of oesophageal cancer based on network pharmacology and experimental validation - Yu Wang; Jianxin Guo; Ming Huang; Shuang Gao; Jianfeng Yuan; Lei Jia; Zhongbing Wu; Jianming Jiang; Jing Li (Natural Product Research, 2025)

Two alkenyl phenol derivatives from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Jing Tang; Rui Xu; Hao Ma; Shuai-Ming Zhu; Fu-Yao Luo; Xue Zhao; Ya-Shuai Kang; Yuan-Wei Gao; Yu Yang; Chang-Wei Li (Natural Product Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Primary greisen-type tin mineralization: Insights from unidirectional solidification texture in oxidized, fluorine-rich ores from the Paleocene Kalonta Sn-W deposit, southern Myanmar - Jin-Xiang Li; Wei-Ming Fan; Rui Yuan; Lamu Ciren; Li-Yun Zhang; Fu-Long Cai; Ya-Hui Yue; Jing Xie; Lin Ding (Journal of Asian Earth Sciences, 2025)

Strawberry preservation using multilayer chitosan films grafted with phenolic acids and loaded with γ-CD-MOFs encapsulated antifungal agents - Linyun Mou; Wei Jiang; Ya Lu; Jianlong Li; Ganpeng Li; Hai Yuan; Ziyi Jiang; Lingzhi Zhang; Tingyin Ming (International Journal of Food Microbiology, 2025)

Agronomic characteristics, objective quantitative, metabolome and transcriptome analysis reveal the influence of fertilization treatments on fresh leaf characteristics and finished tea quality - Liyue Yang; Xizhe Zhu; Ziming Yu; Bicheng Hu; Ping Liu; Fenglan Zhang; Ming Chen; Jinjin Wang; Youyi Huang; Haibo Yuan; Yeyun Li; Jinjie Hua (Food Chemistry, 2025)

Strain-specific effects of fish originated Bacillus velezensis on growth, gut health, and disease resistance of zebrafish - Yuan-Yuan Yao; Wen-Hao Zhou; Juan Hu; Ya-Lin Yang; Ming Li; Rui Xia; Chao Ran; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2025)

Restoration of buried organic carbon for catagenesis-affected rocks using Rock-Eval thermal analysis: Assumptions, performance, and uncertainty analysis - Qianyou Wang; Yaohua Li; Hamed Sanei; Arka Rudra; Ming Yuan; Yang Wang; Yizhou Huang; Richard H. Worden (Earth-Science Reviews, 2025)

Investigation on Fracture Propagation and Energy Evolution of Ultra-low Permeability Sandstone During Reservoir Pressurization - Ming Tang; Tong Zhang; Yanfang Li; Qilong Wang; Mingchao Wang; Yongqiang Chen; Liang Yuan (Rock Mechanics and Rock Engineering, 2025)

Development and Evaluation of a Dual-Mode Cold Atmospheric Plasma System for Stage-Specific Wound Healing Applications - Ching-Yuan Lin; Dong-Jin Li; Yu-Shen Chen; Chia-Wei Hsu; Mohd Yaqub Khan; Ming-Chen Wang (Journal of Medical and Biological Engineering, 2025)

Molecular identification of heterotrophic nitrification and aerobic denitrification bacteria: From methods development to application demonstration - Rui-chun Yang; You-wei Cui; Zhen-ying Li; Ming-teng Li; Liu-xu Jiang; Ya-nan Mi; Yuan Sui; Hui-kai Liang (Water Research, 2025)

Exploring possible ancient applications of perilla: evidence from 3 million fruit remains from Han Dynasty tombs in China - Yun-Jun Bai; Ming Jiang; Xue-Ping Wei; Zhi-Jun Zhao; Xin-Ying Zhou; Hong-En Jiang; Tao Xie; Xiao-Lin Li; Yu-Yang Zhao; Xue Yan; Meng Cheng; Lu-Qi Huang; et al. (Science Bulletin, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Tissue and cell types infected by Ecytonucleospora hepatopenaei (EHP) - Yuan Wang; Shi-ting Lin; Ming Zhao; Peng Di; Jun-fang Zhou; Shou-hu Li; Yan-qing Huang; Ying Na; Xin-cang Li; Wen-hong Fang (Journal of Invertebrate Pathology, 2025)

Synergistic coupling of bipolar membrane electrodialysis and Fenton process for sustainable management of landfill leachate reverse osmosis concentrate - Hao-Ran Yang; Changjiang Li; Chiqian Zhang; Xiaohong Lan; Xinfei Dong; Yi-Hong Jiang; Yu-Ming Zheng; Zhi-Hua Yuan (Chemical Engineering Journal, 2025)

Effects of environmentally relevant concentrations of carbendazim, either alone or combined with benzophenone-3, on testicular development in Xenopus laevis - Jie Li; Hai-Ming Xu; Xing-Hong Li; Yuan-Yuan Li; Zhan-Fen Qin (Aquatic Toxicology, 2025)

Multi-scale characteristics and statistically associated factors of ozone pollution in Hangzhou based on machine learning - Yu-ting He; Tao Ding; Ru Yi; Yuan-yuan Wang; Yi Fu; Cheng-kai Tu; Hong-yan Fang; Jin-ye Li; Ming Zhang (Atmospheric Pollution Research, 2025)

Dynamic changes in DNA methylation and correlated expressing genes during somatic embryogenesis in Hevea brasiliensis - Ling Li; Jia Miao; Jin Liu; Ming-Chun Gui; Min Tang; Hai Tian; Wan-Yuan Shi; Guo-Ping Liang; Xiao-Long Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Bacteria in the Phylum Bacillota Degrade Nicotine Through the Variant of Pyridine and Pyrrolidine Pathway - Xiu-Ming Liu; Xuan Hai; Cong-Jian Li; Yu-Fan Han; Xing Chen; Yu-Jin Fan; Jian Wu; En-Min Zhou; Yuan-Dong Li; Ling-Ling Yang; Yan-Qing Duan; Xiao-Yang Zhi (Current Microbiology, 2025)

Eucalyptus oil: A promising anticoccidial agent with multifaceted protective effects - Jun-jie Huang; Jie-yu Shi; Kai-yuan Li; He Zheng; Wen-hai Zhang; Xiao-bin Yi; Ming-jiang Liu; Ruo-nan Bo; Jin-gui Li (Veterinary Parasitology, 2025)

Numerical simulation of the effect of solar chimneys on NOx-O3 photochemical reaction and ventilation in urban street canyon - Hanbing Xiong; Tianhao Shi; Yongjia Wu; Ruiyue Xia; Xitong Yuan; Renaud de Richter; Wei Li; Yueping Fang; Nan Zhou; Wenyu Li; Chong Peng; Tingzhen Ming (Urban Climate, 2025)

Composition characteristics, source analysis and risk assessment of PAHs in surface waters of Lipu - Jun Luo; Gui-Bin Huang; Mei Wang; Ya-Nan Zhang; Zi-Xuan Liu; Qin Zhang; Shao-Yuan Bai; Dan-Dan Xu; Hui-Li Liu; Sheng-Peng Mo; Xiao-Bin Zhou; Ming-Ming Fu (Journal of Hazardous Materials, 2025)

Novel mechanisms for selenite biotransformation and selenium nanoparticles biogenesis in Acinetobacter sp. SX5 isolated from seleniferous soil - Sheng-Wei Huang; Yuan-yuan Yao; Hua-xu Zhang; Wan-ying Guo; Ming-hui Fang; Hai-bo Wang; Yu-jun Sun; Ming-hao Li (Journal of Hazardous Materials, 2025)

Simultaneous and instrument-free detection of quinine and crystal violet based on a dual-emissive Eu3+-functionalized metal-organic framework - Hou-Qun Yuan; Yuan Yuan; Si-Yi Liu; Jia-Hao Fu; Yi-Fan Xia; Wei Li; Meng-Yuan Pan; Lirong Jiang; Peiyao Chen; Guang-Ming Bao (Journal of Hazardous Materials, 2025)

Efficient capture and detoxification of gaseous arsenic trioxide from flue gas using silicomanganese alloy dust - Xin-Peng Ma; Guang Yang; Guan-Ming Qiao; Song-Yao Liu; Jiao-Jiao Xie; Yuan-Peng Li; Chun-Gang Yuan (Journal of Environmental Management, 2025)

Differential global gene transcription of Saccharomyces cerevisiae by zinc sulfate addition under acetic acid stress and identification of novel zinc and stress-responsive genes related to cell wall function - Ming-Ming Zhang; Bing Yuan; Yu-Zhen Li; Xiao-Lu Wang; Verawat Champreda; Drauzio Eduardo Naretto Rangel; Xin-Qing Zhao (Fungal Biology, 2025)

Co-encapsulation and stability evaluation of myricetin and epicatechin in the oxidized starch-coated edible dock protein hydrogels - Si-Qi Li; Zhi-Yuan Yang; Ming Yang; Wei Wang; Yu-Ru Wu; Yi-Bin Zhou; Kang Liu (Food Hydrocolloids, 2025)

Exploring the distribution and transmission mechanism of ARGs in crab aquaculture ponds and ditches using metagenomics - Chao Li; Yun-xiang Zhu; Xiao-xiao Shen; Yuan Gao; Ming Xu; Meng-kai Chen; Ming-yang An (Environmental Pollution, 2025)

Freezing-enhanced degradation of naproxen by bicarbonate activated hydrogen peroxide: Peformance and mechanisms - Genbao Zhang; Yunze Zhao; Yihang Guo; Ming Li; Qingling Meng; Baoling Yuan; Honghai Xue; Hongliang Wang (Chemical Engineering Journal, 2025)

Dual Co/Li slabs anchoring and surface nano-passivation: toward a stable 4.6 V operation of LiCoO2 cathode with enhanced lattice structure - Yonghuan Wang; Ziqi Wei; Xingchi Li; Guorong Chen; Xin Chen; Yuan Wang; Ming Xie; Liyi Shi; Dengsong Zhang (Chemical Engineering Journal, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Manipulating molecular conformation of charge-transfer cocrystal for NIR-II absorption and light/thermal-responsive imaging - Yun Rong; Si-Qi Chen; Yu Dong Zhao; Sheng Zhuo; Yuan-Yuan Li; Jin-Zhuo Liu; Yi-Yi Ju; Yue-Min Xie; Liang-Sheng Liao; Ming-Peng Zhuo; Ke-Qin Zhang (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

TSPO activation ameliorates maternal immune activation induced PV interneuron deficits via BDNF/TrkB signaling - Ming-Jie Mao; Hui-Ling Yu; Qing-Zhen Liu; Ya-Zhou Wen; Ming Jiang; Hong-Mei Yuan; Hua-Bei Zeng; Li-Dong Zhang; Shan-Wu Feng (Psychopharmacology, 2025)

Directional regulation of one-dimensional channel length in metal-organic frameworks for efficient xylene isomer separation in gas chromatography - Wen-Qi Tang; Yue-Wen Gu; Xiang Qi; Ye-Qin Zhou; Wang Li; Ming Xu; Zhi-Yuan Gu (Analytica Chimica Acta, 2025)

Triploidy induction through cntd1 knockout in red crucian carp (Carassius auratus red var.) - Huilin Li; Yu Zhang; Lina Zhang; Juan Li; Yuan Ou; Ming Wen; Zehong Wei; Jing Wang; Yu Deng; Yinjun Jiang; Conghui Yang; Yuqin Shu; et al. (Aquaculture, 2025)

Synergistic reduction of pollutants and GHGs in China's PET industry: A material metabolism perspective - Fu Guo; Rui Li; Yifan Gu; Mingxuan Tuo; Zixin Bian; Yihan Li; Qingbin Yuan; Ming Yang; Yufeng Wu (Resources, Conservation and Recycling, 2025)

Energy optimal path planning of ocean-energy driven unmanned surface vehicles - Yulei Liao; Ke Li; Yongbo Zhao; Haotian Tang; Ming Zhang; Xiaofeng Liu; Zhi-Ming Yuan (Ocean Engineering, 2025)

The dual-targeted transcription factor BAI1 orchestrates nuclear and plastid gene transcription in land plants - Jing Qin; Yelin Shan; Hao Liu; Zhangzhi Xue; Yike Xie; Guoxin Yuan; Yiming Zou; Xiaonuan Hao; Yunpeng Zhu; Xuan Shen; Meng Li; Xu Wang; et al. (Molecular Plant, 2025)

Near-white light-emitting copper nanoclusters/starch composites for multiplexing imaging and multichannel enhancement of latent fingerprints - Zhibo Gao; Chuanjun Yuan; Ming Li; Zhize Xu; Meng Wang; Jiaming Lyu; Shiqiang Sun; Fenghe Liu; Peiliang Han (Chemical Engineering Journal, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Effects of Subchronic Manganese and Iron Exposure, Alone or in Combination, on Elemental Distribution in Rats - Yan Li; Jian-chao Peng; Yuan-yuan Fang; Li-mei Qin; Michael Aschner; Yue-ming Jiang (Biological Trace Element Research, 2025)

Evaluation of genomic prediction of resistance to visceral white-spot disease in large yellow croaker (Larimichthys crocea) - Yingbo Yuan; Meng Zhou; Zeyu Li; Dan Jiang; Zhiyong Wang; Ming Fang (Aquaculture, 2025)

Energy production and denitrogenation performance by sludge biochar based constructed wetlands-microbial fuel cells system: Overcoming carbon constraints in water - Boda Ouyang; Zhiyong Zhang; Fuzhi Chen; Fei Li; Ming-Lai Fu; Huachun Lan; Baoling Yuan (Water Research, 2025)

Hydroxyl-induced structural defects in metal-organic frameworks for improved photocatalytic decontamination: Accelerated exciton dissociation and hydrogen bonding interaction - Wen-Qiang Li; Yuan-Ming Li; Nannan Hou; Xiao-Guo Zhou; Yang Wang; Xian-Yang Shi; Yang Mu (Journal of Hazardous Materials, 2025)

Visualizing the spatial distribution of metabolites in tomato fruit at different maturity stages by matrix-assisted laser desorption/ionization mass spectrometry imaging - Sihui Guan; Chaochao Liu; Zhuping Yao; Chenxu Liu; Meiying Ruan; Rongqing Wang; Qingjing Ye; Hongjian Wan; Zhimiao Li; Guozhi Zhou; Ming Diao; Yuan Cheng (Food Research International, 2025)

Self-assembled gallic acid-rare earth nanocomplexes against MRSA with multi-targeting antibacterial mechanisms robustly combating bacterial resistance - Xian Liu; Qiwu Yuan; Yang Yang; Ke Li; Nanjiong Pang; Jiangtao Wang; Ming Yang; Xia Li; Junling Guo; Xuepin Liao; Bi Shi (Chemical Engineering Journal, 2025)

Morphological characteristics and distribution of antennal sensilla of Spodoptera litura (Lepidoptera: Noctuidae) using scanning electron microscopy - Yong-Ping Li; Hai-Yan Zhou; Hui Ye; Robert A. Haack; Yuan Yang; Qiu-Lian Hu; Ming-Min Jiang; Jun Cao (Zoomorphology, 2025)

Ornithinibacillus xuwenensis sp. nov., A Novel Thermotolerant Bacterium Isolated from Mangrove Sediment - Ming Li; Xixi Hu; Yuan Ni; Tiancheng Ni; Feng Li; Dong Xue (Current Microbiology, 2025)

Effects of components’ arrangement on the sloshing behavior inside liquid metal reactors under seismic excitation - Yalou Chen; Yuzeng Wu; Pingjian Ming; Guopeng Yu; Yuan Ma; Xiaojia Li; Junlong Zhao; Zhicheng Tan (Annals of Nuclear Energy, 2025)

Effects of pre‐experimental fasting and sheltering on the swimming performance and oxygen consumption of juvenile grass carp ( Ctenopharyngodon idella ) - Malik Haris Ali; Ying‐ping Huang; David Johnson; Wei‐ming Li; Xi Yuan (Journal of Fish Biology, 2025)
This study investigated the effects of pre‐experimental fasting for 2, 7, and 14 days under both unsheltered (12 h dark–12 h light) and sheltered conditions on the critical swimming speed ( U crit ) and oxygen consumption (MO 2 ) of juvenile grass carp, using a modified swim respirometer. Key findings include (1) the U crit of test fish decreased significantly, by 28%, after fasting for 14 days and sheltering intensified the impact to a 43% decrease, and (2) fish anaerobic capacity decreased after 7 days but increased after 14 days, and was enhanced by sheltering conditions. These findings are important as they indicate that fasting and sheltering can impair grass carp survival and disrupt river ecosystem balance, highlighting the need for habitat conservation.

Mapping the Research Landscape: A Comprehensive Bibliometric Review of Global Warming and Human Health - Qingyong Zheng; Jianguo Xu; Ming Liu; Kexin Ji; Yu Zhang; Songlin Wu; Tengfei Li; Kaisen Yuan; Zhichao Ma; Zijian Ma; Jinhui Tian; Jiang Li (International Journal of Climatology, 2025)
Human health is increasingly threatened by global warming, necessitating a thorough understanding of research progress in this critical area to inform future studies. The data were analysed using Microsoft Excel 2021, and visualisations were created with GraphPad, VOSviewer and R‐Studio (Bibliometrix). These tools were used to generate graphs and network visualisations illustrating author and country collaborations, journal article distributions, hotspot clustering and future trend predictions. Our analysis revealed a substantial increase in publications in recent years, with intensified research and collaboration observed across Asia, Europe, North America and Oceania, particularly in the United States. Various high‐impact journals have made meaningful contributions to raising awareness in this field, emphasises the multifaceted impacts of global warming on public health and societal activities, while also exploring adaptive measures being implemented in response to these changes. As the world continues to grapple with the global pandemic, further research is likely to spotlight related issues, with heightened interest anticipated. The evidence of global warming's impact on human health is becoming increasingly evident, underscoring the need for global cooperation to mitigate its effects and promote public health. This study provides a foundation for researchers and policymakers, highlighting the significance of addressing global warming's implications for human well‐being. By fostering international collaboration, we can collectively strive toward sustainable strategies to combat global warming and safeguard public health.

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Integrating three-primary-color and white long-lasting afterglows in triphenylene-doped polymers for time/space-resolved applications - Qian Wang; Xiao-Lei Xu; Meng-Yuan Zhu; Ya-Ping Du; Yu-Juan Ma; Jin-Hua Li; Guo-Ming Wang (Chemical Engineering Journal, 2025)

Incorporating Genetic Diversity to Optimize the Plant Conservation Network in the Third Pole - Moses C. Wambulwa; Guang‐Fu Zhu; Ya‐Huang Luo; Zeng‐Yuan Wu; Jim Provan; Marc W. Cadotte; Alistair S. Jump; Francis N. Wachira; Lian‐Ming Gao; Ting‐Shuang Yi; Jie Cai; Hong Wang; et al. (Global Change Biology, 2025)
Climate change poses a significant threat to the survival of many species. Although protected areas can slow down biodiversity loss, they often lack systematic planning and do not integrate genetic diversity. Genetic diversity is a key prerequisite for species survival and the ability to tolerate new conditions. Using population genetic and distribution data from 96 plant species in the Third Pole (encompassing the Tibetan Plateau and adjacent mountains), we mapped patterns of genetic diversity, projected climate‐driven range dynamics and future genetic erosion, and designed an optimal conservation framework for the region. We identified several patches of high haplotype diversity ( H D ), with a relatively high number of haplotypes in southeastern Third Pole. Regression models revealed that climate and topography have interacted to shape patterns of genetic diversity, with latitude and precipitation being the best predictors for H D of cpDNA and nrDNA, respectively. Ecological niche modeling predicted an approximate 43 km northwestward and 86 m upward shift in suitable habitats under future climate scenarios, likely leading to a significant loss of up to 13.19% and 15.49% of cpDNA and nrDNA genetic diversity, respectively. Alarmingly, 71.20% of the newly identified conservation priority areas fall outside of the existing protected areas and planned National Park Clusters. Therefore, we recommend expanding the network by 2.02 × 10 5 km 2 (5.91%) in the Third Pole, increasing the total conserved area to 1.36 × 10 6 km 2 (39.93%) to effectively preserve the evolutionary potential of plants. This study represents an innovative attempt to incorporate genetic diversity into biodiversity conservation efforts.

Growth, biochemical indexes, and intestinal microbiota response of red tilapia (Oreochromis spp.) under different densities and feeding frequencies in the land-based aquaculture tank - Yu-Xiang Xie; Jun-Neng Liang; Gen Kaneko; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Qiong Yang; Zhen-Ping Liao; Xue-Ming Yang; Hong-ping Zhang; Lin-Yuan Jiang; et al. (Aquaculture, 2025)

Intra-urban comparison of hazardous VOCs in Hong Kong: Source apportionment and integrated risk assessment - Xiangyunong Cao; Dasa Gu; Hao Sun; Ka Fung Leung; Yuchen Mai; Xin Li; Wai Ming Chan; Sin Ka Mak; Zhenxing Liang; Wentai Zhang; Yisheng Zhang; Shan Huang; et al. (Sustainable Cities and Society, 2025)

Optical and molecular techniques are complementary to understand the characteristics of dissolved organic matter in the runoff from sloping croplands with various micro-topographies during rainfall - Guo Chen; Qing-wei Zhang; Hao Wang; Ren Geng; Jian Wang; Yuan-bi Yi; Ming Li; Ding He (Journal of Hydrology, 2025)

Treatment of dye-containing wastewater using discarded animal blood-derived hemoglobin crystals - Xiao-Qian Jin; Jie Liu; Chen-Yuan Li; Liang-Liang Chen; Jia-Lei Li; Xue-Ting Wang; Guang-Ming Mi; Da-Chuan Yin (Journal of Environmental Management, 2025)

Molecular basis of E93-dependent tissue morphogenesis and histolysis during insect metamorphosis - Mei Zeng; Zi-Yu Yan; Ya-Nan Lv; Jia-Ming Zeng; Ning Ban; Dong-Wei Yuan; Sheng Li; Yun-Xia Luan; Yu Bai (Insect Biochemistry and Molecular Biology, 2025)

Deep eutectic solvent-based ultrasonic-assisted extraction of polyphenol from Chenopodium quinoa Willd.: Optimization and lipid-lowering activity - Xiao-tong Lin; Si-xuan Zhou; Zhi-peng Sun; Ming-yuan Cao; Tao Zhou; Li-yan Zhao; Gui-tang Chen (Food Chemistry, 2025)

Carbon catabolite repression during the simultaneous utilization of lignocellulose-derived sugars in lactic acid production: Influencing factors and mitigation strategies - Mingxi Li; Wenbin Zhu; Jiamei Fan; Ming Gao; Xiaona Wang; Chuanfu Wu; Ying Wang; Yuan Lu (Environmental Research, 2025)

Experimental analysis on breaching mechanism of earth-rock dam induced by landslide generated waves - Zhen-han Du; Jia-Wen Zhou; Shi-Chen Zhang; Qi-Ming Zhong; Hai-Bo Li; Yu-Xiang Hu; Cong-Jiang Li; Jie-Yuan Zhang (Engineering Geology, 2025)

Maize kernel nutritional quality—an old challenge for modern breeders - Decui Li; Anqi Hao; Wen Shao; Weiwei Zhang; Fuchao Jiao; Haiyan Zhang; Xueyan Dong; Yuan Zhan; Xia Liu; Chunhua Mu; Zhaohua Ding; De Xue; et al. (Planta, 2025)

Intrasporangium zincisolvens sp. nov., A Novel Actinobacterium Isolated from Rhizosphere Soil - Lu-Yao Feng; Jiang‑Yuan Zhao; Zhu-Feng Shi; Ming‑Gang Li; Te Pu; Zhu-Li Shi; Xin Liu; Yu Wang; Le‑Le Li; Pei‑Wen Yang (Current Microbiology, 2025)

Plasma Ionomic Profile and Interaction Patterns in Coronary Artery Disease Patients - Qing-Qing Zhao; Xian-Long Shu; Zhen Yuan; Qian Gao; Ying Huang; Yuan-Qing Yang; Li-Ming Peng; Guo Wang; Xiao-Ping Chen; Bi-Lian Chen; Jie Tang (Biological Trace Element Research, 2025)

Research on simulation of hydrogen diffusion behavior based on CONTHAC-3D code - Yuan Chang; Hui Wang; Gong-Lin Li; Ming Ding (Annals of Nuclear Energy, 2025)

Highly sensitive and catalytic electrochemical aptamer-based biosensor for β-lactoglobulin via coupling redox recycling background minimization with DNAzyme amplification - Yujie Liu; Yuan Ming; Daxiu Li; Bingying Jiang; Ruo Yuan; Yun Xiang (Analytica Chimica Acta, 2025)

Cynbungenins A-K, structurally diverse steroids with cytotoxic activity from the roots of Cynanchum bungei Decne - Xiao-San Li; Ming-Shang Liu; Wan-Bi Feng; Yu-Hao Luo; Wei-Bin Yuan; Ting-Ting Li; Xiao-Fu Peng; Yong-Mei Huang; Xue-Mei Yang; Hui Luo (Phytochemistry, 2025)

The miR172a–SNB module orchestrates both induced and adult-plant resistance to multiple diseases via MYB30-mediated lignin accumulation in rice - He Wang; Zhe-Xu Wang; Hong-Yuan Tian; Yu-Long Zeng; Hao Xue; Wan-Ting Mao; Lu-Yue Zhang; Jun-Ni Chen; Xiang Lu; Yong Zhu; Guo-Bang Li; Zhi-Xue Zhao; et al. (Molecular Plant, 2025)

Coupling of molten salt heating tire pyrolysis process with carbon black modification process: Technical economic evaluation and life cycle assessment - Jingwei Qi; Yijie Wang; Pengcheng Xu; Ming Hu; Taoli Huhe; Xiang Ling; Haoran Yuan; Jiadong Li; Yong Chen (Journal of Cleaner Production, 2025)

Development of a platform strain for integration expression of phospholipase D and its application in improving phosphatidylserine content of egg yolk - Peng Zhang; Xiao-Li Kong; Jin-Song Gong; Zhi-Yuan Yao; Chang Su; Heng Li; Xiao-Mei Zhang; Zhi-Ming Rao; Zheng-Hong Xu; Jin-Song Shi (Food Bioscience, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)

Significantly improving the stability of high-entropy PtFeNiCoMn nanoalloys by nitrogen doping in oxygen electrocatalysis - Mang Niu; Qinhe Guan; Weiyong Yuan; Chun Xian Guo; Dapeng Cao; Chang Ming Li; Lian Ying Zhang; Xiu Song Zhao (Chemical Engineering Journal, 2025)

Oriented bioconversion of food waste to lactic acid for external carbon source production: Microbial communities and comparison of denitrification performance - Haichuan Pan; Yuan Li; Wenbin Zhu; Chuanfu Wu; Ming Gao; Qunhui Wang; Ying Wang; Yuan Lu; Yi Rao; Chunjiang Yu (Bioresource Technology, 2025)

The analysis of the genetic loci affecting phenotypic plasticity of soybean isoflavone content by dQTG.seq model - Zhenhong Yang; Yuhang Zhan; Yina Zhu; Hanhan Zhu; Changjun Zhou; Ming Yuan; Haiyan Li; Miao Liu; Weili Teng; Yongguang Li; Xue Zhao; Yuhe Wang; et al. (Theoretical and Applied Genetics, 2025)

Effects of imidacloprid on Orius similis: assessing growth, development, and reproduction through age-stage two-sex life table analysis under contact and stomach toxicity treatments - Bo Zhang; Yi-Ru Li; Jin-Long Zhang; Guo-Hua Chen; Nian Yang; Ji-Huan Liu; Guo-Ting Yuan; Xiao-Ming Zhang (Journal of Pest Science, 2025)

Hyperspectral image classification with embedded linear vision transformer - Yunfei Tan; Ming Li; Longfa Yuan; Chaoshan Shi; Yonghang Luo; Guihao Wen (Earth Science Informatics, 2025)

Intramolecular distance-regulated G4 DNA enzymatic activity-based chromophotometric system for visual monitoring of diquat - Ya You; Wei-Guo Yang; Shun Zhang; Ming-Li Su; Qi-Lin Peng; Wan-Jiang Zhao; Ruo Yuan; Shang-Cheng Xu; Wen-Bin Liang (Analytica Chimica Acta, 2025)

Dual emission chiral carbon dots as fluorescent probe for fast chiral recognition of tryptophan enantiomers - Qi Wu; Yuan Chen; Yan-Li Wang; Ji-Ying Song; Hai-Tao Lv; Ya-Ming Sun (Analytica Chimica Acta, 2025)

Comparative genomic analyses of the genus Robertmurraya and proposal of the novel species Robertmurraya mangrovi sp. nov., isolated from mangrove soil - Ming Li; Xixi Hu; Tiancheng Ni; Yuan Ni; Dong Xue; Feng Li (Antonie van Leeuwenhoek, 2025)

Integrative transcriptomics and metabolomics analysis provide insight into the formation of skin pigmentation diversity in Chinese soft-shelled turtle (Pelodiscus sinensis) - Ming Qi; Wei Liu; Wei Li; Guangmei Chen; Wenrui Shi; Gaohua Yao; Yijiang Bei; Fan Yuan; Qinghui Meng; Fan Zhou; Wenjun Ma; Xueyan Ding; et al. (Aquaculture, 2024)

Regime difference between macrophyte and Cyanophyta dominance regulate microbial carbon sequestration mode in lake sediments - Hezhong Yuan; Tong Guan; Enfeng Liu; Ming Ji; Jianghua Yu; Bin Li; Yiwei Cai; Qianhui Yuan; Qiang Li; Qingfei Zeng; Yu Wang (Water Research, 2024)

Nitrogen are the main factors driving the structure and function of the marine archaeal community in Yongle Blue Hole, Sansha - Wenjing Wang; Hongxia Ming; Dongwei Li; Yuan Jin; Yuyang Xie; Jingfeng Fan (Regional Studies in Marine Science, 2024)

Hydrodynamic analysis of marine floating photovoltaics under the influence of seabed topography and coastlines - Huajun Li; Qiujue Jiang; Deqing Zhang; Junfeng Du; Zhi-Ming Yuan; Anteng Chang (Ocean Engineering, 2024)

Numerical simulation of bubble wakes with mixed scales of underwater vehicles - Yang Han; Jue-yu Dong; Ruo-xin Li; Yan-yuan Wu; Ming-lei Ji (Ocean Engineering, 2024)

Multi-objective model predictive control for ship roll motion with gyrostabilizers - Lifen Hu; Ming Zhang; Gang Li; Zhiming Yuan; Junying Bi; Yanli Guo (Ocean Engineering, 2024)

Early postnatal and concurrent exposure to metals and neurobehavioral outcomes at 5 years: Associations with individual environmental exposures and mixtures - Sui-Ling Liao; Shen-Hao Lai; Yuan-Ting Hsu; Li-Chen Chen; Ming-Han Tsai; Man-Chin Hua; Tsung-Chieh Yao; Kuan-Wen Su; Kuo-Wei Yeh; Chih-Yung Chiu; Shau-Ku Huang; Jing-Long Huang (NeuroToxicology, 2024)

Association between indoor PM2.5 components and accelerated biological aging in schizophrenia patients: Evidence from multi-omics mechanisms - Rubing Pan; Xingxu Yi; Yanlong Xu; Jian Song; Weizhuo Yi; Jintao Liu; Rong Song; Xuanxuan Li; Li Liu; Jiajun Yuan; Ning Wei; Yuxing Huang; et al. (Journal of Hazardous Materials, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Molecular dynamics study of waste tire pyrolysis: Focus on intermediate product evolution and sulfur migration law - Jingwei Qi; Yijie Wang; Pengcheng Xu; Ming Hu; Taoli Huhe; Xiang Ling; Haoran Yuan; Jiadong Li; Yong Chen (Journal of Environmental Chemical Engineering, 2024)

Green fabrication of modified lignin/zeolite/chitosan-based composite membranes for preservation of perishable foods - Zhan-Chao Li; Meng-Yao Su; Xiao-Yu Yuan; Hai-Qing Lv; Rui Feng; Li-Jie Wu; Xiao-Ping Gao; Yan-Xia An; Zhan-Wei Li; Miao-Yun Li; Gai-Ming Zhao; Xiao-Peng Wang (Food Chemistry, 2024)

Corrigendum to “A critical review on graphene oxide membrane for industrial wastewater treatment” [Environ. Res. 223 (2023) 115409] - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2024)

Metagenomic analysis manifesting intrinsic relatedness between antibiotic resistance genes and sulfate- and iron-reducing microbes in sediment cores of the Pearl River Estuary - Zhaohong Li; Lan Lin; Xiuqin Xie; Lili Ming; Songzhang Li; Lan Liu; Ke Yuan; Li Lin; Ligang Hu; Tiangang Luan; Baowei Chen (Environmental Pollution, 2024)

Fe-MOF derived Fe3O4/C-based hydrogel for efficient solar-driven photothermal evaporation - You Zhou; Lei Xu; Sheng-Jie Han; Cai-Hua Liu; Yi-Bin Li; Ming-Lai Fu; Baoling Yuan (Desalination, 2024)

Increase of PCSK9 expression in diabetes promotes VEGFR2 ubiquitination to inhibit endothelial function and skin wound healing - Jian-Jun Gao; Fang-Yuan Wu; Yu-Jia Liu; Le Li; Yi-Jun Lin; Yue-Ting Kang; Yue-Ming Peng; Yi-Fang Liu; Chen Wang; Zhen-Sheng Ma; Yang Cao; Hong-Yu Cao; et al. (Science China Life Sciences, 2024)

Exploring the adaptive behaviour and environmental acclimation of artificially-bred Chinese sturgeon (Acipenser sinensis) in semi-open marine environment: insights for endangered species conservation - Huangxin Liu; Pengcheng Li; Xiaoqian Leng; Ming Jiang; Li Shen; Puyuan Wang; Hui Zhang; Jiang Luo; Wei Xiong; Yuan Liu; Hao Du (Reviews in Fish Biology and Fisheries, 2024)

Transcriptomic analysis of hub genes regulating nitrate and glucose response of nitrate response deficiency 1 (NRD1) mutant in foxtail millet - Xin-Li Yao; Zi-Dong Li; Ming-Hua Zhang; Hui-Xin Meng; Yu-Ze Wang; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; Xiaoqian Chu; Jia-Gang Wang (Plant Cell Reports, 2024)

Embryonic Genome Activation (EGA) Occurred at 1-Cell Stage of Embryonic Development in the Mud Crab, Scylla paramamosain, Revealed by RNA-Seq - Li-Kun Xu; Chun-Yan Ma; Feng-Ying Zhang; Wei Wang; Ming Zhao; Xin Jin; Jin-Ju Yin; Ling-Bo Ma; Wei Chen; Jia-Yuan Xu; Ke-Yi Ma; Zhi-Qiang Liu (Marine Biotechnology, 2024)

Solibacillus ferritrahens sp. nov., a novel siderophore-producing bacterium isolated from Wumeng Mountain National Nature Reserve in Yunnan Province - Xiao-Di Liu; Jiang-Yuan Zhao; Le-Le Li; Jian-Yu Li; Pei-Wen Yang; Song-Guo Liang; Lu-Yao Feng; Zhu-Feng Shi; Zhang-Gui Ding; Ming-Gang Li; Shu-Kun Tang (Antonie van Leeuwenhoek, 2024)

Simplicispira sedimenti sp. nov., isolated from a sediment of drainage ditch in winery - Xing Chen; Yuan-Dong Li; Xiu-Ming Liu; Li Gao; Xing-Kui Zhou; Li-Min Dong; Gang Du; Neeli Habib; Wen-Jun Li; Yan-Qing Duan (Antonie van Leeuwenhoek, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Gckr depletion leads to growth retardation and diet-dependent visceral obesity in red crucian carp (Carassius auratus red var.) - Juan Li; Huilin Li; Yuan Ou; Qiyong Lou; Zehong Wei; Ming Wen; Shi Wang; Qingfeng Liu; Yuqin Shu; Shaojun Liu (Aquaculture, 2024)

Progressive melting of surface water and unequal discharge of different DOM components profoundly perturb soil biochemical cycling - Yongli Hao; Yuan Song; Xianwen Li; Ming Li; Xiaorong Wei; Shengli Guo; Yaxian Hu (Water Research, 2024)

Identification and bioactivity evaluation of twelve previously undescribed depsidone derivatives from Garcinia oligantha - Xiao-Hui Peng; Sha Chen; Xiao-Fan Liu; Jin-Yuan Yang; Fan-Zhu Meng; Hao Cao; Da-Hong Li; Hui-Ming Hua (Phytochemistry, 2024)

Differential spatial responses and assembly mechanisms of soil microbial communities across region-scale Taiga ecosystems - Zheng-Xiao Liu; Yue-Ming Lyu; Yang Liu; Yun-Qi Wang; Ming-Min Xiong; Yuan Tang; Xing-Yue Li; Han Sun; Ji-Liang Xu (Journal of Environmental Management, 2024)

Effects of 1-oleate-2-palmitate-3-linoleate glycerol supplementation on the small intestinal development and gut microbial composition of neonatal mice - Fang Wu; Yaqiong Liu; Ming Zhang; Xinlei Yuan; Tengteng Ji; Yutong Jin; Yixuan Li; Ran Wang; Yanling Hao; Bing Fang (Food Research International, 2024)

Investigation of non-volatile metabolite variations during round green tea processing and effect of pan-frying degree using untargeted metabolomics and objective quantification - Yaya Yu; Xizhe Zhu; Bifeng Yuan; Ming Chen; Jinjin Wang; Li Zhu; Yongwen Jiang; Haibo Yuan; Jinjie Hua (Food Chemistry, 2024)

A newly identified secretory phospholipase A2 group XIIA homolog (LcPLA2XIIA) in Larimichthys crocea exhibits antimicrobial and antitumor activities - Shouhu Li; Chuang Qin; Shi-Ming Peng; Ya-Bing Wang; Yuan Wang; Xiao-Shan Wang; Jian-Gao Shi; Xin-Cang Li (Fish & Shellfish Immunology, 2024)

Planting halophytes increases the rhizosphere ecosystem multifunctionality via reducing soil salinity - Jin-Peng Hu; Yuan-Yuan He; Jian-Hong Li; Zhao-Long Lü; Yue-Wei Zhang; Yuan-Hong Li; Jia-Lü Li; Ming-Xu Zhang; Yan-Hua Cao; Jin-Lin Zhang (Environmental Research, 2024)

MGDA-assisted plant washing agent for improving the removal of Cd and Cu from farmland soils - Yi Wang; Chen Tu; Yuan Li; Shuai Yang; Ying Liu; Xia Zhu; Shao-cheng Si; Run-lai Luo; Xiang-liang Pan; Yong-ming Luo (Environmental Pollution, 2024)

Design of epoxy composites via molecular orbital modulation and enhanced π-πF interactions achieving synchronous improvement of electrical and mechanical performance - Wenxia Sima; Wenlong Pang; Potao Sun; Tao Yuan; Ming Yang; Xiaoxiao Chen; Zhaoping Li; Xiaotong Liu; Xinyu Tang (Chemical Engineering Journal, 2024)

Placental ischemia-upregulated angiotensin II type 1 receptor in hypothalamic paraventricular nucleus contributes to hypertension in rat - Abdoulaye Issotina Zibrila; Jun Zhou; Xiaomin Wang; Ming Zeng; Md. Ahasan Ali; Xiaoxu Liu; Asma A. Alkuhali; Zhaoshu Zeng; Yuan Meng; Zheng Wang; Xuelan Li; Jinjun Liu (Pflügers Archiv - European Journal of Physiology, 2024)

Anti-adipogenesis and anti-obesity potential of alliin mediated by modulating glycolipid metabolism via activating PPARγ signaling - Ming-Yan Yang; Yu-Jing Liu; Mei-Hua Zheng; Tao Pan; Zhen-Yuan Li; Bai-Fang Gong; Hua-Ying Fan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Concentration and activation biresponsive strategy in one analysis system with simultaneous use of G4 structure-specific signal probe and enzyme-catalyzed reaction - Yu-Shu Li; Chun-Feng Feng; Hao-Ran Chen; Wei-Guo Yang; Fei Liu; Ming-Li Su; Ruo Yuan; Li-Qun Zhang; Wen-Bin Liang (Analytica Chimica Acta, 2024)

Epidemiology of human metapneumovirus in Taiwan from 2013 to 2023 - Su-Lin Yang; Tai-Yuan Chiu; Kun-Lin Tsai; Chung-Hao Li; Jyh-Yuan Yang; Ming-Tsan Liu; Fang-Tzy Wu (Archives of Virology, 2024)

Comparative transcriptome analysis provides a glance into the regulatory of insulin-like peptide 1 gene in the Pacific white shrimp Litopenaeus vannamei - Manwen Su; Xiaojun Zhang; Xiaoxi Zhang; Jianbo Yuan; Ming Yang; Fuhua Li (Aquaculture, 2024)

Macroalgal fossil Longfengshania from the Tonian Shiwangzhuang and Jiuliqiao formations in western Shandong and northern Anhui, North China - Guang-Jin Li; Lei Chen; Ke Pang; Qing Tang; Cheng-Xi Wu; Rui Huang; Ming-Yang Qiu; Xun-Lai Yuan; Chuan-Ming Zhou (Palaeoworld, 2024)

Abundant small microplastics hidden in water columns of the Yellow Sea and East China Sea: Distribution, transportation and potential risk - Jia Lin; Jia-Yuan Zheng; Zhi-Geng Zhan; Yuan-Ming Zhao; Qian-Zhi Zhou; Juan Peng; Yan Li; Xi Xiao; Jiang-Hai Wang (Journal of Hazardous Materials, 2024)

Magnetic modification of cerium organic frame materials to improve the phosphorus adsorption performance: Modulating the valence state - Boda Ouyang; Fei Li; Zhiyong Zhang; Xiaoyi Xie; Lei Chen; Wenjie Sun; Ming-Lai Fu; Baoling Yuan (Journal of Environmental Chemical Engineering, 2024)

Cu inanchored MnO/carbonaceous frameworks trigger peroxymonosulfate activation for enrofloxacin degradation: ROS generation and pollutant attacking processes - Huai-Yuan Niu; Zheng-Tao Dong; Hai Guo; Ya-Ya Yang; Wen-Jie Yang; Ming Yan; Cheng-Gang Niu; Ji-Shan Li (Journal of Environmental Chemical Engineering, 2024)

Dual-Salt aqueous electrolyte for enhancing Charge-Storage properties of VO2 polymorphic cathodes for Zn-Ion batteries - Jing-Hong Huang; Xu-Feng Luo; Tzu-Yu Kuo; Yu-Hua Lai; Purna Chandra Rath; Chun-Wei Huang; Ming-Hsien Lin; An-Yuan Hou; Ju Li; Yu-Sheng Su; Wen-Wei Wu; Jeng-Kuei Chang (Chemical Engineering Journal, 2024)

The role of ALDH1A1 in glioblastoma proliferation and invasion - Yu-Kai Huang; Tzu-Ming Wang; Chi-Yu Chen; Chia-Yang Li; Shu-Chi Wang; Khushboo Irshad; Yuan Pan; Kun-Che Chang (Chemico-Biological Interactions, 2024)

Identification of systemic nitrogen signaling in foxtail millet (Setaria italica) roots based on split-root system and transcriptome analysis - Xin-Li Yao; Yu-Ze Wang; Hui-Xin Meng; Ming-Hua Zhang; Xuan Zhou; Xue-Ting Kang; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; Xiaoqian Chu; et al. (Plant Cell Reports, 2024)

Inflammation in Metal-Induced Neurological Disorders and Neurodegenerative Diseases - Ruokun Wei; Peiqi Wei; Haiyan Yuan; Xiang Yi; Michael Aschner; Yue-ming Jiang; Shao-jun Li (Biological Trace Element Research, 2024)

Enhancing CO2 storage and marine carbon sink based on seawater mineral carbonation - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Shuo Chen Li; Zhi Bo Wang; Jun Ma (Marine Pollution Bulletin, 2024)

Vibration reduction and efficiency enhancement effects of twisted rudders in submarines under small rudder angle conditions - Di Zhang; Jin-ming Ye; Wan-li Yang; Yuan-run Wu; Jian-lin Shou (Ocean Engineering, 2024)

A facile and intelligent detection method for diclazuril based on a stable dual emissive Eu3+-dopped metal–organic framework - Yi-Fan Xia; Yan-Xia Li; Qing-Yan Xiao; Zhi-Qiang Cai; Qian-Wen Yang; Yi-Xuan Hu; Zi-Yi Mei; Guang-Ming Bao; Hou-Qun Yuan (Food Chemistry, 2024)

Anomaly detection of massive bridge monitoring data through multiple transfer learning with adaptively setting hyperparameters - Chun-Xu Qu; Hong-Ming Zhang; Ting-Hua Yi; Zhi-Yuan Pang; Hong-Nan Li (Engineering Structures, 2024)

Carbon dots with tunable excitation-independent fluorescence and organelle-specific targeting via core graphitization and surface groups engineering - Ming-Yuan Sun; Bao-Hua Tian; Xin-Xin Li; Yu Li; Yu Lei; Xi-Lin Guo; Qiang Miao; Hao Li; Hai-Xia Liang (Chemical Engineering Journal, 2024)

Mechanisms for carbon stock driving and scenario modeling in typical mountainous watersheds of northeastern China - Jin Zhang; Wen-Guang Zhang; Xin-Yan Zhang; Yu-Hong Li; Ming-Ming Feng; Peng Qi; Yi-Qiang Huang; Rui Li; Ming Jiang; Yuan-Chun Zou; Yi Wu (Environmental Monitoring and Assessment, 2024)

Signal Transduction Associated with Mn-induced Neurological Dysfunction - Xiao-wei Zheng; Yuan-yuan Fang; Jun-jie Lin; Jing-jing Luo; Shao-jun Li; Michael Aschner; Yue-ming Jiang (Biological Trace Element Research, 2024)

Fangchinoline inhibits mouse oocyte meiosis by disturbing MPF activity - Shi-Cai Gao; Ming-Zhe Dong; Bing-Wang Zhao; Sai-Li Liu; Jia-Ni Guo; Si-Min Sun; Yuan-Yuan Li; Yuan-Hong Xu; Zhen-Bo Wang (Toxicology in Vitro, 2024)

Synergistic reduction of pollution and carbon mitigation in constructed wetlands-microbial fuel cell using sludge-derived biochar - Chao Li; Quan Yuan; Liangshan Hao; Ming Xu; Jiashun Cao; Weijing Liu (Science of The Total Environment, 2024)

Increasing structure diversity of farnesylated chalcones by a fungal aromatic prenyltransferase - Ying Wu; Shiyunhua Qian; Xiang Zhou; Shu-Ming Li; Chun-Mao Yuan; Song Yang; Kang Zhou (Phytochemistry, 2024)

Weathering-induced organic matter enrichment in marine-continental transitional shale: A case study on the early Permian Taiyuan Formation in the Ordos Basin, China - Zhengfu Zhao; Caineng Zou; Shifeng Dai; Zhaojie Guo; Yong Li; Arne Thorshøj Nielsen; Niels Hemmingsen Schovsbo; Zhenhua Jing; Hanlin Liu; Ming Yuan; Fangliang Fu; Jia Yin; et al. (International Journal of Coal Geology, 2024)

Construction and characterization of a novel Myr-OSADS-CIn micelle for enhanced stability and bioavailability of myricetin - Zhi-Yuan Nie; Xue-Ying Li; Ying-Ying Chen; Yuan-Yuan Deng; Dan-Dan Kuang; Yu-Lin Sun; Huan-Huan Xiao; Qiang-Ming Li; Jian-Ping Luo; Xue-Qiang Zha (Food Bioscience, 2024)

Surface charge accumulation of functionalized carbonized polymer dots selectively induces lysosomal membrane permeabilization of breast cancer cells - Yu Lei; Bao-Hua Tian; Xin-Xin Li; Ming-Yuan Sun; Xi-Lin Guo; Yi-Da Wang; Hui-Qing Zhou; Ri-Sheng Ma; Hai-Xia Liang (Chemical Engineering Journal, 2024)

La promoted Ni0-Niδ+ synergistic interaction for rapid and deep hydrogenation of liquid organic hydrogen carriers - Ting Zhu; Li Liu; Yifang Zhao; Min Gao; Yuan Dong; Dong Xia; Peng Huang; Hansong Cheng; Ming Yang (Chemical Engineering Journal, 2024)

Occurrence and mechanism of sulfamethoxazole in alginate-like extracellular polymers from excess sludge - Chen Shi; Ming Cheng; Run-Gen Zeng; Cong-Cong Li; Qian Wang; Li-Ting Hao; Ran-Bin Liu; Xiao-Di Hao; Xiang-Yang Wang; Yuan-Yuan Wu (Bioresource Technology, 2024)

Prevalence and molecular characterization of Cryptosporidium spp., Enterocytozoon bieneusi, and Giardia duodenalis in dairy cattle in Ningxia, northwestern China - Ming-Yuan Wang; Shan Zhang; Zhan-Sheng Zhang; Xiao-Yin Qian; Hai-Liang Chai; Yan Wang; Wen-Jun Fan; Chao Yi; Yu-Lin Ding; Wen-Xiong Han; Li Zhao; Yong-Hong Liu (Veterinary Research Communications, 2024)

Biochar produced from diverse invasive species improves remediation of cadmium-contaminated soils - Xue Wang; Wei-Long Zheng; Hao-Ming Yuan; Mark van Kleunen; Fei-Hai Yu; Mai-He Li (Biological Invasions, 2024)

Phylogeny and genetic diversity of Echinometra sea urchin in Taiwan - Mei-Fang Lin; Ming-Che Yang; Yi-Yuan Lin; Sheng-Chi Chung; Li-Lian Liu (Marine Biology Research, 2024)

Effect of microwaves combined with peracetic acid to improve the dewatering performance of residual sludge - Ming-Yuan Yu; Jian-Ping Sun; Shao-Feng Li; Jian Sun; Xiao-Ming Liu; Ao-Qian Wang (Environmental Science and Pollution Research, 2024)

Microplastic coupled with soil dissolved organic matter mediated changes in the soil chemical and microbial characteristics - Zhiwang Feng; Ningyuan Zhu; Hanzhou Wu; Ming Li; Jian Chen; Xuyin Yuan; Jizhou Li; Yimin Wang (Chemosphere, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Study on the effects of toosendanin against Eimeria tenella and its impact on the apoptosis of cecal cells in chicks - Li’nan Yang; Yanyang Yuan; Lei Xiong; Qingyu Zhao; Ming Yang; Xun Suo; Zhihui Hao (Veterinary Parasitology, 2024)

Non-equilibrium compression achieving high sensitivity and linearity for iontronic pressure sensors - Jing Yang; Zhibin Li; Ying Wu; Yong Shen; Ming Zhang; Bin Chen; Guojiang Yuan; Songhua Xiao; Jiansong Feng; Xu Zhang; Yuwei Tang; Sunan Ding; et al. (Science Bulletin, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Toxic effect and mRNA mechanism of moon dust simulant induced pulmonary inflammation in rats - Jintao Wang; Yuan Xue; Bin Wu; Ming Lei; Honglei Ma; Xinxing He; Qi Tan; Jian Guan; Wei Song; Renfu Li; Xinguang Cui (Toxicology, 2024)

Coating seeds with biopolymers extracted from waste-activated sludge - Chen Shi; Shi-Chao Yuan; Lin Zhang; Xiang-Yang Wang; Li-Ting Hao; Shi-Ming Su; Zhongfang Lei; Xiao-Di Hao (Sustainable Chemistry and Pharmacy, 2024)

Spatiotemporal characterization of PM2.5, O3, and trace gases associated with East Asian continental outflows via drone sounding - Chih-Yuan Chang; Jia-Lin Wang; Yen-Chen Chen; Wei-Nai Chen; Sheng-Hsiang Wang; Ming-Tung Chuang; Neng-Huei Lin; Charles C.-K. Chou; Wei-Syun Huang; Li-Jin Ke; Xiang-Xu Pan; Yu-Jui Ho; et al. (Science of The Total Environment, 2024)

Exploring the chemical diversity of sesquiterpenes from the rarely studied south China sea soft coral Sinularia tumulosa assisted by molecular networking strategy - Sheng-Hui Zhu; Yuan-Min Chang; Song-Wei Li; Ming-Zhi Su; Li-Gong Yao; Lin-Fu Liang; Hong Wang; Yue-Wei Guo (Phytochemistry, 2024)

Numerical simulation of wedges slamming non-Newtonian fluids based on SPH method - Jie Cui; Qing Yao; Xin Chen; Ming-Yuan Li; De-Tao Xu (Ocean Engineering, 2024)

Extraction and identification of polyphenol from Camellia oleifera leaves using tailor-made deep eutectic solvents based on COSMO-RS design - Shiling Feng; Guanfeng Deng; Huanyao Liu; Haiqiu Shi; Pingjin Li; Xiao Li; Tao Chen; Lijun Zhou; Ming Yuan; Chunbang Ding (Food Chemistry, 2024)

Boosting persulfate activation through efficient π → π* transition activated by Cu ion anchored porphyrin-based metal–organic framework - Wen-Qiang Li; Oleksandr Savateev; Yuan-Ming Li; Jian-Kang Zheng; Yi-Xuan Wang; Nannan Hou; Xiao-Cheng Liu; Rong-Rong Ding; Xiao-Guo Zhou; Yang Wang; Xian-Yang Shi; Yang Mu (Chemical Engineering Journal, 2024)

Kidney-targeted antioxidant salvianolic acid B nanoparticles restoring lysosome homeostasis for acute kidney injury therapy - Jian-Li Chen; Xiao-Hui Jia; Xuan Wu; Ming-Heng Yuan; Xinyue Xia; Dan Yin; Xu Chen; Ze-Yun Gu; Jia-Zheng Liu; Li-Ping Bai; Kathy Qian Luo; Jianfang Wang; et al. (Chemical Engineering Journal, 2024)

Multifunctional asymmetric foam with Compression-Enhanced EMI shielding effectiveness exhibits Real-Time tunability of Reflection/Absorption ratio and pressure sensing - Changxin Yuan; Xu Li; Ming Huang; Fei Li; Zongwen Zhang; Chunhui Wang; Wanbiao Hu (Chemical Engineering Journal, 2024)

Chemical constitutents and chemotaxonomic research of the deep-sea-derived fungus Talaromyces minioluteus W19 - Kai Zhang; Yuan Wang; Teng Long; Ya-Ping Xie; Zheng-Biao Zou; Yong Zhang; You Li; Ming-Min Xie; Guang-Ming Liu; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Chemical constituents of the deep-sea-derived fungus Trichoderma simmonsii ZEN3 and their chemotaxonomic significance - Li-Fang Liu; Yuan Wang; Rong Chao; Lin Xu; Zheng-Biao Zou; Kai Zhang; Ming-Min Xie; Xian-Qiang Chen; Cheng-Hai Gao; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

3D Visualization of Whole Brain Vessels and Quantification of Vascular Pathology in a Chronic Hypoperfusion Model Causing White Matter Damage - Yang Wu; Jia Ke; Song Ye; Li-Li Shan; Shuai Xu; Shu-Fen Guo; Meng-Ting Li; Tian-Ci Qiao; Zheng-Yu Peng; Yi-Lin Wang; Ming-Yuan Liu; He Wang; et al. (Translational Stroke Research, 2024)

Was the 2022 drought in the Yangtze River Basin, China more severe than other typical drought events by considering the natural characteristics and the actual impacts? - Siquan Yang; Hongquan Sun; Ruxin Zhao; Lisong Xing; Zhuoyan Tan; Yuan Ning; Ming Li (Theoretical and Applied Climatology, 2024)

Tannic Acid Impedes the Proliferation of Bladder Cancer Cells by Elevating Mitochondrial Pathways of Apoptosis - Chi-Cheng Li; Bruce Chi-Kang Tsai; Selvaraj Annseles Rajula; Chiung-Hung Hsu; Ming-Cheng Chen; Chia-Hua Kuo; Chung-Min Yeh; Dennis Jine-Yuan Hsieh; Wei-Wen Kuo; Chih-Yang Huang (Cell Biochemistry and Biophysics, 2024)

Rapidly count crop seedling emergence based on waveform Method(WM) using drone imagery at the early stage - Jie Yuan; Xu Li; Meng Zhou; Hengbiao Zheng; Zhitao Liu; Yang Liu; Ming Wen; Tao Cheng; Weixing Cao; Yan Zhu; Xia Yao (Computers and Electronics in Agriculture, 2024)

Antihypertensive treatment during pregnancy induces long-term changes in gut microbiota and the behaviors of the attention deficit hyperactivity disorder offspring - Hong-Bao Li; Meng-Lu Xu; Wen-Jie Xia; Yuan-Yuan Dong; Bo Peng; Qing Su; Xiao-Min Wang; Jia-Yue Yu; Ya-Nan Gao; Jun-Zhe Wu; Meng-Yue Xu; Jin-Bao Yang; et al. (Toxicology and Applied Pharmacology, 2024)

Microplastics in remote coral reef environments of the Xisha Islands in the South China Sea: Source, accumulation and potential risk - Jia Lin; Yuan-Ming Zhao; Zhi-Geng Zhan; Jia-Yuan Zheng; Qian-Zhi Zhou; Juan Peng; Yan Li; Xi Xiao; Jiang-Hai Wang (Journal of Hazardous Materials, 2024)

Endophytic bacteria for Cd remediation in rice: Unraveling the Cd tolerance mechanisms of Cupriavidus metallidurans CML2 - Yuan Zhang; Qi Zhou; Chang Gao; Yue Lu; Yang Sheng; Ming Xiao; Yueli Yun; Jonathan Nimal Selvaraj; Xianhua Zhang; Yadong Li; Xuejing Yu (Journal of Hazardous Materials, 2024)

Waste cigarette butts-templated synthesis of in-situ graphitic carbon-doped ZnO fibers boosting dual-selectivity NO2/butanone at different temperatures - Zhao-Qi Cui; Ze Wei; Cong Chen; Yuan-Yuan Sun; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2024)

Effects of land-use on soil C, N, and P stocks and stoichiometry in coastal wetlands dependent on soil depth and latitude - Jing Xiong; Xuexin Shao; Niu Li; Haijing Yuan; Enjun Liu; Ming Wu (CATENA, 2024)

Inhibition of PARP1 improves cardiac function after myocardial infarction via up-regulated NLRC5 - Jia-Ming Luo; Hong-Bin Lin; Ya-Qian Weng; Ying-Hui Lin; Lu-Ying Lai; Ji Li; Feng-Xian Li; Shi-Yuan Xu; Hong-Fei Zhang; Wei Zhao (Chemico-Biological Interactions, 2024)

Seeding invigoration effect of ice-containing clouds on lower convective clouds during MeiYu season in 2020 - Dejun Li; Chuanfeng Zhao; Jiefan Yang; Cao Liu; Tianyi Wang; Yingying Chen; Ming Li; Zhengteng Yuan; Hai Wang; Jia Fu; Yikun Yang; Yadi Li (Atmospheric Research, 2024)

Initial study and phylogenetic analysis of hard ticks (Acari: Ixodidae) in Nantong, China along the route of avian migration - Jian-Ming Yuan; Jing Su; Zhi-Hai Zhang; Bin Sun; Xue-Li Jiao; Xin Zhang; Yun-Peng Zhai; Yu-Jie Chen (Experimental and Applied Acarology, 2024)

Proteomics Sequencing Reveals the Role of TGF-β Signaling Pathway in the Peripheral Blood of Offspring Rats Exposed to Fluoride - Fang-fang Yu; Shui-yuan Yu; Lei-zhen Duan; Shuo Yang; Xiang-bo Hou; Yu-hui Du; Ming-hui Gao; Juan Zuo; Lei Sun; Xiao-li Fu; Zhi-yuan Li; Hui Huang; et al. (Biological Trace Element Research, 2024)

Changes in size-dependent Chlorophyll a concentration and group-specific picophytoplankton abundance in short-term nutrient-addition experiments in the Equatorial Eastern Indian Ocean - Ping Sun; Kai-Ming Sun; Yuping Zhou; Lu Liu; Chao Yuan; Zongjun Xu; Yan Li; Xuelei Zhang; Zongling Wang (Frontiers in Marine Science, 2024)
To clarify the changes in phytoplankton community and influencing factors in short-term nutrient-addition experiments in the Equatorial Eastern Indian Ocean, we conducted three experiments (one in situ-like experiment, one on-deck experiment with deep seawater, and one on-deck experiment with surface seawater). Our findings indicate that when nutrients were added, there was a more significant increase in the chlorophyll a (chl a ) concentrations of microphytoplankton (>20 μm) compared to those of nanophytoplankton (2-20 μm) and picophytoplankton (<2 μm). The chl a concentrations for phytoplankton <20 μm only exhibited significant increases in the on-board incubation of surface seawater collected at 1300 hr when grazing stress have likely been weak. In picophytoplankton, occasional increases in the abundances of Synechococcus were found, while the abundances of Prochlorococcus and eukaryotic picophytoplankton (Peuk) did not increase significantly. It results likely from the preference of grazing effect by herbivores and bottle effects. Additionally, the Prochlorococcus from 75 m was more adapted to weak light, thus its abundance sharply decreased when incubated under high light. We suggest that the nutrient effects have greater influence on microphytoplankton, but other factors, such as grazing and light, might contribute more to <20 μm phytoplankton. Furthermore, bottle effects should be considered when conducting incubation experiments.

Multimedia distribution, dynamics, and seasonal variation of PAHs in Songhua wetland: Implications for ice-influenced conditions - Bo Meng; Xi-Ze Min; Meng-Yuan Xiao; Wen-Xi Xie; Wen-Long Li; Ming-Gang Cai; Hang Xiao; Zi-Feng Zhang (Chemosphere, 2024)

Biogenic manganese oxides promote metal(loid) remediation by shaping microbial communities in biological aqua crust - Guobao Wang; Zekai Feng; Xiuran Yin; Daijie Chen; Nan Zhao; Yongqiang Yuan; Chiyu Chen; Chong Liu; Ming Ao; Lei Chen; Ziwu Chen; Wenjun Yang; et al. (Water Research, 2024)

Predicting environmental impacts of smallholder wheat production by coupling life cycle assessment and machine learning - Chunxiao Yu; Gang Xu; Ming Cai; Yuan Li; Lijia Wang; Yan Zhang; Huilong Lin (Science of The Total Environment, 2024)

Petrogenetic link between leucogranite and spodumene pegmatite in Lhozhag, eastern Himalaya: Constraints from U–(Th)–Pb geochronology and Li–Nd–Hf isotopes - Lei Yang; Jia-Min Wang; Xiao-Chi Liu; Fang-Yang Hu; Kang-Shi Hou; Jian-Gang Fu; Guang-Ming Li; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2024)

Gamma-ray irradiation as an effective method for mitigating antibiotic resistant bacteria and antibiotic resistance genes in aquatic environments - Ming-Qi Zhang; Xiao-Yong Zhang; Han-Chao Zhang; Hai-Bin Qiu; Zheng-Hao Li; Dong-Hua Xie; Li Yuan; Guo-Ping Sheng (Journal of Hazardous Materials, 2024)

Advancing safe bioenergy production from cadmium-contaminated sweet sorghum through mild synergistic pretreatment - Ming-Zhao Xiao; Ling-Hua Xu; Chen Zhang; Xiaojun Shen; Li Zhang; Tong-Qi Yuan (Journal of Cleaner Production, 2024)

Crystal mush rejuvenation in the formation of Triassic dacites in Mengku, SE Tibetan Plateau - Feng Cong; Fu-Yuan Wu; Wen-Chang Li; Zai-Bo Sun; Xiao-Chi Liu; De-Feng He; Wei-Qiang Ji; Fang-Yang Hu; Shao-Hua Zhang; Xiao-Ming Huang (Journal of Asian Earth Sciences, 2024)

Tailor-Made Homo/Heterojunction engineering of CdS@Prussian blue via One-Pot kinetic regulation for photoreduction of uranium (VI) from radioactive wastewater - Hao Ye; Rou-Ming Wen; Ming-Bang Wu; Zi-Hao Yuan; Jun Cao; Chaorong Li; Juming Yao (Chemical Engineering Journal, 2024)

Revealing of K and SO2 poisoning mechanism on CuCeOx catalyst for low-temperature CO oxidation - Zhenghua Shen; Xiangdong Xing; Yuan She; Sunxuan Wang; Ming Lv; Jixuan Li; Huizi Li (Chemical Engineering Journal, 2024)

Kinematic response analysis of a three-dimensional lifeboat water entry based on smoothed particle hydrodynamics - Ming-Yuan Li; Jie Cui; Xin Chen; Chang-Jun Gu; Bright Masvaya (Ocean Engineering, 2024)

Multifunctional Eu3+-MOF for simultaneous quantification of malachite green and leuco-malachite green and efficient adsorption of malachite green - Yi-Fan Xia; Hou-Qun Yuan; Chen Qiao; Wei Li; Ran Wang; Peiyao Chen; Yan-Xia Li; Guang-Ming Bao (Journal of Hazardous Materials, 2024)

Melatonin alleviates the toxic effect of di(2-ethylhexyl) phthalate on oocyte quality resulting from CEBPB suppression during primordial follicle formation - Jun-Jie Wang; Xiao-Yuan Zhang; Yue Zeng; Qing-Chun Liu; Xin-Lei Feng; Jia-Mao Yan; Ming-Hao Li; Russel J. Reiter; Wei Shen (Journal of Hazardous Materials, 2024)

Green space and its types can attenuate the associations of PM2.5 and its components with prediabetes and diabetes—— a multicenter cross-sectional study from eastern China - Zhiqian Cui; Rubing Pan; Jintao Liu; Weizhuo Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Li Liu; Ning Wei; Rong Song; Jiajun Yuan; et al. (Environmental Research, 2024)

Analyzing the correlation between quinolone-resistant Escherichia coli resistance rates and climate factors: A comprehensive analysis across 31 Chinese provinces - Yi-Chang Zhao; Zhi-Hua Sun; Ming-Xuan Xiao; Jia-Kai Li; Huai-yuan Liu; Hua-Lin Cai; Wei Cao; Yu Feng; Bi-Kui Zhang; Miao Yan (Environmental Research, 2024)

Optimal loading distribution of chillers based on an improved beluga whale optimization for reducing energy consumption - Ze Li; Jiayi Gao; Junfei Guo; Yuan Xie; Xiaohu Yang; Ming-Jia Li (Energy and Buildings, 2024)

Thermally managed and fireproof composite aerogels for safer and year-round energy saving - Wei Cai; Zhaoxin Li; Heng Xie; Wei Wang; Tianyang Cui; Bicheng Lin; Liangyuan Qi; Xin Hu; Yu Du; Yang Ming; Shuo Shi; Daming Chen; et al. (Chemical Engineering Journal, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Heterozygosity analysis of spontaneous 2n female gametes and centromere mapping of the diploid Hevea brasiliensis based on full-sib triploid populations - Yuan-yuan Zhang; Hong-kun Li; Xiao Huang; Yu-jiao Yuan; Xiao-fei Zhang; Xin-sheng Gao; Xiang-jun Wang; Ming-ming Wei; Hua-sun Huang; Weiguo Li (Plant Reproduction, 2024)

Associations between metal(loid) exposure with overweight and obesity and abdominal obesity in the general population: A cross-sectional study in China - Tianran Shen; Liling Zhong; Guiyuan Ji; Baolan Chen; Mengfan Liao; Lvrong Li; Huiming Huang; Jiajie Li; Yuan Wei; Shan Wu; Zihui Chen; Wenjun Ma; et al. (Chemosphere, 2024)

Effects of different stocking densities and feeding frequencies on growth, physiological and biochemical indexes, and intestinal microflora of largemouth bass (Micropterus salmoides) under land-based round pond - Yu-Xiang Xie; Xue-Ming Yang; Gen Kaneko; Jun-Neng Liang; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Pan Li; Wen-Wu Min; Lin-Yuan Jiang; Qiong Yang; et al. (Aquaculture, 2024)

Ponazuril: Clinical efficacy, ultrastructure, and histopathology studies of in vivo anticoccidial action against Eimeria tenella - Yanyang Yuan; Li’nan Yang; Qingyu Zhao; Lei Xiong; Ming Yang; Xun Suo; Zhihui Hao (Veterinary Parasitology, 2024)

Methionine redox regulation of actin-interacting proteins primarily governs antioxidative signaling and response to the salvianolic acid B treatment in EA.hy926 cells - Ai-Cheng Wang; Xiao-Ming Qi; Qing-Fang Li; Yi-Jia Feng; Yuan-Lin Zhang; Hui-Zhi Wei; Jin-Shan Li; Yuan-Biao Qiao; Qing-Shan Li (Toxicology and Applied Pharmacology, 2024)

Microplastics as potential barriers to ultraviolet light emitting diode inactivation of MS2 bacteriophage: Influence of water-quality parameters - Jiuming Hu; Zhiyong Zhang; Xiaoxue Li; Xiaochao Bi; Hongyang Jiang; Wenjie Sun; Ming-Lai Fu; Baoling Yuan (Science of The Total Environment, 2024)

Mechanisms and targeted reversion/prevention of hepatic fibrosis caused by the non-hereditary toxicity of benzo(a)pyrene - Xinru Du; Ming Jin; Ruzhi Li; Fei Zhou; Yuanze Sun; Qinliang Mo; Sisi Song; Na Dong; Shuoke Duan; Maoxuan Li; Ming Lu; Chi Zhang; et al. (Science of The Total Environment, 2024)

Co-application of concentrated biogas slurry and pyroligneous liquor mitigates ammonia emission and sustainably releases ammonium from paddy soil - Zichuan Li; Rui Zhang; Jianfeng Jiang; Yanjun Chai; Haijun Yang; Yutong Zong; Wenbin Tong; Mengting Yuan; Ronghui Li; Lanting Wang; Shengdao Shan; Ming Hung Wong (Science of The Total Environment, 2024)

Characteristics of ash formed by different lubricant additives and its effect on DPF performance - Pi-qiang Tan; Tian-peng Liu; Li-shuang Duan; Yi-fan Yin; Di-ming Lou; Zhi-yuan Hu (Fuel, 2024)

A biomimetic nociceptor system with tactile perception based on Ni-Al layered double hydroxides/gelatin heterojunction memristor - Yanmei Sun; Yan Dong; Zhiyuan Li; Qingkun Li; Ming Liu; Qi Yuan; Bingxun Li (Chemical Engineering Journal, 2024)

Solar driven thermal responsive polyionic liquid/PDDA semi-IPN hydrogel for near-room temperature membrane-free osmotic desalination - Xueyu Yuan; Jing Jiang; Zihao Zhou; Hongyu Pan; Chengwei Wang; Chor Yong Tay; Jinhua Hu; Li Liu; Bing Li; Yufeng Cai; Ming Liu (Chemical Engineering Journal, 2024)

Interactions between soil bacterial communities, assembly processes and microbial functions along the elevational gradient - Donghui Zhao; Congcong Shen; Zhi-Ming Zhang; Jichen Wang; Li-Mei Zhang; Baodong Chen; Guo-Xin Sun; Yuan Ge (CATENA, 2024)

Peroxisome Proliferator-Activated Receptor-γ Coactivator-1α in the Spotlight with Multiple Sclerosis - Ya-Na Yang; Mao-Qing Zhang; Feng-Lin Yu; Bing Han; Ming-Yue Bao; Yan He; Xing Li; Yuan Zhang (Neuroscience Bulletin, 2024)

VNS improves VSMC metabolism and arteriogenesis in infarcted hearts through m/n-AChR-Akt-SDF-1α in adult male rats - Xing-yuan Li; Jia-Qi Liu; Yan Wang; Yan Chen; Wen-hui Hu; Yan-xia Lv; Yan Wu; Jing Lv; Jun-ming Tang; Deying Kong (Journal of Molecular Histology, 2024)
Vagal nerve stimulation (VNS) provides a novel therapeutic strategy for injured hearts by activating cholinergic anti-inflammatory pathways. However, little information is available on the metabolic pattern and arteriogenesis of VSMCs after MI. VNS has been shown to stimulate the expression of CPT1α, CPT1β, Glut1, Glut4 and SDF-1α in coronary VSMCs, decreasing the number of CD68-positive macrophages while increasing CD206-positive macrophages in the infarcted hearts, leading to a decrease in TNF-α and IL-1β accompanied by a reduced ratio of CD68- and CD206-positive cells, which were dramatically abolished by atropine and mecamylamine in vivo. Knockdown of SDF-1α substantially abrogated the effect of VNS on macrophagecell alteration and inflammatory factors in infarcted hearts. Mechanistically, ACh induced SDF-1α expression in VSMCs in a dose-dependent manner. Conversely, atropine, mecamylamine, and a PI3K/Akt inhibitor completely eliminated the effect of ACh on SDF-1α expression. Functionally, VNS promoted arteriogenesis and improved left ventricular performance, which could be abolished by Ad-shSDF-1α. Thus, VNS altered the VSMC metabolism pattern and arteriogenesis to repair the infarcted heart by inducing SDF-1α expression, which was associated with the m/nAChR-Akt signaling pathway.

Dual-emissive Eu(III)-functionalized metal-organic frameworks for visual, rapid, and intelligent sensing of albendazole and albendazole sulfoxide in animal-origin food - Hou-Qun Yuan; Yi-Fan Xia; Yu-Fei Zhong; Wei Li; Hongda Zhu; Ran Wang; Peiyao Chen; Zhiming Gao; Xiangwei Zhu; Yan-Xia Li; Guang-Ming Bao (Analytica Chimica Acta, 2024)

Gut microbiota influence frailty syndrome in older adults: mechanisms and therapeutic strategies - Xiao-Ming Wang; Lu Fan; Chen-Chen Meng; Yun-Jiao Wang; Li-E Deng; Zhuo Yuan; Jun-Ping Zhang; Yan-Yang Li; Shi-Chao Lv (Biogerontology, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Overlooked encounter process that affects physical behaviors of stabilized nanoscale zero-valent iron during in situ groundwater remediation - Yujie Xie; Miaoyue Zhang; Lihang Ma; Ting Du; Dan Zhou; Ming-Lai Fu; Baoling Yuan; Xiao-yan Li; Yi-bo Hu (Journal of Hazardous Materials, 2024)

Effects of lubricant components on ash-bridge deposition characteristics in the diesel particulate filter - Pi-qiang Tan; Yuan Tian; Li-shuang Duan; Yun-peng Li; Di-ming Lou; Zhi-yuan Hu (Fuel, 2024)

The brominated flame retardant tetrabromobisphenol A-bis(2,3-dibromo-2-methylpropyl ether) as well as hexabromocyclododecane lead to lipid disorders in mice - Xuan-Yue Chen; Yuan-Yuan Li; Lin Lv; Yi-Ming Xiong; Zhan-Fen Qin (Environmental Pollution, 2024)

Environmentally friendly super-insulating material with three-dimensional nanoporous structure: A promising candidate for future gas insulated transmission lines and carbon sequestration - Wenxia Sima; Xiaoxiao Chen; Potao Sun; Tao Yuan; Ming Yang; Yongqing Chen; Wenlong Pang; Zhaoping Li (Chemical Engineering Journal, 2024)

Preparation and characterization of lotus root starch based bioactive edible film containing quercetin-encapsulated nanoparticle and its effect on grape preservation - Ya-Fan Zeng; Ying-Ying Chen; Yuan-Yuan Deng; Chao Zheng; Cheng-Zhi Hong; Qiang-Ming Li; Xue-Fei Yang; Li-Hua Pan; Jian-Ping Luo; Xue-Ying Li; Xue-Qiang Zha (Carbohydrate Polymers, 2024)

Identification and fine-mapping of QYrAS286-2BL conferring adult-plant resistance to stripe rust in cultivated emmer wheat - Yuqin Li; Yanling Hu; Yun Jiang; Qiang Zhou; Yu He; Jingshu He; Xuejiao Chen; Xue Chen; Bo Jiang; Ming Hao; Shunzong Ning; Zhongwei Yuan; et al. (Theoretical and Applied Genetics, 2024)

Potentiation of the lateral habenula-ventral tegmental area pathway underlines the susceptibility to depression in mice with chronic pain - Chun-Kui Zhang; Pan Wang; Yuan-Yuan Ji; Jian-Shuai Zhao; Jun-Xiang Gu; Xian-Xia Yan; Hong-Wei Fan; Ming-Ming Zhang; Yu Qiao; Xiao-Die Liu; Bao-Juan Li; Ming-Hui Wang; et al. (Science China Life Sciences, 2024)

Assessment of the seismic hazard in North China by combining micro-seismicity records and geodetic observations - Yuan Gao; Wei Qu; Qin Zhang; Jiuyuan Li; Da Li; Yuhao Wang; Ming Hao (Tectonophysics, 2023)

Occurrence of liquid crystal monomers in indoor and outdoor air particle matters (PM10): Implications for human exposure indoors - Li-Li Yao; Jun-Li Wang; Rong-Fa Xu; Ming Zhu; Yan Ma; Bin Tang; Qi-Yuan Lu; Feng-Shan Cai; Xiao Yan; Jing Zheng; Yun-Jiang Yu (Science of The Total Environment, 2023)

Non-steroidal anti-inflammatory drugs (NSAIDs) in the environment: Recent updates on the occurrence, fate, hazards and removal technologies - Jia-yuan Lin; Yuan Zhang; Yu Bian; Yi-xin Zhang; Rong-zhu Du; Ming Li; Yue Tan; Xue-song Feng (Science of The Total Environment, 2023)

Time-domain numerical simulation for multi-ships moving in waves with forward speed - Mingxin Li; Suyong Pan; Yong Cheng; Zhi-Ming Yuan; Longbin Tao (Ocean Engineering, 2023)

Physicochemical characteristics of ash-bridges in diesel particulate filter - Li-shuang Duan; Pi-qiang Tan; Yun-peng Li; Yi-fan Yin; Di-ming Lou; Zhi-yuan Hu (Journal of Cleaner Production, 2023)

An acidic heteropolysaccharide rich in galactose and arabinose derived from ginger: Structure and dynamics - Xiao-tong Lin; Bo-xian Xiao; Jun-ping Liu; Ming-yuan Cao; Zhi-ping Yang; Li-yan Zhao; Gui-tang Chen (Food Bioscience, 2023)

Insights into the adsorptive separation of iron from pickling waste acid: The overlooked role of FeCl3 species - Ling Yuan; Mujian Xu; Rongming Xu; Chenghan Ji; Hailun Yang; Hang Yu; Xiaoyang Li; Ming Hua; Lu Lv; Weiming Zhang (Chemical Engineering Journal, 2023)

Exploration of the Catalytic Cycle Dynamics of Vigna Radiata H+–Translocating Pyrophosphatases Through Hydrogen–Deuterium Exchange Mass Spectrometry - Li-Kun Huang; Yi-Cyuan Huang; Pin-Chuan Chen; Ching-Hung Lee; Shih-Ming Lin; Yuan-Hao Howard Hsu; Rong-Long Pan (The Journal of Membrane Biology, 2023)

The Prevention Effect of Lactobacillus plantarum 17–5 on Escherichia coli-Induced Mastitis in Mice - Ke Li; Ming Yang; Li Jia; Mengyue Tian; Jinliang Du; Yinghao Wu; Lining Yuan; Lianmin Li; Yuzhong Ma (Probiotics and Antimicrobial Proteins, 2023)

Abnormal grey matter structural changes in patients with end-stage kidney disease and mild cognitive impairment: correlations with clinical features - Huijie Yuan; Zhaoyao Luo; Wen Gu; Shaohui Ma; Guangyu Li; Dun Ding; Xueying Ma; Peng Li; Jing Yang; Xiaoling Xu; Junya Mu; Ming Zhang (Metabolic Brain Disease, 2023)
End-stage kidney disease and mild cognitive impairment (ESKD-MCI) affect the quality of life and long-term treatment outcomes of patients affected by these diseases. Clarifying the morphological changes from brain injuries in ESKD-MCI and their relationship with clinical features is helpful for the early identification and intervention of MCI before it progresses to irreversible dementia. This study gathered data from 23 patients with ESKD-MCI, 24 patients with ESKD and non-cognitive impairment (NCI), and 27 health controls (HCs). Structural magnetic resonance studies, cognitive assessments, and general clinical data were collected from all participants. Voxel-based morphometry analysis was performed to compare grey matter (GM) volume differences between the groups. The patients’ GM maps and clinical features were subjected to univariate regression to check for possible correlations. Patients with ESKD-MCI displayed significantly more impairments in multiple cognitive domains, including global cognition, visuospatial and executive function, and memory, compared to patients with ESKD-NCI. Using a more liberal threshold ( P < 0.001, uncorrected), we found that compared to patients with ESKD-NCI, patients with ESKD-MCI exhibited clusters of regions with lower GM volumes, including the right hippocampus (HIP), parahippocampal gyrus (PHG), Rolandic operculum, and supramarginal gyrus. The volumes of the right HIP and PHG were negatively correlated with serum calcium levels. ESKD-MCI was associated with a subtle volume reduction of GM in several brain areas known to be involved in memory, language, and auditory information processing. We speculate that these slight morphometric impairments may be associated with disturbed calcium metabolism.

DDB2 and MDM2 genes are promising markers for radiation diagnosis and estimation of radiation dose independent of trauma and burns - Ling-Hu Cai; Xiang-Yu Chen; Wei Qian; Chuan-Chuan Liu; Li-Jia Yuan; Liang Zhang; Chao Nie; Zhen Liu; Yue Li; Tian Li; Ming-Hua Liu (Functional & Integrative Genomics, 2023)

Maximum helical dichroism enabled by an exceptional point in non-Hermitian gradient metasurfaces - Xiao Li; Chuanjie Hu; Yuan Tian; Youwen Liu; Huanyang Chen; Yadong Xu; Ming-Hui Lu; Yangyang Fu (Science Bulletin, 2023)

Phenolic glycosides and indole alkaloids isolated from the roots and rhizomes of Clematis chinensis and their anti-inflammatory activity - Hai-Bing Jiang; Si-Yuan Shao; Ya-Zi Wei; Ming-Bao Lin; Shuai Li (Phytochemistry, 2023)

Interference effects on the upstream wave generated by the catamaran moving across a depth change - Mingxin Li; Yi Chen; Zhi-Ming Yuan; Yong Cheng; Longbin Tao (Ocean Engineering, 2023)

Dual roles of the Arabidopsis PEAT complex in histone H2A deubiquitination and H4K5 acetylation - Si-Yao Zheng; Bin-Bin Guan; Dan-Yang Yuan; Qiang-Qiang Zhao; Weiran Ge; Lian-Mei Tan; Shan-Shan Chen; Lin Li; She Chen; Rui-Ming Xu; Xin-Jian He (Molecular Plant, 2023)

Mineralogy, petrology and P-T conditions of the spodumene pegmatites and surrounding meta-sediments in Lhozhag, eastern Himalaya - Jia-Min Wang; Kang-Shi Hou; Lei Yang; Xiao-Chi Liu; Ru-Cheng Wang; Guang-Ming Li; Jian-Gang Fu; Fang-Yang Hu; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2023)

Effect of ash on temperature and particulate emission characteristics of diesel particulate filter during active regeneration - Li-shuang Duan; Pi-qiang Tan; Yi-fan Yin; Yun-peng Li; Di-ming Lou; Zhi-yuan Hu (Journal of Cleaner Production, 2023)

Enhancing data reliability in quantitative characterization of moisture distribution in sludge using DSC: Impact of sample attributes and test parameters - Ya-Li Zhang; Hao Zhang; Wen-Hui Liu; Ping Sun; Shao-Ming Zheng; Yun-Yan Gao; Yuan-Ping Zeng; Hou-Feng Wang; Raymond Jianxiong Zeng (Journal of Environmental Management, 2023)

Ångstrom-scale silver particles ameliorate collagen-induced and K/BxN-transfer arthritis in mice via the suppression of inflammation and osteoclastogenesis - Ze-Hui He; Jing-Tao Zou; Xia Chen; Jiang-Shan Gong; Ya Chen; Ling Jin; Yi-Wei Liu; Shan-Shan Rao; Hao Yin; Yi-Juan Tan; Zun Wang; Wei Du; et al. (Inflammation Research, 2023)

Extended exposure to tetrabromobisphenol A-bis(2,3-dibromopropyl ether) leads to subfertility in male mice at the late reproductive age - Yuan-Yuan Li; Yi-Ming Xiong; Xuan-Yue Chen; Jia-Yi Sheng; Lin Lv; Xing-Hong Li; Zhan-Fen Qin (Archives of Toxicology, 2023)

Paternal lipopolysaccharide exposure induced intrauterine growth restriction via the inactivation of placental MEST/PI3K/AKT pathway in mice - Pei-Ying Jiang; Shuai Lin; Jie-Ru Liu; Yan Liu; Li-Ming Zheng; Qiang Hong; Yi-Jun Fan; De-Xiang Xu; Yuan-Hua Chen (Archives of Toxicology, 2023)

The regulative effect and repercussion of probiotics and prebiotics on osteoporosis: involvement of brain-gut-bone axis - Yuan-Wei Zhang; Mu-Min Cao; Ying-Juan Li; Guang-Chun Dai; Pan-Pan Lu; Ming Zhang; Li-Yong Bai; Xiang-Xu Chen; Cheng Zhang; Liu Shi; Yun-Feng Rui (Critical Reviews in Food Science and Nutrition, 2023)

Current advances in the detection and removal of organic arsenic by metal-organic frameworks - Wen-Qing Ding; Lazhar Labiadh; Lei Xu; Xiao-Ying Li; Chen Chen; Ming-Lai Fu; Baoling Yuan (Chemosphere, 2023)

Manganese losses induced by severe soil acidification in the extensive Lei bamboo (Phyllostachys violascens) plantation stands in Eastern China - Yutong Zong; Zichuan Li; Renyi Gui; De Chen; Mengting Yuan; Yanjun Chai; Shengdao Shan; Ming Hung Wong (Chemosphere, 2023)

Vertical distribution and transport of microplastics in the urban atmosphere: New insights from field observations - Zhen Yuan; Cheng-Lei Pei; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Kai Zhang; Ming-Gang Cai; Xiang-Rong Xu (Science of The Total Environment, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

Inhibition of postharvest rachis browning of table grapes by sulfur dioxide: Evidence from phenolic metabolism and sulfur assimilation - Zhenbiao Li; Siqi Chen; Ming Qi; Mingyi Yang; Hemao Yuan; Yanqun Xu; Jing Huang; Dong Li; Wei Zhou; Yaya Yuan; Zisheng Luo; Li Li (Postharvest Biology and Technology, 2023)

Nine pairs of undescribed enantiomers from the resin of Styrax tonkinensis (Pierre) Craib ex Hart with anti-inflammatory activity - Qun Li; Hong-Bin Fang; Bin-Yuan Hu; Yong-Ming Yan; Ya-Bin Jiao; Gan-Peng Li; Yong-Xian Cheng (Phytochemistry, 2023)

Rapid determination of the relative configuration of diverse 8,4′-oxyneolignans by NMR analysis: Retrospective studies, improvement and structural revision - Peng Zhao; Li-Li Lou; Ben-Song Xin; Zhi-Yuan Li; Rui Guo; Wei-Yu Zhou; Tian-Ming Lv; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Ent-eudesmane sesquiterpenoids from the Chinese liverwort Chiloscyphus polyanthus - Ming-Zhu Zhu; Yi Li; Jin-Chuan Zhou; Dong-Xue Lv; Xiao-Jie Fu; Zhen Liang; Shuang-Zhi Yuan; Jing-Jing Han; Jiao-Zhen Zhang; Ze-Jun Xu; Wen-Qiang Chang; Hong-Xiang Lou (Phytochemistry, 2023)

Real-time control of ship's roll motion with gyrostabilisers - Lifen Hu; Ming Zhang; Xingxing Yu; Zhi-Ming Yuan; Wubin Li (Ocean Engineering, 2023)

Investigation on the flow characteristics near the duct of a pump-jet propulsion under different advance coefficient conditions - Shun Xu; Yong-liang Xiong; Gui-bin Li; Ming-yuan Wei; Xin-ping Long; Bin Ji (Ocean Engineering, 2023)

Effects of ammonia and roxithromycin exposure on skin mucus microbiota composition and immune response of juvenile yellow catfish Pelteobagrus fulvidraco - Donghao Yuan; Shidong Wang; Xue Li; Muzi Zhang; Ming Li (Fish & Shellfish Immunology, 2023)

Construction of covalent organic framework nanozymes with photo-enhanced hydrolase activities for colorimetric sensing of organophosphorus nerve agents - Sai-Jin Xiao; Ming-Yue Yuan; Ya-Di Shi; Meng-Ping Wang; Hui-Han Li; Li Zhang; Jian-Ding Qiu (Analytica Chimica Acta, 2023)

Co-exposure of polystyrene microplastics influence cadmium trophic transfer along the “lettuce-snail” food chain: Focus on leaf age and the chemical fractionations of Cd in lettuce - Yimin Wang; Xinyue Qian; Juan Chen; Xuyin Yuan; Ningyuan Zhu; Yudong Chen; Tingting Fan; Ming Li; Harry Toland; Zhiwang Feng (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Numerical simulation and energy extraction power fitting of OWSCs under regular waves using SPH method - Xin Chen; Jie Cui; Ming-Yuan Li (Ocean Engineering, 2023)

Codelivery of vorinostat and chloroquine by autophagy-inhibitory hollow ZrO2 nanoshells for synergistic combination chemotherapy - Jian-Li Chen; Xiao-Hui Jia; Xinyue Xia; Xuan Wu; Yan-Neng Xu; Gang Yuan; Ze-Yun Gu; Kathy Qian Luo; Ming-Heng Yuan; Ruibin Jiang; Jianfang Wang; Xiao-Ming Zhu (Chemical Engineering Journal, 2023)

Chemomechanical pretreatment for efficient delignification and saccharification of corn stover biomass - Samuel Ntakirutimana; Tao Xu; Ming-Zhu Ding; Zhi-Hua Liu; Bing-Zhi Li; Ying-Jin Yuan (Chemical Engineering Journal, 2023)

Improving lactic acid yield of hemicellulose from garden garbage through pretreatment of a high solid loading coupled with semi-hydrolysis using low enzyme loading - Wenbin Zhu; Haishu Sun; Yuanchun Zhang; Nuohan Wang; Yuan Li; Shuo Liu; Ming Gao; Ying Wang; Qunhui Wang (Bioresource Technology, 2023)

Rapid generation of a tomato male sterility system and its feasible application in hybrid seed production - Ming Zhou; Lei Deng; Guoliang Yuan; Wei Zhao; Mingyang Ma; Chuanlong Sun; Minmin Du; Chuanyou Li; Changbao Li (Theoretical and Applied Genetics, 2023)

Structural characteristics of the moss (bryophyte) layer and its underlying soil structure and water retention characteristics - Xia Hu; Zhou Gao; Xiao-Yan Li; Rui-Zhe Wang; Yuan-Ming Wang (Plant and Soil, 2023)

Delays in heading and improvements in both spikelet number and spike length are associated with the Aegilops tausschii photoperiod-sensitive ppd-D1b allele - Shunzong Ning; Laibin Zhao; Shijie Li; Shengke Li; Tianqing Zang; Yu’e Liu; Hongkun Yang; Xuejiao Chen; Xue Chen; Yingjin Yi; Ming Hao; Lianquan Zhang; et al. (Cereal Research Communications, 2023)

Enhancement of electrokinetic-phytoremediation by Ophiopogon japonicus: stimulation of electrokinetic on root system and improvement of polycyclic aromatic hydrocarbon degradation - Ming Li; Yingping Huang; Kun Li; Xi Yuan; Huigang Liu; Meng Li; Tao Xu; Zhaonian Zhang; David M. Johnson; Ying Xi (Environmental Science and Pollution Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Bidirectional crosstalk of the cAMP/ROS-dependent signaling pathways in inflammatory macrophage: An activation of formononetin - Lan-Fang Zhang; Xiao-Yan Zhang; Ai-Cheng Wang; Yi-Jia Feng; Xiao-Ming Qi; Yuan-Lin Zhang; Qing-Fang Li; Yuan-Biao Qiao; Qing-Shan Li (Toxicology and Applied Pharmacology, 2023)

Variations and driving mechanisms of desertification in the southeast section of the China-Mongolia-Russia Economic Zone - Yonghua Zhao; Shuyuan Yang; Li Liu; Xia Jia; Lei Han; Xuefeng Yuan; Ming Zhao; Peng Zhang (Science of The Total Environment, 2023)

Experimental study of emission characteristics and performance of SCR coated on DPF with different catalyst washcoat loadings - Pi-qiang Tan; Ying-jie Chen; Zi-tong Wang; Li-shuang Duan; Yang Liu; Di-ming Lou; Zhi-yuan Hu; Yun-hua Zhang (Fuel, 2023)

Characteristics of mesenchymal stem cells and their exosomes derived from giant panda (Ailuropoda melanoleuca) endometrium - Yu-Liang Liu; Jia-Song Chen; Jun-Hui An; Zhi-Gang Cai; Jing-Chao Lan; Yuan Li; Xiang-Wei Kong; Ming-Yue Zhang; Rong Hou; Dong-Hui Wang (In Vitro Cellular & Developmental Biology - Animal, 2023)

Population structure and genetic diversity of Triticum araraticum Jakubz. and Triticum timopheevii Zhuk. - Ting Peng; Xiaomei Jiang; Dinghao Wang; Minghu Zhang; Xin Liu; Ming Hao; Wei Li; Dengcai Liu; Bo Jiang; Lin Huang; Shunzong Ning; Zhongwei Yuan; et al. (Genetic Resources and Crop Evolution, 2023)

Correlation of heavy metals’ exposure with the prevalence of coronary heart disease among US adults: findings of the US NHANES from 2003 to 2018 - Xi Li; Dongdong Zhang; Yang Zhao; Lei Kuang; Hao Huang; Weiling Chen; Xueru Fu; Yuying Wu; Tianze Li; Jinli Zhang; Lijun Yuan; Huifang Hu; et al. (Environmental Geochemistry and Health, 2023)

A systematic review: on the mercaptoacid metabolites of acrylamide, N-acetyl-S-(2-carbamoylethyl)-L-cysteine - Fang-Fang Zhao; Xiao-Li Wang; Ya-Ting Lei; Hong-Qiu Li; Zhi-Ming Li; Xiao-Xiao Hao; Wei-Wei Ma; Yong-Hui Wu; Sheng-Yuan Wang (Environmental Science and Pollution Research, 2023)

Numerical study of wedge entry in still water and waves using smoothed particle hydrodynamics methods - Jie Cui; Chang-Jun Gu; Xin Chen; Ming-Yuan Li; Bright Masvaya (Ocean Engineering, 2023)

Dansyl-labelled cellulose as dual-functional adsorbents for elimination and detection of mercury in aqueous solution via aggregation-induced emission - Ming Li; Siqi Zhang; Panpan Zhang; Kexin Qin; Qian Chen; Qianyong Cao; Yuling Zhang; Jinghong Zhang; Chungang Yuan; Huining Xiao (Journal of Environmental Management, 2023)

Variation in microbiological heterogeneity in Chinese strong-flavor Baijiu fermentation for four representative varieties of sorghum - Mao-Ke Liu; Yu-Ming Tang; Cheng-Yuan Liu; Xin-Hui Tian; Ji-Wei Zhang; Xiao-Li Fan; Kai-Feng Jiang; Xian-Lin Ni; Xin-Yu Zhang (International Journal of Food Microbiology, 2023)

Heavy metals in fish, rice, and human hair and health risk assessment in Wuhan city, central China - Muhammad Ubaid Ali; Chuan Wang; Yuan Li; Ruolan Li; Shaochen Yang; Li Ding; Lin Feng; Bo Wang; Ping Li; Ming Hung Wong (Environmental Pollution, 2023)

Identification of sweet spots in shale-type and siltstone-type “shale oil systems”: A case study of the Chang 7 Member in Ordos Basin - Songqi Pan; Qiulei Guo; Caineng Zou; Zhenhua Jing; Ming Yuan; Ying He; He Zheng; Ying Mu; Zhi Yang; Shixiang Li; Xinping Zhou; Songtao Wu; et al. (Science China Earth Sciences, 2023)

Chitinolyticbacter albus sp. Nov., A Novel Chitin-Degrading Bacterium Isolated from Ancient Wood Rhizosphere Soil - Meng-Yu Zhang; Jiang-Yuan Zhao; Le-Le Li; Cheng Ling; Jing Tang; Song-Guo Liang; Jian-Yu Li; Xiao-Di Liu; Lu-Yao Feng; Pei-Wen Yang; Zhu-Feng Shi; Zhang-Gui Ding; et al. (Current Microbiology, 2023)

Synthesis of novel adsorbent S-SiO2@Fe3O4 based on strong bonding of S-O-Se for selenium removal in water - Chang-Xian Zhao; Xin-Peng Ma; Xue-Lei Duan; Qi Guo; Sheng-Li Niu; Wen-Jing Zhou; Yuan-Ming Cao; Chun-Gang Yuan (Journal of Environmental Chemical Engineering, 2023)

Phenylpropanoids from the Nitraria tangutorum fruit as glycerol phosphate dehydrogenase inhibitors through in vitro, in silico and in vivo studies - Zhi-Xiang Liu; Lin-Lin Yuan; Nan Zhang; Min Zhao; Yue Li; Ming-Yue Zhao; Yu-Meng Wang; Zi-Zhuo Wang; Yang-Yang Zhang; Jin-Long Tian (Food Bioscience, 2023)

Effects of adsorption characteristics of carbocatalysts on persulfate-based advanced oxidation processes: Organic removal mechanisms and optimization strategies - Xiang-Feng Huang; Jing-Xi Yuan; Xia Zhao; Shuang-Qiang Li; Li-Heng Yang; Wen-Yan Li; Kai-Ming Peng; Chen Cai; Jia Liu (Chemical Engineering Journal, 2023)

Upregulation of glycolytic enzyme PFKFB3 by deubiquitinase OTUD4 promotes cardiac fibrosis post myocardial infarction - Feizuo Wang; Xiaojian Yin; Yuan-Ming Fan; Xinyao Zhang; Chao Ma; Keke Jia; Wei Zhou; Zongxiang Tang; Lian-Wen Qi; Jia Li (Journal of Molecular Medicine, 2023)
Metabolic dysregulations have emerged as a major mediator of cardiovascular disorders and fibrotic diseases. Metabolic reprogramming contributes a lot to cardiac fibroblast activation and cardiac fibrosis post-myocardial infarction (MI), yet the mechanism remains incompletely understood. Our work aimed to determine whether or not glycolytic reprogramming, regulated by phosphofructokinase-2/fructose-2,6-bisphosphatase 3 (PFKFB3), is a therapeutic target for alleviating post-MI cardiac fibrosis. Here, we showed that cardiac fibroblasts displayed cell energy phenotype toward augmented glycolysis in response to transforming growth factor-beta 1 (TGF-β1), evidenced by significant extracellular acidification rate (ECAR) increase and lactate accumulation. The expression of glycolytic enzyme PFKFB3, a master activator of glycolysis, was up-regulated in TGF-β1-treated cardiac fibroblasts and in cardiac fibroblasts of post-MI mice. Pharmacological inhibition of PFKFB3 by 3PO diminished TGF-β1-mediated profibrotic phenotypes, attenuated cardiac fibrosis, and preserved cardiac functions in post-MI mice. Meanwhile, the genetic inhibition of PFKFB3 decreased the cardiac fibroblast activation and reversed the differentiated phenotypes in vitro and in vivo. Mechanistically, we identified deubiquitinase OTUD4 as a new binding protein of PFKFB3, and their interaction blocked PFKFB3 degradation via OTUD4-mediated deubiquitylation. Taken together, this work characterized a key role for PFKFB3 in cardiac fibroblast activation and suggested that inhibiting PFKFB3-involved glycolysis is an alternative way to alleviate post-MI cardiac fibrosis. Key messages PFKFB3, a master activator of glycolysis, was highly expressed in ischemic cardiac fibroblasts to enhance cardiac fibrosis The deubiquitinase OTUD4 was identified as a new binding protein of PFKFB3 TGF-β1 blunted the ubiquitination-mediated degradation of PFKFB3 via OTUD4-mediated deubiquitylation Blockade of PFKFB3 contributed to ameliorating ischemia-induced cardiac fibrosis

Pseudomonas subflava sp. nov., a new Gram-negative bacterium isolated from Guishan in Yunnan province, south–west China - Cheng Ling; Jiang-Yuan Zhao; Le-Le Li; Zhang-Gui Ding; Meng-Yu Zhang; Jing Tang; Song-Guo Liang; Jian-Yu Li; Xiao-Di Liu; Lu-Yao Feng; Pei-Wen Yang; Yao Lu; et al. (Antonie van Leeuwenhoek, 2023)

Wash waves generated by ship moving across a depth change - Mingxin Li; Zhi-Ming Yuan; Longbin Tao (Ocean Engineering, 2023)

Overexpression of Sedum SpHMA2, SpHMA3 and SpNramp6 in Brassica napus increases multiple heavy metals accumulation for phytoextraction - Zi Yang; Hai-Tao Wu; Hao Yang; Wan-Di Chen; Jia-Lan Liu; Fan Yang; Li Tai; Bin-Bin Li; Bo Yuan; Wen-Ting Liu; Yan-Feng Zhang; Yan-Rong Luo; et al. (Journal of Hazardous Materials, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Effects of frequencies on the cyclic behavior of marine soft clay under different consolidated stress paths - Mingfeng Li; Ming Dai; Shengnan Yao; Shihu Gao; Guohui Yuan (Marine Georesources & Geotechnology, 2023)

Regional-modal optimization problems and corresponding normal search particle swarm optimization algorithm - Yi-li Yuan; Chang-ming Hu; Liang Li; Yuan Mei; Xue-yan Wang (Swarm and Evolutionary Computation, 2023)

Effect of lithofacies on differential movable fluid behaviors of saline lacustrine fine-grained mixed sedimentary sequences in the Jimusar sag, Junggar Basin, NW China: Forcing mechanisms and multi-scale models - Wei Yang; Yaohua Wang; Ming Xie; Yingyan Li; Yang Gao; Yuan Deng; Changfu Xu; Jianhua Qin; Shouchang Peng; Leilei Yang; Linjie Yao; Haodong Hou (Marine and Petroleum Geology, 2023)

Numerical investigations of the micro lunar dust particles deposition in the human oral respiratory airway - Xinguang Cui; Wei Song; Yuan Xue; Hanxiong Guan; Jinhua Zhang; Xinxing He; Honglei Ma; Ming Lei; Jintao Wang; Yichao Li (Journal of Hazardous Materials, 2023)

Smart contract design and process optimization of carbon trading based on blockchain: The case of China's electric power sector - Tian-yuan Zhang; Tian-tian Feng; Ming-li Cui (Journal of Cleaner Production, 2023)

The priming effects of plant leachates on dissolved organic matter degradation in water depend on leachate type and water stability - Yuan Cui; Jian-Qiao Meng; Yu-Han Chen; Fei-Fan Shao; Xuan-Zheng Chen; Yu Jin; Ming-Xiang Zhang; Guo Yun-Qian; Fang-Li Luo; Fei-Hai Yu (Environmental Research, 2023)

A critical review on graphene oxide membrane for industrial wastewater treatment - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2023)

Suppressing staircase-like electrochemical profile induced by P O transition by solid-solution reaction with continuous structural evolution in layered Na-ion battery cathode - Kun Luo; Ming Chen; Mengdan Tian; Wenhui Li; Yang Jiang; Zhihao Yuan (Chemical Engineering Journal, 2023)

Rapid room-temperature polymerization strategy to prepare organic/inorganic hybrid conductive organohydrogel for terahertz wave responsiveness - Haihan Zou; Peng Yi; Wenbin Xu; He Cai; Junzhe He; Xin Sun; Xufeng Li; Chunyan Chen; Gao Deng; Yingbo Yuan; Zhenyang Li; Ming Fang; et al. (Chemical Engineering Journal, 2023)

Targeting Senescent Tendon Stem/Progenitor Cells to Prevent or Treat Age-Related Tendon Disorders - Hao Wang; Guang-Chun Dai; Ying-Juan Li; Min-Hao Chen; Pan-Pan Lu; Yuan-Wei Zhang; Ming -Zhang; Mu-Min Cao; Yun-Feng Rui (Stem Cell Reviews and Reports, 2023)

Enzyme-trigger ratiometric fluorescent nanoplatform for diagnosis and imaging of oral diseases - Ming Bi; Yong Li; Pinyi Ma; Yijun Li; Xiaowen Yuan; Hui Han (Analytica Chimica Acta, 2023)

Real-World Underwater Image Enhancement Based on Attention U-Net - Pengfei Tang; Liangliang Li; Yuan Xue; Ming Lv; Zhenhong Jia; Hongbing Ma (Journal of Marine Science and Engineering, 2023)
In recent years, with the increasingly serious problems of resource shortage and environmental pollution, the exploration and development of underwater clean energy were particularly important. At the same time, abundant underwater resources and species have attracted a large number of scientists to carry out research on underwater-related tasks. Due to the diversity and complexity of underwater environments, it is difficult to perform related vision tasks, such as underwater target detection and capture. The development of digital image technology has been relatively mature, and it has been applied in many fields and achieved remarkable results, but the research on underwater image processing technology is rarely effective. The underwater environment is much more complicated than that on land, and there is no light source underwater. Underwater imaging systems must rely on artificial light sources for illumination. When light travels through water, it is severely attenuated by water absorption, reflection, and scattering. The collected underwater images inevitably have problems such as limited visible range, blur, low contrast, uneven illumination, incoherent colors, and noise. The purpose of image enhancement is to improve or solve one or more of the above problems in a targeted manner. Therefore, underwater image enhancement technology has become one of the key contents of underwater image processing technology research. In this paper, we proposed a conditional generative adversarial network model based on attention U-Net which contains an attention gate mechanism that could filter invalid feature information and capture contour, local texture, and style information effectively. Furthermore, we formulate an objective function through three different loss functions, which can evaluate image quality from global content, color, and structural information. Finally, we performed end-to-end training on the UIEB real-world underwater image dataset. The comparison experiments show that our method outperforms all comparative methods, the ablation experiments show that the loss function proposed in this paper outperforms a single loss function, and finally, the generalizability of our method is verified by executing on two different datasets, UIEB and EUVP.

Reduced plastic film mulching under zero tillage boosts water use efficiency and soil health in semiarid rainfed maize field - Ai-Tian Ren; Ji-Yuan Li; Ling Zhao; Rui Zhou; Jian-Sheng Ye; Yi-Bo Wang; Xu-Cheng Zhang; Kiprotich Wesly; Ming-Sheng Ma; You-Cai Xiong (Resources, Conservation and Recycling, 2023)

Early Neoproterozoic well-preserved stromatolites from southern Liaoning, North China: characteristics and paleogeographic implications - Yong-Li Zhang; Guan-Ming Lai; En-Pu Gong; Mark A. Wilson; Wen-Tao Huang; Chang-Qing Guan; Ding-Cheng Yuan (Palaeoworld, 2023)

Effect of a novel catalyst zonal coating strategy on the performance of SCR coated particulate filters - Pi-qiang Tan; Li-shuang Duan; Yang Liu; Ying-jie Chen; Di-ming Lou; Zhi-yuan Hu (Fuel, 2023)

Genome-wide transcriptome analysis uncovers gene networks regulating fruit quality and volatile compounds in mango cultivar 'Tainong' during postharvest - Li Li; Ping Yi; Jian Sun; Jie Tang; Guoming Liu; Jinfeng Bi; Jianwen Teng; Meijiao Hu; Fang Yuan; Xuemei He; Jinfeng Sheng; Ming Xin; et al. (Food Research International, 2023)

Flexible nitrogen-doped carbon nanofiber-reinforced hierarchical hollow iron oxide nanorods as a binder-free electrode for efficient capacitive deionization - Ming Gao; Jiaxin Li; Yuan Wang; Wencui Liang; Zhiqian Yang; Yi Chen; Wenyang Deng; Zhen Wang; Tianqi Ao; Wenqing Chen (Desalination, 2023)

A novel Stauntonia leucantha fruits arabinogalactan: isolation and structural characterization - Hui Li; Tao Gao; Zhonghao Zhang; Jiangping Lei; Junchao Hu; Zizhong Tang; Shiling Feng; Chunbang Ding; Tao Chen; Yanger Chen; Shu Yuan; Ming Yuan (Carbohydrate Polymers, 2023)

Application value of circulating LncRNA in diagnosis, treatment, and prognosis of breast cancer - Ming Li; Yuan Zhao; Huimin Li; Xuming Deng; Miaomiao Sheng (Functional & Integrative Genomics, 2023)

Mobile Phone Imaging Point Cloud Modelling for 3D Recording and Measurement of Small Scenes of Suspected Fossil Outcrops Found in the Field - Gao Sha; Gan Shu; Yuan Xiping; Hu Lin; Bi Rui; Li Raobo; Yang Ming (Geoheritage, 2023)

Characterizing the effects of stormwater runoff on dissolved organic matter in an urban river (Jiujiang, Jiangxi province, China) using spectral analysis - Keting Yuan; Qiong Wan; Beibei Chai; Xiaohui Lei; Aiqing Kang; Jianghai Chen; Xiang Chen; Hongwei Shi; Lixin He; Ming Li (Environmental Science and Pollution Research, 2023)

Improving the genome and proteome annotations of the marine model diatom Thalassiosira pseudonana using a proteogenomics strategy - Xiao-Huang Chen; Ming-Kun Yang; Yuan-Yuan Li; Zhang-Xian Xie; Shu-Feng Zhang; Mats Töpel; Shady A. Amin; Lin Lin; Feng Ge; Da-Zhi Wang (Marine Life Science & Technology, 2023)
Diatoms are unicellular eukaryotic phytoplankton that account for approximately 20% of global carbon fixation and 40% of marine primary productivity; thus, they are essential for global carbon biogeochemical cycling and climate. The availability of ten diatom genome sequences has facilitated evolutionary, biological and ecological research over the past decade; however, a complimentary map of the diatom proteome with direct measurements of proteins and peptides is still lacking. Here, we present a proteome map of the model marine diatom Thalassiosira pseudonana using high-resolution mass spectrometry combined with a proteogenomic strategy. In-depth proteomic profiling of three different growth phases and three nutrient-deficient samples identified 9526 proteins, accounting for ~ 81% of the predicted protein-coding genes. Proteogenomic analysis identified 1235 novel genes, 975 revised genes, 104 splice variants and 234 single amino acid variants. Furthermore, our quantitative proteomic analysis experimentally demonstrated that a considerable number of novel genes were differentially translated under different nutrient conditions. These findings substantially improve the genome annotation of T. pseudonana and provide insights into new biological functions of diatoms. This relatively comprehensive diatom proteome catalog will complement available diatom genome and transcriptome data to advance biological and ecological research of marine diatoms.

Biotransformation of sulfamonomethoxine in a granular sludge system: Pathways and mechanisms - Meng-Yuan Li; Run-Dong Zhang; Yi-Xing Lin; Qi-Wen Li; Qiu-Yue Zhao; Zong-Xi Zhao; Zhong-Ming Ling; Long-Fei Shu; Min Zhang; Li-Xin Hu; Yi-Jing Shi; Guang-Guo Ying (Chemosphere, 2023)

Efficient simulation of stochastic seismic response of long-span bridges in river valleys using hybrid BEM-FEM - Zhong-xian Liu; Wen-xuan Li; Li-guo Jin; Si-bo Meng; Xiao-ming Yuan; Xing-lei Cheng; Tian-chun Ai (Soil Dynamics and Earthquake Engineering, 2023)

Distribution and drivers of antibiotic resistance genes in brackish water aquaculture sediment - Chao Li; Hao-qiang Chen; Peng Gao; Xing-hao Huang; Yun-xiang Zhu; Ming Xu; Quan Yuan; Yuan Gao; Xiao-xiao Shen (Science of The Total Environment, 2023)

Transcriptomic data recover a new superfamily-level phylogeny of Cucujiformia (Coleoptera, Polyphaga) - Ming-Long Yuan; Wen-Ting Chen; Qi-Lin Zhang; Min Li; Li Zhang; Pei-An Tang (Molecular Phylogenetics and Evolution, 2023)

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

Hierarchical ensembles of FeCo metal-organic frameworks reinforced nickel foam as an impedimetric sensor for detection of IL-1RA in human samples - Priya Vijayaraghavan; Yen-Yun Wang; Sathyadevi Palanisamy; Li-Yun Lee; Yuk-Kwan Chen; Shey-Cherng Tzou; Shyng-Shiou F. Yuan; Yun-Ming Wang (Chemical Engineering Journal, 2023)

Highly efficient polyhydroxyalkanoate production from lignin using genetically engineered Halomonas sp. Y3 - Yuan-Qiu Li; Ming-Jun Wang; Chao-Bing Luo (Bioresource Technology, 2023)

Highly efficient oriented bioconversion of food waste to lactic acid in an open system: Microbial community analysis and biological carbon fixation evaluation - Shuo Liu; Qunhui Wang; Yuan Li; Xiaoyu Ma; Wenbin Zhu; Nuohan Wang; Haishu Sun; Ming Gao (Bioresource Technology, 2023)

New (4 → 2)-abeo-clerodane diterpenoids from the Polyalthia laui and their chemotaxonomic significance - Zhang-Xin Yu; Xin-Ming Song; Mu-Yuan Li; Man-Man Zhang; Li-Zhu Huang; Xiao-Bao Li (Biochemical Systematics and Ecology, 2023)

Bibliometric Analysis of Research Trends Related to Carbon Sources for Nitrogen Removal in Wastewater Treatment - Yuan Li; Jin Ni; Feng Liu; Wenbin Zhu; Chuanfu Wu; Qunhui Wang; Ming Gao (Water, Air, & Soil Pollution, 2023)

Sodium Para-Aminosalicylic Acid Modulates Autophagy to Lessen Lead-Induced Neurodegeneration in Rat Cortex - Lei-lei Wang; Xiao-juan Zhu; Yuan-yuan Fang; Yan Li; Yue-song Zhao; Cui-liu Gan; Jing-jing Luo; Shi-yan Ou; Michael Aschner; Yue-ming Jiang (Neurotoxicity Research, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

Huntingtin-associated protein 1 is a potential tumor suppressor for gastric cancer - Ye-Min Qu; Ai Chen; Xue Zhao; Zan Wang; Dong Guo; Shu-Li Shao; Yuan-Yong Tao; Qiu-Jing Li; Ming-Yi Wang; Wan-Shan Ma (Molecular Biology Reports, 2023)

Comparative analysis of cold-responsive genes under short-term cold stimulation and cold-adaptive genes under long-term heterogeneous environments reveals a cold adaptation mechanism in weeping forsythia - Yong Li; Shu-Chen Wang; Qian Li; Ming-Wan Li; Run-Li Mao; He-Chen Zhang; Wang-Jun Yuan; Jine Quan (Genetica, 2023)

Development of an interpretable machine learning model associated with heavy metals’ exposure to identify coronary heart disease among US adults via SHAP: Findings of the US NHANES from 2003 to 2018 - Xi Li; Yang Zhao; Dongdong Zhang; Lei Kuang; Hao Huang; Weiling Chen; Xueru Fu; Yuying Wu; Tianze Li; Jinli Zhang; Lijun Yuan; Huifang Hu; et al. (Chemosphere, 2023)

Multiple drought indices and their teleconnections with ENSO in various spatiotemporal scales over the Mekong River Basin - Thi-Thu-Ha Nguyen; Ming-Hsu Li; Tue Minh Vu; Pei-Yuan Chen (Science of The Total Environment, 2023)

PGC-1α/NRF1-dependent cardiac mitochondrial biogenesis: A druggable pathway of calycosin against triptolide cardiotoxicity - Xiao-Ming Qi; Yuan-Biao Qiao; Yuan-Lin Zhang; Ai-Cheng Wang; Jin-Hong Ren; Hui-Zhi Wei; Qing-Shan Li (Food and Chemical Toxicology, 2023)

Improving ignition and combustion performance of Al@Ni in CMDB Propellants: Effect of nickel coating - Jiankan Zhang; Fengqi Zhao; Hui Li; Zhifeng Yuan; Ming Zhang; Yanjing Yang; Qing Pei; Ying Wang; Xueli Chen; Zhao Qin (Chemical Engineering Journal, 2023)

Melt-stretched poly(vinylidene fluoride)/zinc oxide nanocomposite films with enhanced piezoelectricity by stress concentrations in piezoelectric domains for wearable electronics - Ming Yuan; Ruixue Ma; Qiuyang Ye; Xue Bai; Hanchuan Li; Feifei Yan; Chuntai Liu; Yue Ren; Zhen Wang (Chemical Engineering Journal, 2023)

Cleaner 2,3-butanediol production from unpretreated lignocellulosic biomass by a newly isolated Klebsiella pneumoniae PX14 - Yuan-Qiu Li; Ming-Jun Wang; Xiao-Feng Gan; Chao-Bing Luo (Chemical Engineering Journal, 2023)

Low concentrations of benzophenone-type UV-filters impair testis development in the amphibian Xenopus laevis - Hong-Mei Li; Ying-Chi Zhang; Yuan-Yuan Li; Qing-Qing Zhu; Jie Li; Hai-Ming Xu; Yi-Ming Xiong; Zhan-Fen Qin (Aquatic Toxicology, 2023)

Retraction Note: Knockdown of long non‑coding RNA TUG1 depresses apoptosis of hippocampal neurons in Alzheimer’s disease by elevating microRNA‑15a and repressing ROCK1 expression - Xia Li; Sheng‑Wu Wang; Xi‑Ling LI; Feng‑Yuan Yu; Hai‑Ming Cong (Inflammation Research, 2023)

Brevibacillus daliensis sp. nov., Isolated From Soil in Machangqing Nature Reserve - Shi-Qiang Ye; Jiang-Yuan Zhao; Le-Le Li; Cheng Ling; Meng-Yu Zhang; Jing Tang; Song-Guo Liang; Jian-Yu Li; Pei-Wen Yang; Jiao Xiong; Lu-Yao Feng; Zhu-Feng Shi; et al. (Current Microbiology, 2023)

Environmental impact of typical zinc smelting that implements solid waste collaborative utilization in China - Wei-Ning Liu; Yao Shi; Chen-Mu Zhang; Lang-Ming Liu; Hui-Quan Li; Bin Lu; Yuan-Bo Xie; Cai-Bei Zhuang; Tian-You Sun; Wei-Ping Liu; Xue Guan; Ying-Yan Hu (The International Journal of Life Cycle Assessment, 2022)

Therapeutic Effects of Human Pluripotent Stem Cell-Derived Mesenchymal Stem Cells on a Murine Model of Acute Type-2-Dominated Airway Inflammation - Si-Yuan Ma; Ning Zhao; Lele Cui; Ying Li; Hang Zhang; Jing Wang; Jie Pang; Ming Wang; Chengshuo Wang; Sun Ying; Zi-Bing Jin; Luo Zhang (Stem Cell Reviews and Reports, 2022)

Correction to: Involvement of regulation of the excitation:inhibition functional balance in the mPFC in the antidepressant-anxiolytic effect of YL-IPA08, a novel TSPO ligand - Jin Yuan; Jun-Qi Yao; Xin-Xin Fang; Wei Dai; Yun-Hui Wang; Li-Ming Zhang; Yun-Feng Li (Metabolic Brain Disease, 2022)

A Fundamental Role of Slope Aspect and Elevation in Controlling Diversity Patterns of Soil Bacterial Communities: Insights from an Arid-Montane Ecosystem in China - Long-Fei Chen; Jun-Qia Kong; Zhi-Bin He; Wen-Zhi Zhao; Ming-Dan Song; Yue-Mei Li; Yuan Gao; Shu-Ping Yang (Journal of Soil Science and Plant Nutrition, 2022)

Uncovering expression and functional analysis of newly discovered high-affinity K+ transporter family members from sugarcane - Hai-bin Luo; Cheng-mei Huang; Yuan-wen Wei; Hui-ming Zhu; Hui-qing Cao; Sheng-li Jiang; Zhi-nian Deng; Kai-chao Wu; Lin Xu (Journal of Plant Biochemistry and Biotechnology, 2022)

Role of carnitine in adaptation of Chromohalobacter salexigens DSM 3043 and its mutants to osmotic and temperature stress in defined medium - Xiang-Lin Meng; Xia Gao; Yuan-Ming Si; Li-Li Xu; Li-Zhong Guo; Wei-Dong Lu (Extremophiles, 2022)

Removal of Cd from contaminated farmland soil by washing with residues of traditional Chinese herbal medicine extracts - Yi Wang; Yuan Li; Shuai Yang; Qi-hao Wang; Shao-cheng Si; Han-yi Mei; Guo-ming Liu; Xiang-liang Pan; Yong-ming Luo (Environmental Science and Pollution Research, 2022)

Genetic variations in the bitter taste receptor gene TAS2R38 are related to cigarette smoking behavior in Han Chinese smokers - Fei-Yan Qi; Zhou-Hai Zhu; Meng Li; Ying Guan; Qi-Yuan Peng; She-Ming Lu; Zhi-Hua Liu; Ming-Feng Wang; Ming-Ming Miao; Zhang-Yu Chen; Xue-Mei Li; Jie Bai; et al. (Genes & Genomics, 2022)

Palmitoylation of MDH2 by ZDHHC18 activates mitochondrial respiration and accelerates ovarian cancer growth - Xuan Pei; Kai-Yue Li; Yuan Shen; Jin-Tao Li; Ming-Zhu Lei; Cai-Yun Fang; Hao-Jie Lu; Hui-Juan Yang; Wenyu Wen; Miao Yin; Jia Qu; Qun-Ying Lei (Science China Life Sciences, 2022)

Involvement of regulation of the excitation:inhibition functional balance in the mPFC in the antidepressant-anxiolytic effect of YL-IPA08, a novel TSPO ligand - Jin Yuan; Jun-Qi Yao; Xin-Xin Fang; Wei Dai; Yun-Hui Wang; Li-Ming Zhang; Yun-Feng Li (Metabolic Brain Disease, 2022)

Effect of particulate matters on inactivation of bacteriophage MS2 under irradiation above 320 nm - Xiaoxue Li; Xiaochao Bi; Xiaoyang Shi; La Rao; Ming-Lai Fu; Wenjie Sun; Baoling Yuan (Environmental Science and Pollution Research, 2022)

Construction of a target MSNs drugcarrier loaded with siRNAGLI1 and siRNASMO aim at hedgehog signal pathway and the pharmacodynamic study of drug-carriers in the treatment of leukemia stem cells - Yuan Zhang; Rui Cai; HaiJun Li; Yu Duan; Yan Zhang; Wei Jing; ShaoGang Lv; Xi Chu; Zheng Cao; Lei Yang; Liang Ming (Drug Delivery and Translational Research, 2022)

Dyella sedimenti sp. nov., Isolated from the Sediment of a Winery - Li Gao; Yuan-Dong Li; Xing-Kui Zhou; Xiu-Ming Liu; Hui-Tian Li; Wen-Jun Li; Yan-Qing Duan (Current Microbiology, 2022)

Adsorption properties and mechanism research of phosphorus with different molecular structures from aqueous solutions by La-modified biochar - Ming-yao Yuan; Shang-kai Qiu; Meng-meng Li; Yuan Li; Ji-Xiu Wang; Yuan Luo; Ke-qiang Zhang; Feng Wang (Environmental Science and Pollution Research, 2022)

Aculeaquamide A, cytotoxic paraherquamide from the marine fungus Aspergillus aculeatinus WHUF0198 - Jun Wu; Fuqian Wang; Li-Ming He; Si-Yuan Zhou; Shou-Bao Wang; Jia Jia; Kui Hong; You-Sheng Cai (Natural Product Research, 2022)

Long-term changes in zooplankton in the Changjiang estuary from the 1960s to 2020 - Ping Du; Wen-Jian Ye; Bang-Ping Deng; Ming Mao; Yuan-Li Zhu; Fang-Ping Cheng; Zhi-Bing Jiang; Lu Shou; Quan-Zhen Chen (Frontiers in Marine Science, 2022)
The Changjiang estuary (CJE) is a large estuary that is affected by multiple anthropogenic stressors and climate change. The long-term trend of zooplankton in the CJE is an important indicator of the ecological response to stressors. We applied the Mann–Kendall trend analysis and Pettitt test to detect the trend and breakpoints of the biomass of the large mesozooplankton (LMZ; 505–20 000 μm) in four seasons, abundance of main LMZ taxa in summer from the 1960s to 2020, and abundance of dominant species in summer from 2000 to 2020 in the CJE. Results showed that LMZ biomass increased significantly during spring and summer, and the breakpoints both occurred in the 1980s. After the breakpoint, the mean biomass increased from 142.88 to 429.42 mg/m 3 in spring and from 296.28 to 723.92 mg/m 3 in summer. After 2000, the abundance of Copepoda in summer increased by more than 10 times compared to the 1960s. Under the conditions of warming and increased dinoflagellate abundance in the CJE, the abundance of the warm-water and omnivorous small calanoid copepod Paracalanus aculeatus increased significantly. Meanwhile, the significant decrease in the abundance of the temperate brackish species Labidocera euchaeta was probably mainly related to warming. The rapid changes in LMZ biomass during the late 1980s and mid-1990s is probably the result of a combination of enhanced bottom–up support, reduced top–down pressure, and promotion of temperature. This study provides scientific evidence and insights into the adaptive management of the Changjiang Basin.

Insertion Speed Affects the Initial Stability of Dental Implants - Yuan-Yang Hsu; Ming-Tzu Tsai; Heng-Li Huang; Lih-Jyh Fuh; Jui-Ting Hsu (Journal of Medical and Biological Engineering, 2022)
Purpose This study investigated the effects of insertion speed of dental implants on their stability. Methods Dental implants were inserted at speeds of 4, 10, 20, and 30 rpm, respectively, into artificial bones of two different bone qualities; namely, good bone (GB) and poor bone (PB). Therefore, the four insertion speeds and two bone qualities totaled eight groups, with five specimens per group. During the insertion process, the maximum insertion torque value (ITV) was measured, along with two stability parameters: periotest value (PTV) and initial stability quotient (ISQ). Results Dental implants in the GB group exhibited better stability than those in the PB group (p < 0.001). Significant differences in ITVs were observed among the four insertion speeds in both the GB and PB groups (p = 0.004 and p = 0.034, respectively). In general, the higher the insertion speed, the lower the ITV; in particular, the ITVs for implants inserted at 4 rpm were higher than those measured at 20 and 30 rpm (p = 0.008). However, regardless of the bone quality, the PTVs did not differ significantly among the four insertion speeds (p = 0.066). In both the GB and PB groups, the ISQs differed significantly differences among the four insertion speeds (p = 0.016 and p = 0.004, respectively). Conclusion The stability parameters measured for dental implants in the GB group were all higher than those measured in the PB group. In general, a higher insertion speed resulted in a lower ITV value. The PTV did not differ significantly, while the ISQ differed significantly among the four insertion speeds.

Cohnella mopanensis sp. nov., a new Gram-negative bacterium isolated from soil in Xinping Mountain National Forest Park - Jing Tang; Jiang-Yuan Zhao; Le-Le Li; Zhang-Gui Ding; Shi-Qiang Ye; Cheng Ling; Meng-Yu Zhang; Song-Guo Liang; Jian-Yu Li; Pei-Wen Yang; Jiao Xiong; Lu-Yao Feng; et al. (Archives of Microbiology, 2022)

Correction to: Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2022)

RIG-I acts as a tumor suppressor in melanoma via regulating the activation of the MKK/p38MAPK signaling pathway - Rui Guo; Shun-Yuan Lu; Jin-Xia Ma; Qian-Lan Wang; Lu Zhang; Ling-Yun Tang; Yan Shen; Chun-Ling Shen; Jin-Jin Wang; Li-Ming Lu; Zhu-Gang Wang; Hong-Xin Zhang (Human Cell, 2022)
Studies have indicated that RIG-I may act as a tumor suppressor and participate in the tumorigenesis of some malignant diseases. However, RIG-I induces distinct cellular responses via different downstream signaling pathways depending on the cell type. To investigate the biological function and underlying molecular mechanism of RIG-I in the tumorigenesis of melanoma, we constructed RIG-I knockout, RIG-I -overexpressing B16-F10 and RIG-I knockdown A375 melanoma cell lines, and analyzed the RIG-I-mediated change in the biological behavior of tumor cells in spontaneous and poly (I:C)-induced RIG-I activation. Cell proliferation, cell cycling, apoptosis and migration were detected by CCK-8 assay, BrdU incorporation assay, Annexin V–PI staining assay and Transwell assay, respectively. In vivo tumorigenicity was evaluated by tumor xenograft growth in nude mice and subsequently by Ki67 staining and TUNEL assays. Furthermore, Western blotting was utilized to explore the underlying mechanism of RIG-I in melanoma cells. Our data showed that RIG-I promotes apoptosis and inhibits proliferation by G1 phase cell cycle arrest in the melanoma cell lines. Mechanistically, RIG-I induced the phosphorylation of p38 MAPK and MAPK kinases MKK3 and MKK4. In conclusion, the current study demonstrated that RIG-I suppressed the development of melanoma by regulating the activity of the MKK/p38 MAPK signaling pathway, which is relevant to research on novel therapeutic targets for this malignant disease.

Aquapteridospora jiangxiensis, a new aquatic hyphomycetous fungus from a freshwater habitat in China - Su-Qin Peng; Yu-Lin Liu; Jun-En Huang; Xiao-Hong Li; Xin-Yi Yan; Hai-Yan Song; Yang Gao; Zhi-Jun Zhai; Yuan-Qiu Liu; Dian-Ming Hu (Archives of Microbiology, 2022)

Diversity and Structure of Demersal Fish Community Over the Northern Slope in the South China Sea - Jun Zhang; Kui Zhang; Yan-e Jiang; Yuan-jie Li; Jiang-tao Fan; Wen-ming Yu; Zuo-zhi Chen (Frontiers in Marine Science, 2022)
Three bottom trawl surveys over the northern continental slope in the South China Sea (18°50′–20°40′N, 112°50′–115°10′E) were carried out, in June 2015, March 2017 and September 2018, to investigate species composition, biodiversity and community structure of demersal fish. Surveys in 2015, 2017 and 2018 captured 97 fish species (representing 77 genera, 52 families, 26 orders), 108 fish species (representing 84 genera, 61 families, 19 orders) and 126 fish species (representing 105 genera, 74 families, 25 orders), respectively. Three surveys captured a total of 252 fish species, representing 164 genera, 97 families, 30 orders. Perciformes dominated. Species richness in station linking shallow continental shelf with deep slope was the lowest among stations. In three surveys, 16 species occurred in the catches of three surveys, accounting for 6.35% of all species. Species replacement rate between stations showed a significant linear relationship with the depth difference and latitude difference. Margalef’s species richness index ( D ), Shannon–Weiner diversity index ( H’ ) and Pielou’s evenness index ( J’ ) among stations ranged 2.65–6.74, 1.02–4.15 and 0.28–1.14, respectively. Differences of D , H ’ and J ’ were insignificant among seasons. There were significant positive linear relations between H’ and J’ and latitude. D , H’ and J’ decreased with increasing sampling depth, however the relations were not significant. Based on multivariate statistical analysis, fish community at species level was divided into five groups with average dissimilarities of 95.69%–99.96%. In terms of genus and family, average dissimilarities among groups were more than 88.11% and 82.69%. There were significant differences in species composition between depths, but no significant differences between seasons and temperatures, as well as in genus and family composition.

Extracellular vesicles derived from human Sertoli cells: characterizations, proteomic analysis, and miRNA profiling - Xiao-Hui Tan; Sheng-Ji Gu; Wen-Jie Tian; Wen-Peng Song; Yang-Yang Gu; Yi-Ming Yuan; Xue-Song Li; Zhong-Cheng Xin; Sae Woong Kim; Rui-Li Guan; Woong Jin Bae (Molecular Biology Reports, 2022)

Correction to: Sox10 Gene Is Required for the Survival of Saccular and Utricular Hair Cells in a Porcine Model - Jing-cui Qi; Qing-qing Jiang; Long Ma; Shuo-long Yuan; Wei Sun; Li-sheng Yu; Wei-wei Guo; Shi-ming Yang (Molecular Neurobiology, 2022)

Sox10 Gene Is Required for the Survival of Saccular and Utricular Hair Cells in a Porcine Model - Jing-cui Qi; Qing-qing Jiang; Long Ma; Shuo-long Yuan; Wei Sun; Li-sheng Yu; Wei-wei Guo; Shi-ming Yang (Molecular Neurobiology, 2022)

Therapeutic Effects of Sodium Para-Aminosalicylic Acid on Cognitive Deficits and Activated ERK1/2-p90RSK/NF-κB Inflammatory Pathway in Pb-Exposed Rats - Li-li Lu; Yu-wen Zhang; Zhao-cong Li; Yuan-yuan Fang; Lei-lei Wang; Yue-song Zhao; Shao-jun Li; Shi-yan Ou; Michael Aschner; Yue-ming Jiang (Biological Trace Element Research, 2022)

Effect of Culture Period and Stocking Density on Input Demand and Scale Economies of Milkfish (Chanos chanos) Polycultures with White Shrimp (Penaeus indicus) - Wei-Tse Pai; Christian Schafferer; Jie-Min Lee; Li-Ming Ho; Yung-Hsiang Lu; Han-Chung Yang; Chun-Yuan Yeh (Fishes, 2022)
Milkfish, Chanos chanos, is one of the major inland cultured fish species in Taiwan. Variations in land resources and climate have led to the application of two distinct culture practices of milkfish polycultures with white shrimp, Penaeus indicus. This study applies a translog cost function model to analyze the production scale economy and input demand price elasticity of four milkfish polyculture systems with two different culture periods (OWC and NOWC) and two different white shrimp–milkfish fry stocking ratios (low SMR: 10–55 fry/ha; high SMR: 56–100 fry/ha). The findings show that the four milkfish polyculture systems require different operational adjustments to increase production while reducing the average culture cost. More specifically, overwinter cultures (OWC) have economies of scale. Farmers may reduce the average cost by expanding the production scale. Non-overwinter polycultures (NOWC) with high SMR are at the stage of decreasing return to scale, meaning that gains in output of milkfish cannot reduce the average cost. In terms of input factor use, farmers of OWC systems with high SMR are sensitive to fluctuations in the fry price since fry constitutes the input factor exhibiting the highest own-price elasticity. Moreover, fry and feed of OWC households with high SMR have high levels of substitutability, whereas fry and other input exhibit substitutability in OWC systems with low SMR. In NOWC farming households with high SMR, fry and capital have substitutability. It is thus recommended to modify the input factor use according to the culture mode and the white shrimp–milkfish stocking density ratio. Moreover, the study found that NOWCs have considerably higher SMR than OWCs, which may lead to a deterioration of the water quality in NOWC fishponds and lower survival rates. It is thus recommended to reduce the SMR to 31:1 to achieve economies of scale in production and increase the survival rate of milkfish and white shrimp.

Characteristics of the TDRD1 gene promoter in chickens - Xiaomin Gao; Xiaolin Sun; Pei Xu; Xiang Shi; Ming Zhang; Xia Yuan; Jingyi Jiang; Kai Jin; Qisheng Zuo; Yani Zhang; Bichun Li (Molecular Genetics and Genomics, 2022)

The Effects of Ground and Treadmill Running on Energy Metabolism and Muscle Contractile Properties: A Randomized Cross-Over Study - Yuan Zhou; Jian-gang Chen; Xiao-long Li; Xin-liang Pan; Yi-zheng Zhou; Zheng-ao Li; Zhi-cheng Liang; Jia-min Long; Ming-ze Qin; Jing Zhang; Bing Shi; Bing-jun Wan; et al. (Journal of Science in Sport and Exercise, 2022)
Purpose This study aimed to compare the effects of ground and treadmill running on energy metabolism and muscle contractile properties, providing a basis for the general public to choose running venues. Methods Ten male college students (age, 20.10 ± 1.53 years; height, 176.20 ± 5.49 cm; weight, 72.14 ± 8.25 kg; body fat percent, 12.41% ± 4.65%) were recruited in this study. Energy expenditure (EE) was measured using the accelerometer (GT9X) combined with specific estimation equations. Average heart rate (HR) was measured using a heart rate band (Polar). Muscle contractile properties were assessed by measuring muscle displacement (Dm) and contraction velocity (Vc) using tensiomyography (TMG-S1). Blood glucose (Glu) and lactate (Lac) were measured by portable devices (eB-G and Lactate Scout). The running speed was 9 km/h and the duration was 25 min. Two-way ANOVA (protocol × time) was used to analyze the effect of running protocols on energy metabolism and muscle contractile properties. Results EE of treadmill running was significantly higher than EE of ground running (protocol main effect, P < 0.001), and HR of treadmill running was significantly higher than that of ground running in the first testing time (protocol simple effect, P = 0.026; protocol × time interaction P = 0.043). The decrease in Dm of the rectus femoris after treadmill running was significantly higher than that of ground running (protocol main effect, P = 0.009). The interaction of different running protocols and testing times on Lac was significant ( P = 0.025), but all results of the simple effects analysis were not statistically significant ( P > 0.05). Conclusion Our study found a difference in energy expenditure between treadmill and ground running at 9 km/h with duration of 25 min. In addition, treadmills are more likely to cause a decrease in muscle displacement distance of the rectus femoris measured after exercise than ground running. Future studies are needed to further investigate whether the differences are induced by internal metabolism or the environmental conditions of running.

Delayed rFGF21 Administration Improves Cerebrovascular Remodeling and White Matter Repair After Focal Stroke in Diabetic Mice - Yinghua Jiang; Jinrui Han; Yadan Li; Yinga Wu; Ning Liu; Samuel X. Shi; Li Lin; Jing Yuan; Shusheng Wang; Ming-Ming Ning; Aaron S. Dumont; Xiaoying Wang (Translational Stroke Research, 2022)

Anterior Cingulate Cortex Mediates Hyperalgesia and Anxiety Induced by Chronic Pancreatitis in Rats - Dan Ren; Jia-Ni Li; Xin-Tong Qiu; Fa-Ping Wan; Zhen-Yu Wu; Bo-Yuan Fan; Ming-Ming Zhang; Tao Chen; Hui Li; Yang Bai; Yun-Qing Li (Neuroscience Bulletin, 2022)
Central sensitization is essential in maintaining chronic pain induced by chronic pancreatitis (CP), but cortical modulation of painful CP remains elusive. Here, we examined the role of the anterior cingulate cortex (ACC) in the pathogenesis of abdominal hyperalgesia in a rat model of CP induced by intraductal administration of trinitrobenzene sulfonic acid (TNBS). TNBS treatment resulted in long-term abdominal hyperalgesia and anxiety in rats. Morphological data indicated that painful CP induced a significant increase in FOS-expressing neurons in the nucleus tractus solitarii (NTS) and ACC, and some FOS-expressing neurons in the NTS projected to the ACC. In addition, a larger portion of ascending fibers from the NTS innervated pyramidal neurons, the neural subpopulation primarily expressing FOS under the condition of painful CP, rather than GABAergic neurons within the ACC. CP rats showed increased expression of vesicular glutamate transporter 1, and increased membrane trafficking and phosphorylation of the N -methyl-D-aspartate receptor (NMDAR) subunit NR2B and the α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptor (AMPAR) subunit GluR1 within the ACC. Microinjection of NMDAR and AMPAR antagonists into the ACC to block excitatory synaptic transmission significantly attenuated abdominal hyperalgesia in CP rats, which was similar to the analgesic effect of endomorphins injected into the ACC. Specifically inhibiting the excitability of ACC pyramidal cells via chemogenetics reduced both hyperalgesia and comorbid anxiety, whereas activating these neurons via optogenetics failed to aggravate hyperalgesia and anxiety in CP rats. Taken together, these findings provide neurocircuit, biochemical, and behavioral evidence for involvement of the ACC in hyperalgesia and anxiety in CP rats, as well as novel insights into the cortical modulation of painful CP, and highlights the ACC as a potential target for neuromodulatory interventions in the treatment of painful CP.

Assessing the impacts of natural disasters on rice production in Jiangxi, China - Xiao Fu; Guannan Zhao; Weicheng Wu; Bin Xu; Jie Li; Xiaoting Zhou; Xinxin Ke; Yuan Li; Wenjing Li; Cuimin Zhou; Jingheng Jiang; Ming Zhang; et al. (International Journal of Remote Sensing, 2022)

Reliability Analysis of Reinforced Slope Combining Random Forest Algorithm and Meshless SPH Algorithm - Xu Liu; Liang Li; ShangShang Wang; Fu Chen; Ming Zhai; Zhengquan Yang; Yuan Gao (Geotechnical and Geological Engineering, 2022)

Making of Massoia Lactone-Loaded and Food-Grade Nanoemulsions and Their Bioactivities against a Pathogenic Yeast - Li Yuan; Hong-Qian Zhang; Zhe Chi; Guang-Lei Liu; Zhen-Ming Chi (Journal of Marine Science and Engineering, 2022)
Nanoemulsions (NEs) have been made for improving the delivery and disperse of bioactive compounds. In this study, it was found that the best ingredients for the stable Massoia lactone-loaded and food-grade NEs making were 560.0 µL of Tween-80, 240.0 µL of Span-80 and 200.0 µL of Massoia lactone. Then, 9.0 mL of distilled water was titrated into the mixture under continuous magnetic stirring (750 rotations min−1) with about 2 drops per second for 20 min. Finally, the system was treated by ultrasonication using an ultrasonic generator (180 W and 22 KHz) for 5 min. All the prepared particles with a mean droplet diameter of 43 nm were spherical, had uniform size distribution and were equally distributed in the Massoia lactone-loaded NEs. The obtained Massoia lactone-loaded nanoemulsions (NEs) were very stable without changes of the mean droplet diameter and polydispersity indexes (PDI) for over two months under different conditions. As with free Massoia lactone, Massoia lactone loaded in the NEs had high anti-fungal activity against Metschnikowia bicuspidate LIAO, a pathogenic yeast causing milky disease in the Chinese mitten crab by damaging its cell membrane and causing cellular necrosis. Massoia lactone loaded in the NEs also had the DPPH radical scavenging activity and the hydroxyl radical scavenging activity.

The antioxidant activities of flavonoids in Jerusalem artichoke ( Helianthus tuberosus L.) leaves and their quantitative analysis - Ming-Yang Wang; Zhi-Li Ma; Cheng-Li He; Xiao-Yan Yuan (Natural Product Research, 2022)

Petrogenesis of the Late Triassic Mengsong strongly peraluminous granites in the southeastern Tibetan Plateau: highly fractionated from crystal mush - Feng Cong; Fu-Yuan Wu; Wen-Chang Li; De-Feng He; Zai-Bo Sun; Xiao-Ming Huang; Zhi-Zhong Hu; Han Zhao (International Geology Review, 2022)

A new indole alkaloid from the stems of Glycosmis puberula var . craibii - Qi Zhou; Chun-Xiao Jiang; Shou-Yuan Wu; Zi-Ming Chen; Li-Ping Huang (Natural Product Research, 2022)

Viridibacillus soli sp. nov., isolated from forest soil in Ailaoshan National Nature Reserve - Yan Xu; Jiang-Yuan Zhao; Yu Geng; Hui-Ren Yuan; Le-Le Li; Meng-Liang Wen; Ming-Gang Li; Shu-Kun Tang (Archives of Microbiology, 2022)

Propioniciclava soli sp. nov., isolated from forest soil, Yunnan, China, and reclassification of the genus Brevilactibacter into the genus Propioniciclava, and Brevilactibacter sinopodophylli, Brevilactibacter flavus, and Brevilactibacter coleopterorum as Propioniciclava sinopodophylli comb. nov., Propioniciclava flava comb. nov., and Propioniciclava coleopterorum comb. nov., respectively - Le-Le Li; Jiang-Yuan Zhao; Yu Geng; Yu-Guang Zhou; Hui-Ren Yuan; Man Cai; Meng-Liang Wen; Ming-Gang Li; Shu-Kun Tang (Archives of Microbiology, 2022)

The Key Regulator of Necroptosis, RIP1 Kinase, Contributes to the Formation of Astrogliosis and Glial Scar in Ischemic Stroke - Yong-Ming Zhu; Liang Lin; Chao Wei; Yi Guo; Yuan Qin; Zhong-Sheng Li; Thomas A. Kent; Claire E. McCoy; Zhan-Xiang Wang; Yong Ni; Xian-Yong Zhou; Hui-Ling Zhang (Translational Stroke Research, 2021)
Necroptosis initiation relies on the receptor-interacting protein 1 kinase (RIP1K). We recently reported that genetic and pharmacological inhibition of RIP1K produces protection against ischemic stroke-induced astrocytic injury. However, the role of RIP1K in ischemic stroke-induced formation of astrogliosis and glial scar remains unknown. Here, in a transient middle cerebral artery occlusion (tMCAO) rat model and an oxygen and glucose deprivation and reoxygenation (OGD/Re)-induced astrocytic injury model, we show that RIP1K was significantly elevated in the reactive astrocytes. Knockdown of RIP1K or delayed administration of RIP1K inhibitor Nec-1 down-regulated the glial scar markers, improved ischemic stroke-induced necrotic morphology and neurologic deficits, and reduced the volume of brain atrophy. Moreover, knockdown of RIP1K attenuated astrocytic cell death and proliferation and promoted neuronal axonal generation in a neuron and astrocyte co-culture system. Both vascular endothelial growth factor D (VEGF-D) and its receptor VEGFR-3 were elevated in the reactive astrocytes; simultaneously, VEGF-D was increased in the medium of astrocytes exposed to OGD/Re. Knockdown of RIP1K down-regulated VEGF-D gene and protein levels in the reactive astrocytes. Treatment with 400 ng/ml recombinant VEGF-D induced the formation of glial scar; conversely, the inhibitor of VEGFR-3 suppressed OGD/Re-induced glial scar formation. RIP3K and MLKL may be involved in glial scar formation. Taken together, these results suggest that RIP1K participates in the formation of astrogliosis and glial scar via impairment of normal astrocyte responses and enhancing the astrocytic VEGF-D/VEGFR-3 signaling pathways. Inhibition of RIP1K promotes the brain functional recovery partially via suppressing the formation of astrogliosis and glial scar. Graphical Abstract

Economic Evaluation of Water-Saving Irrigation Practices for Sustainable Sugarcane Production in Guangxi Province, China - Shan-Shan He; Yuan Zeng; Zhao-Xu Liang; Yan Jing; ShiYun Tang; Baoqing Zhang; Haifeng Yan; Song Li; Tinglin Xie; Fang Tan; Ming Li (Sugar Tech, 2021)

Effective Thermal Conductivity Estimation of Fractured Rock Masses - Zheng-Wei Li; Yuan Liu; Shi-Ming Mei; Shi-Cheng Xing; Xiao-Kai Wang (Rock Mechanics and Rock Engineering, 2021)

Organic Acid Excretion in Root Exudates as a Mechanism of Cadmium Uptake in a Sonchus Asper–Zea Mays Intercropping System - Li Qin; Zuran Li; Bo Li; Jixiu Wang; Yanqun Zu; Ming Jiang; Yuan Li (Bulletin of Environmental Contamination and Toxicology, 2021)

Evaluation of four artificial diets on demography parameters of Neoseiulus barkeri - Ya-Ying Li; Jin-Ge Yuan; Ming-Xiu Liu; Zi-Hui Zhang; Hai-Wei Zhou; Huai Liu (BioControl, 2021)

Supply‐controlled calcium carbonate dissolution decouples the seasonal dissolved oxygen and pH minima in Chesapeake Bay - Jianzhong Su; Wei‐Jun Cai; Jeremy M. Testa; Jean R. Brodeur; Baoshan Chen; K. Michael Scaboo; Ming Li; Chunqi Shen; Margaret Dolan; Yuan‐Yuan Xu; Yafeng Zhang; Najid Hussain (Limnology and Oceanography, 2021)
Acidification can present a stress on organisms and habitats in estuaries in addition to hypoxia. Although oxygen and pH decreases are generally coupled due to aerobic respiration, pH dynamics may be more complex given the multiple modes of buffering in the carbonate system. We studied the seasonal cycle of dissolved oxygen (DO), pH, dissolved inorganic carbon, total alkalinity, and calcium ion (Ca 2+ ) along the main channel of Chesapeake Bay from May to October in 2016. Contrary to the expected co‐occurrence of seasonal DO and pH declines in subsurface water, we found that the pH decline ended in June while the DO decline continued until August in mid‐Chesapeake Bay. We discovered that aerobic respiration was strong from May to August, but carbonate dissolution was minor in May and June and became substantial in August, which buffered further pH declines and caused the seasonal DO and pH minima mismatch. The rate of calcium carbonate (CaCO 3 ) dissolution was not primarily controlled by the saturation state in bottom water, but was instead likely controlled by the supply of CaCO 3 particles. The seasonal variability of Ca 2+ addition in the mid‐bay was connected to Ca 2+ removal in the upper bay, and the timing of high carbonate dissolution coincided with peak seasonal biomass of upper Bay submerged aquatic vegetation. This study suggests a mechanism for a novel decoupling of DO and pH in estuarine waters associated with CaCO 3 , but future studies are needed to fully investigate the seasonality of physical transport and cycling of CaCO 3 .

Cross‐phytogroup assessment of foliar epiphytic mycobiomes - Ting Zhu; Jia Yao; Hao Liu; Chen‐Hao Zhou; Yuan‐Zhan Liu; Zheng‐Wei Wang; Zhe‐Xue Quan; Bo Li; Ji Yang; Wei‐Chang Huang; Ming Nie (Environmental Microbiology, 2021)
Summary The foliar surface forms one of the largest aboveground habitats on Earth and maintains plant‐fungus relationships that greatly affect ecosystem functioning. Despite many studies with particular plant species, the foliar epiphytic mycobiome has not been studied across a large number of plant species from different taxa. Using high‐throughput sequencing, we assessed epiphytic mycobiomes on leaf surfaces of 592 plant species in a botanical garden. Plants of angiosperms, gymnosperms, and pteridophytes were involved. Plant taxonomy, leaf side, growing environment, and evolutionary relationships were considered. We found that pteridophytes showed the higher fungal species diversity, stronger mutualistic fungal interactions, and a greater percentage of putative pathogens than gymnosperms and angiosperms. Plant taxonomic group, leaf side, and growing environment were significantly associated with the foliar epiphytic mycobiome, but the similarity of the mycobiomes among plants was not directly related to the distance of the host evolutionary tree. Our results provide a general understanding of the foliar fungal mycobiomes from pteridophytes to angiosperms. These findings will facilitate our understanding of foliar fungal epiphytes and their roles in plant communities and ecosystems.

Identification of a recessive gene YrZ15-1370 conferring adult plant resistance to stripe rust in wheat-Triticum boeoticum introgression line - Minghu Zhang; Xin Liu; Ting Peng; Dinghao Wang; Dongyu Liang; Hongyu Li; Ming Hao; Shunzong Ning; Zhongwei Yuan; Bo Jiang; Xuejiao Chen; Xue Chen; et al. (Theoretical and Applied Genetics, 2021)

Chronic AdipoRon Treatment Mimics the Effects of Physical Exercise on Restoring Hippocampal Neuroplasticity in Diabetic Mice - Thomas H Lee; Ahadullah; Brian R Christie; Kangguang Lin; Parco Ming-fai Siu; Li Zhang; Ti-fei Yuan; Pragya Komal; Aimin Xu; Kwok-fai So; Suk-yu Yau (Molecular Neurobiology, 2021)
Administration of exercise mimetic drugs could be a novel therapeutic approach to combat comorbid neurodegeneration and metabolic syndromes. Adiponectin is an adipocyte-secreted hormone. In addition to its antidiabetic effect, adiponectin mediates the antidepressant effect of physical exercise associated with adult hippocampal neurogenesis. The antidiabetic effect of the adiponectin receptor agonist AdipoRon has been demonstrated, but its potential pro-cognitive and neurotrophic effects in the hippocampus under diabetic condition are still unclear. This study reported that chronic AdipoRon treatment for 2 weeks improved hippocampal-dependent spatial recognition memory in streptozotocin-induced diabetic mice. Besides, AdipoRon treatment increased progenitor cell proliferation and neuronal differentiation in the hippocampal dentate gyrus (DG) of diabetic mice. Furthermore, AdipoRon treatment significantly increased dendritic complexity, spine density, and N -methyl-D-aspartate receptor-dependent long-term potentiation (LTP) in the dentate region, and increased BDNF levels in the DG of diabetic mice. AdipoRon treatment activated AMPK/PGC-1α signalling in the DG, whereas increases in cell proliferation and LTP were not observed when PGC-1α signalling was pharmacologically inhibited. In sum, chronic AdipoRon treatment partially mimics the benefits of physical exercise for learning and memory and hippocampal neuroplasticity in the diabetic brain. The results suggested that AdipoRon could be a potential physical exercise mimetic to improve hippocampal plasticity and hence rescue learning and memory impairment typically associated with diabetes.

Dynamic mechanical behavior and damage constitutive model of shales with different bedding under compressive impact loading - Xueru Fan; Ning Luo; Yishuo Yuan; Hanliang Liang; Cheng Zhai; Zhe Qu; Ming Li (Arabian Journal of Geosciences, 2021)

Pinocembrin-7-Methylether Protects SH-SY5Y Cells Against 6-Hydroxydopamine-Induced Neurotoxicity via Modulating Nrf2 Induction Through AKT and ERK Pathways - Zhi-Cong Zou; Ji-Jun Fu; Yuan-Ye Dang; Qian Zhang; Xiu-Fen Wang; Han-Bin Chen; Xue-Jing Jia; Simon Ming-Yuen Lee; Chu-Wen Li (Neurotoxicity Research, 2021)

Spontaneous thought-related network connectivity predicts sertraline effect on major depressive disorder - Li-Ming Hsu; Timothy Joseph Lane; Changwei W. Wu; Chien-Yuan Lin; Chi-Bin Yeh; Hung-Wen Kao; Ching-Po Lin (Brain Imaging and Behavior, 2021)

The developmental regulator PatD modulates assembly of the cell‐division protein FtsZ in the cyanobacterium Anabaena sp. PCC 7120 - Li Wang; Tian‐Cai Niu; Ana Valladares; Gui‐Ming Lin; Ju‐Yuan Zhang; Antonia Herrero; Wen‐Li Chen; Cheng‐Cai Zhang (Environmental Microbiology, 2021)
Summary FtsZ is a tubulin‐like GTPase that polymerizes to initiate the process of cell division in bacteria. Heterocysts are terminally differentiated cells of filamentous cyanobacteria that have lost the capacity for cell division and in which the ftsZ gene is downregulated. However, mechanisms of FtsZ regulation during heterocyst differentiation have been scarcely investigated. The patD gene is NtcA dependent and involved in the optimization of heterocyst frequency in Anabaena sp. PCC 7120. Here, we report that the inactivation of patD caused the formation of multiple FtsZ‐rings in vegetative cells, cell enlargement, and the retention of peptidoglycan synthesis activity in heterocysts, whereas its ectopic expression resulted in aberrant FtsZ polymerization and cell division. PatD interacted with FtsZ, increased FtsZ precipitation in sedimentation assays, and promoted the formation of thick straight FtsZ bundles that differ from the toroidal aggregates formed by FtsZ alone. These results suggest that in the differentiating heterocysts, PatD interferes with the assembly of FtsZ. We propose that in Anabaena FtsZ is a bifunctional protein involved in both vegetative cell division and regulation of heterocyst differentiation. In the differentiating cells PatD‐FtsZ interactions appear to set an FtsZ activity that is insufficient for cell division but optimal to foster differentiation.

Multi-generational effects of simulated herbivory and habitat types on the invasive weed Alternanthera philoxeroides: implications for biological control - Yongge Yuan; Sumin Guo; Ming Yan; Junmin Li (Biological Invasions, 2021)

Aestuariimicrobium ganziense sp. nov., a new Gram-positive bacterium isolated from soil in the Ganzi Tibetan autonomous prefecture, China - Yu Geng; Jiang-Yuan Zhao; Hui-Ren Yuan; Le-Le Li; Meng-Liang Wen; Ming-Gang Li; Shu-Kun Tang (Archives of Microbiology, 2021)

Chthonobacter rhizosphaerae sp. nov., a bacterium isolated from rhizosphere soil of Citrus sinenesis - Xiu-Ming Liu; Xing-Kui Zhou; Yuan-Dong Li; Ju-Xing Jiang; Li-Min Dong; Bao-Zhu Fang; Wen-Jun Li; Yan-Qing Duan (Archives of Microbiology, 2021)

Different posterior hippocampus and default mode network modulation in young APOE ε4 carriers: a functional connectome-informed phenotype longitudinal study - Li Juan Zheng; Li Lin; U. Joseph Schoepf; Akos Varga-Szemes; Rock H. Savage; Han Zhang; Yun Fei Wang; Xin Yuan Zhang; Song Luo; Ya Liu; Gui Fen Yang; Guang Ming Lu; et al. (Molecular Neurobiology, 2021)

Overexpression of T-type calcium channel Cav3.1 in oral squamous cell carcinoma: association with proliferation and anti-apoptotic activity - Rui-Fang Li; Qi-Wen Man; Jin-Yuan Liu; Yue-Yu Zheng; Xin Gao; Hai-Ming Liu (Journal of Molecular Histology, 2021)

Molecular Imaging for Radiolabeling a PSMA-Targeted Long Circulating Peptide as a Theranostic Agent in Mice Bearing a Human Prostate Tumor - Ming-Hsin Li; Sheng-Nan Lo; Ming-Wei Chen; Wei-Lin Lo; Yuan-Ruei Huang; Shih-Ying Lee; Su-Jung Chen; Shih-Wei Lo; Shih-Ming Wang; Chih-Hsien Chang (Journal of Medical and Biological Engineering, 2021)

Synthesis and antitumor evaluation of (aryl)methyl-amine derivatives of dehydroabietic acid-based B ring-fused-thiazole as potential PI3K/AKT/mTOR signaling pathway inhibitors - Nai-Yuan Chen; Yu-Lan Xie; Guo-Dong Lu; Fang Ye; Xin-Yu Li; Yu-Wen Huang; Ming-Li Huang; Tie-Yu Chen; Cui-Ping Li (Molecular Diversity, 2021)

The optimal number of embryo cells for effective pregnancy and decrease of multiple pregnancy rate in frozen-thawed embryo transfer - Xu-Li Zhu; Zhi-Ming Zhao; Yuan-Jie Du; Liang Zhou; Yue Wang; Qing-Yun Sun; Gui-Min Hao; Bu-Lang Gao (Human Cell, 2021)

Photocatalytic optical fibers for degradation of organic pollutants in wastewater: a review - Yongwu Wu; Lanlan Zhong; Jilin Yuan; Wenhao Xiang; Xin Xin; Huimin Liu; Hongyang Luo; Linyang Li; Ming Chen; Dengjie Zhong; Xinghong Zhang; Nianbing Zhong; et al. (Environmental Chemistry Letters, 2021)

The changes of brain functional networks in young adult smokers based on independent component analysis - XianFu Wang; Ting Xue; Fang Dong; Yangding Li; Dongdong Xie; Chang Liu; Ming Zhang; Yanzhi Bi; Kai Yuan; Dahua Yu (Brain Imaging and Behavior, 2021)

A novel Schiff base cobalt(III) complex induces a synergistic effect on cervical cancer cells by arresting early apoptosis stage - Wen-Hui Liao; Xue-Qing Song; Yan-Jie Kong; Rui-Dan Bao; Fang-Fang Li; Jie Zhou; Qi-Hua Zhao; Jing-Yuan Xu; Ni Xie; Ming-Jin Xie (BioMetals, 2021)

Effects of habitat fragmentation on the demography of the critically endangered tree Pterospermum kingtungense (Sterculiaceae) in Yunnan, China - Chun-Ming Yuan; Shan-Shan Zhang; Guo-Ping Yang; Jian Chen; Yun-Fen Geng; Xiao-Shuang Li; Wen-Zhong Yang (Tropical Ecology, 2021)

Association of FMO3 rs1736557 polymorphism with clopidogrel response in Chinese patients with coronary artery disease - Kong-Xiang Zhu; Pei-Yuan Song; He-Li; Mu-Peng Li; Yin-xiao Du; Qi-lin Ma; Li-Ming Peng; Xiao-Ping Chen (European Journal of Clinical Pharmacology, 2021)

Serotype Distribution and Characteristics of the Minimum Inhibitory Concentrations of Streptococcus pneumoniae Isolated from Pediatric Patients in Kunming, China - Mingbiao Ma; Mei Yuan; Ming Li; Xiaojuan Li; Hailin Huang; Haiping Wang; Jue Li; Tingyi Du; Rongwei Huang (Current Microbiology, 2021)
Streptococcus pneumoniae ( S. pneumoniae ) is the main conditional pathogen of acute respiratory infection in infants, children, and older adults worldwide. It was great significant to identify the epidemic characteristics of serotypes and antibiotic susceptibility for the prevention and treatment of S. pneumoniae diseases. This research assessed the serotype distribution and the minimum inhibitory concentrations (MICs) of S. pneumoniae isolated from pediatric patients to provide information on the epidemiology and antibiotic resistance of S. pneumoniae in Kunming, China. A total of 140 S. pneumoniae isolates were collected from pediatric patients at Kunming Children’s Hospital from January 2016 to October 2017. Serotype identification was done by Quellung reaction and multiplex polymerase chain reaction. MICs were determined by E -test. 140 isolates distributed in 13 types of serotypes. The top-three prevalent serotypes were 19F, 19A, and 6B. The immunization coverage rate of 13-valent pneumococcal conjugate vaccine (PCV) was relatively higher and should be introduced into the vaccination program in the region. MIC 50 of penicillin, ceftriaxone, and levofloxacin was 1 μg/mL. MIC 50 for meropenem and vancomycin was 0.38 μg/mL. MIC 90 of penicillin, ceftriaxone, and levofloxacin was 1.5 μg/mL and that of meropenem and vancomycin was 0.5 μg/mL. The MIC 90 of erythromycin was > 256 μg/mL. In summary, S. pneumoniae had low resistance rates to penicillin, ceftriaxone, levofloxacin, vancomycin, and meropenem, and these antibiotics could be the first-line agents for children with pneumococcal infections in Kunming.

Pseudomonas laoshanensis sp. nov., isolated from peanut field soil - Ming-Qing Wang; Chu-Shu Zhang; Li-Na Yu; Wei-Qiang Yang; Kun Jiao; Kui-Jie Gong; Xiao-Yuan Chi; Jie Bi; Yu Song; Qing-Li Yang; Jian-Cheng Zhang; Gui-Wen Yang; et al. (Archives of Microbiology, 2021)

Noroleanane-type triterpenoids from Dolichos trilobus L. and their anti-α-glucosidase activities - Ming Luo; Yan-Hong Li; Ya Lu; Yan Yuan; Rong-Sheng Ruan; Yong-Ming Chuan; Kai Tian; Xiang-Zhong Huang (Natural Product Research, 2021)

Task-related functional magnetic resonance imaging-based neuronavigation for the treatment of depression by individualized repetitive transcranial magnetic stimulation of the visual cortex - Zhijun Zhang; Hongxing Zhang; Chun-Ming Xie; Meng Zhang; Yachen Shi; Ruize Song; Xiang Lu; Haisan Zhang; Kun Li; Bi Wang; Yongfeng Yang; Xianrui Li; et al. (Science China Life Sciences, 2021)

KASP markers to detect sub-chromosomal arm translocations between 6VS of Haynaldia villosa and 6AS of wheat - Shujie Zhang; Chaolan Fan; Jiangtao Luo; Lei Huang; Die Xie; Yazhou Li; Zhuo Chen; Bo Jiang; Shunzong Ning; Zhongwei Yuan; Lin Huang; Lianquan Zhang; et al. (Euphytica, 2021)

Superoxide dismutase 3 as an inflammatory suppressor in A549 cells infected with Mycoplasma pneumoniae - Jia-Yuan Jin; Ye Chen; Xing-You Wang; Chen-Ming Li; Wei-Lin Chen; Li Li (Journal of Biosciences, 2020)

Enrichment of cadmium in rice (Oryza sativa L.) grown under different exogenous pollution sources - Yi-Min Zhou; Si-Si Long; Bing-Yu Li; Ya-Yuan Huang; Yong-Jie Li; Jia-Yan Yu; Hui-Hui Du; Sardar Khan; Ming Lei (Environmental Science and Pollution Research, 2020)

Gut dysbiosis-influence on amygdala-based functional activity in patients with end stage renal disease: a preliminary study - Li Juan Zheng; Li Lin; Jianhui Zhong; Zhihong Zhang; Yu Bing Ye; Xin Yuan Zhang; Yun Fei Wang; Han Zhang; Ya Liu; Guang Ming Lu; Dehua Gong; Long Jiang Zhang (Brain Imaging and Behavior, 2020)

Effects of the Lower Airway Secretions on Airway Opening Pressures and Suction Pressures in Critically Ill COVID-19 Patients: A Computational Simulation - Zhenglong Chen; Ming Zhong; Li Jiang; Nanshan Chen; Shengjin Tu; Yuan Wei; Ling Sang; Xia Zheng; Chunyuan Zhang; Jiale Tao; Linhong Deng; Yuanlin Song (Annals of Biomedical Engineering, 2020)

Adaptive transgenerational effects remain significant - Yuan‐Ye Zhang; Junjie Yin; Ming Zhou; Zeru Lin; Qingshun Q. Li (Ecology Letters, 2020)
The comment by Sánchez‐Tójar et al . (2020, Ecol Lett) questioned the methodology, transparency and conclusion of our study (Ecol Lett, 22, 2019, 1976). The comment has overlooked important evolutionary assumptions in their reanalysis, and the issues raised were in fact dealt with through the peer‐review process. Far from being biased, the key conclusion of our meta‐analysis still stands; transgenerational effects are largely adaptive.

Isolation and characterization of 20 polymorphic microsatellites loci for Xenocypris davidi based on high-throughput sequencing - Aihuan Guo; Julin Yuan; Qingping Lian; Ming Li; Zhimin Gu (Molecular Biology Reports, 2020)

Effects of biochar properties on the bioremediation of the petroleum-contaminated soil from a shale-gas field - Hong-Yang Ren; Zi-Jing Wei; Yan Wang; Yuan-Peng Deng; Ming-Yu Li; Bing Wang (Environmental Science and Pollution Research, 2020)

Cloning and Characterization of a Ginsenoside-Hydrolyzing α-L-Arabinofuranosidase, CaAraf51, From Cellulosimicrobium aquatile Lyp51 - Sha-Sha Zuo; Yu-Chen Wang; Ling Zhu; Jiang-Yuan Zhao; Ming-Gang Li; Xiu-Lin Han; Meng-Liang Wen (Current Microbiology, 2020)

Small RNA profiling reveal regulation of microRNAs in field peanut pod rot pathogen infection - Mian Wang; Chao-xin Zhang; Li-juan Pan; Tong Wang; Na Chen; Ming-na Chen; Zhen Yang; Xin-gang Guo; Shan-lin Yu; Xiao-yuan Chi (Biologia, 2020)

RETRACTED ARTICLE: Knockdown of long non-coding RNA TUG1 depresses apoptosis of hippocampal neurons in Alzheimer’s disease by elevating microRNA-15a and repressing ROCK1 expression - Xia Li; Sheng-Wu Wang; Xi-Ling LI; Feng-Yuan Yu; Hai-Ming Cong (Inflammation Research, 2020)

Privet golden leaves adapt unexpectedly well to light changes - Ming Yuan; Bo Huang; Li-Hua Dong; Qiao-Hong Han; Yong Yang; Chun-Bang Ding; Chao Hu; Yang-Er Chen; Zhong-Wei Zhang; Shu Yuan (Horticulture, Environment, and Biotechnology, 2020)

Fe and Cu co-doped graphitic carbon nitride as an eco-friendly photo-assisted catalyst for aniline degradation - Li Li; Ming Liang; Jun Huang; Sai Zhang; Yuan Liu; Fangyun Li (Environmental Science and Pollution Research, 2020)

Single-cell transcriptome analysis of the novel coronavirus (SARS-CoV-2) associated gene ACE2 expression in normal and non-obstructive azoospermia (NOA) human male testes - Xixi Liu; Yidong Chen; Wenhao Tang; Li Zhang; Wei Chen; Zhiqiang Yan; Peng Yuan; Ming Yang; Siming Kong; Liying Yan; Jie Qiao (Science China Life Sciences, 2020)

The trichome-specific acetolactate synthase NtALS1 gene, is involved in acylsugar biosynthesis in tobacco (Nicotiana tabacum L.) - Ai-Xia Chang; Biao Chen; Ai-Guo Yang; Ri-Sheng Hu; Quan-Fu Feng; Ming Chen; Xiao-Ning Yang; Cheng-Gang Luo; Yang-Yang Li; Yuan-Ying Wang (Planta, 2020)

Astrocytic GABAB Receptors in Mouse Hippocampus Control Responses to Behavioral Challenges through Astrocytic BDNF - Ji-Hong Liu; Ze-Lin Li; Yi-Si Liu; Huai-De Chu; Neng-Yuan Hu; Ding-Yu Wu; Lang Huang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2020)

MicroRNA-153-3p enhances the sensitivity of chronic myeloid leukemia cells to imatinib by inhibiting B-cell lymphoma-2-mediated autophagy - Yu-Ling Li; Jia-Ming Tang; Xiao-Yun Chen; Bing Luo; Guo-Hua Liang; Qian Qu; Zi-Yuan Lu (Human Cell, 2020)

Materials and Microenvironments for Engineering the Intestinal Epithelium - Jessica Snyder; Chia-Ming Wang; An Qi Zhang; Yuan Li; Joshua Luchan; Sanjin Hosic; Ryan Koppes; Rebecca Lyn Carrier; Abigail Koppes (Annals of Biomedical Engineering, 2020)

Comparative transcriptomic analysis of fireflies (Coleoptera: Lampyridae) to explore the molecular adaptations to fresh water - Qi‐Lin Zhang; Hong‐Wei Li; Zhi‐Xiang Dong; Xiao‐Jie Yang; Lian‐Bing Lin; Jun‐Yuan Chen; Ming‐Long Yuan (Molecular Ecology, 2020)
Aquatic insects are well adapted to freshwater environments, but the molecular basis of these adaptations remains largely unknown. Most firefly species (Coleoptera: Lampyridae) are terrestrial, but the larvae of several species are aquatic. Here, larval and adult transcriptomes from Aquatica leii (freshwater) and Lychnuris praetexta (terrestrial) were generated to test whether the genes associated with metabolic efficiency and morphology have undergone adaptive evolution to fresh water. The aquatic fireflies had a significantly lower ratio of nonsynonymous to synonymous substitutions than the terrestrial insects, indicating a genomewide evolutionary constraint in the aquatic fireflies. We identified 341 fast‐evolving genes and 116 positively selected genes in the aquatic fireflies. Of these, 76 genes exhibiting both fast evolution and positive selection were primarily involved in ATP production, energy metabolism and the hypoxia response. We identified 7,271 differentially expressed genes (DEGs) in A . leii (adults versus larvae) and 8,309 DEGs in L . praetexta (adults versus larvae). DEGs specific to the aquatic firefly ( n = 1,445) were screened via interspecific comparisons ( A . leii versus L . praetexta ) and were significantly enriched for genes involved in metabolic efficiency (e.g., ATP production, hypoxia, and immune responses) and certain aspects of morphology (e.g., cuticle chitin, tracheal and compound eye morphology). These results indicate that sequence and expression‐level changes in genes associated with both metabolic efficiency and morphological attributes related to the freshwater lifestyle contributed to freshwater adaptation in fireflies. This study provides new insights into the molecular mechanisms of aquatic adaptation in insects.

Design, synthesis and cholinesterase inhibitory activity of α -mangostin derivatives - Xiao-Qian Chi; Bo Hou; Liu Yang; Cheng-Ting Zi; Yong-Feng Lv; Jin-Yu Li; Fu-Cai Ren; Ming-Yan Yuan; Jiang-Miao Hu; Jun Zhou (Natural Product Research, 2020)

Expression Patterns of Inducible Cre Recombinase Driven by Differential Astrocyte-Specific Promoters in Transgenic Mouse Lines - Neng-Yuan Hu; Ya-Ting Chen; Qian Wang; Wei Jie; Yi-Si Liu; Qiang-Long You; Ze-Lin Li; Xiao-Wen Li; Sophie Reibel; Frank W. Pfrieger; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2020)

Primary percutaneous coronary intervention in a COVID-19 patient with ST-segment elevation myocardial infarction after lung transplantation: a case report - Tian-ming Xuan; Xing-xiang Wang; Xiang-yuan Pu; Wei-li Han; Xiao-gang Guo (Journal of Zhejiang University-SCIENCE B, 2020)

Phylogenetic patterns of shrub communities along the longitudinal and latitudinal gradients on the northeastern Qinghai–Tibetan Plateau - Yuan-ming Xiao; Lu-cun Yang; Xiu-qing Nie; Chang-bin Li; Feng Xiong; Guo-ying Zhou (Journal of Mountain Science, 2020)

SP94 Peptide-Functionalized PEG-PLGA Nanoparticle Loading with Cryptotanshinone for Targeting Therapy of Hepatocellular Carcinoma - Xiaoling Nie; Yuan Liu; Ming Li; Xuesong Yu; Wanwen Yuan; Sixi Huang; Di Ren; Ying Wang; Yan Wang (AAPS PharmSciTech, 2020)

AAV/BBB-Mediated Gene Transfer of CHIP Attenuates Brain Injury Following Experimental Intracerebral Hemorrhage - Shuo Zhang; Zheng-wei Hu; Hai-yang Luo; Cheng-yuan Mao; Mi-bo Tang; Yu-sheng Li; Bo Song; Yao-he Wang; Zhong-xian Zhang; Qi-meng Zhang; Li-yuan Fan; Yao Zhang; et al. (Translational Stroke Research, 2020)

Molecular characterization of soil organic carbon in water-stable aggregate fractions during the early pedogenesis from parent material of Mollisols - Na Li; Jinghong Long; Xiaozeng Han; Yaru Yuan; Ming Sheng (Journal of Soils and Sediments, 2020)

Involvement of the JNK signaling in granular corneal dystrophy by modulating TGF-β-induced TGFBI expression and corneal fibroblast apoptosis - Danyao Nie; Xinhua Liu; Yuan Wang; Wenling He; Ming Li; Yun Peng; Jing Zhang; Liangnan Sun; Zonghui Yan; Lin Ye (In Vitro Cellular & Developmental Biology - Animal, 2020)

Phosphate-modified ferric-based material remediates lead and arsenic co-contaminated soil and enhances maize seedling growth - Yining Yuan; Ming Lu; Naimei Tu; Yaoyao Li (Environmental Science and Pollution Research, 2020)

Spatial distribution characteristics of bacterial community structure and gene abundance in sediments of the Bohai Sea - Quanrui Chen; Jingfeng Fan; Jie Su; Hongxia Ming; Zhihao Sun; Mengfei Li; Xiaohui Zhao; Yantao Wang; Yingxue Zhang; Huizhen Zhang; Yuan Jin; Xiaowan Ma; et al. (Acta Oceanologica Sinica, 2020)

Comprehensive strength deterioration model of compacted loess exposed to drying-wetting cycles - Chang-ming Hu; Yi-li Yuan; Yuan Mei; Xue-yan Wang; Zheng Liu (Bulletin of Engineering Geology and the Environment, 2020)

Microlunatus speluncae sp. nov., a novel actinobacterium isolated from a Karstic subterranean environment sample - Yuan-Guo Xie; Bao-Zhu Fang; Ming-Xian Han; Lan Liu; Jian-Yu Jiao; Xiao-Tong Zhang; Min Xiao; Wen-Jun Li (Antonie van Leeuwenhoek, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Carbamazepine promotes specific stimuli-induced NLRP3 inflammasome activation and causes idiosyncratic liver injury in mice - Zhilei Wang; Guang Xu; Xiaoyan Zhan; Youping Liu; Yuan Gao; Nian Chen; Yuming Guo; Ruisheng Li; Tingting He; Xueai Song; Ming Niu; Jiabo Wang; et al. (Archives of Toxicology, 2019)

A novel one-step quantitative reverse transcription PCR assay for selective amplification of hepatitis B virus pregenomic RNA from a mixture of HBV DNA and RNA in serum - Ming Gao; Chengqian Feng; Ruosu Ying; Yuan Nie; Xizi Deng; Ying Zhu; Xiaoping Tang; Yujuan Guan; Fengyu Hu; Feng Li (Archives of Virology, 2019)

Transgenerational effects benefit offspring across diverse environments: a meta‐analysis in plants and animals - Junjie Yin; Ming Zhou; Zeru Lin; Qingshun Q. Li; Yuan‐Ye Zhang (Ecology Letters, 2019)
The adaptive value of transgenerational effects (the ancestor environmental effects on offspring) in changing environments has received much attention in recent years, but the related empirical evidence remains equivocal. Here, we conducted a meta‐analysis summarising 139 experimental studies in plants and animals with 1170 effect sizes to investigate the generality of transgenerational effects across taxa, traits, and environmental contexts. It was found that transgenerational effects generally enhanced offspring performance in response to both stressful and benign conditions. The strongest effects are in annual plants and invertebrates, whereas vertebrates appear to benefit mostly under benign conditions, and perennial plants show hardly any transgenerational responses at all. These differences among taxonomic/life‐history groups possibly reflect that vertebrates can avoid stressful conditions through their mobility, and longer‐lived plants have alternative strategies. In addition to environmental contexts and taxonomic/life‐history groups, transgenerational effects also varied among traits and developmental stages of ancestors and offspring, but the effects were similarly strong across three generations of offspring. By way of a more comprehensive data set and a different effect size, our results differ from those of a recent meta‐analysis, suggesting that transgenerational effects are widespread, strong and persistent and can substantially impact the responses of plants and animals to changing environments.

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Moss patch size and microhabitats influence stoichiometry of moss crusts in a temperate desert, Central Asia - Yong-Gang Li; Xiao-Bing Zhou; Yuan-Ming Zhang (Plant and Soil, 2019)

Recycled oceanic crust in the form of pyroxenite contributing to the Cenozoic continental basalts in central Asia: new perspectives from olivine chemistry and whole-rock B–Mo isotopes - Yunying Zhang; Chao Yuan; Min Sun; Ming Chen; Lubing Hong; Jie Li; Xiaoping Long; Pengfei Li; Zhengfan Lin (Contributions to Mineralogy and Petrology, 2019)

Assessing the influence of the minimum measured diameter on forest spatial patterns and nearest neighborhood relationships - Yuan-fa Li; Hai-peng Yang; Hong-xiang Wang; Shao-ming Ye; Wen-zhen Liu (Journal of Mountain Science, 2019)

Ottowia flava sp. nov., isolated from fish intestines - Song-Biao Shi; Gui-Ding Li; Li-Fang Yang; Cong Liu; Ming-Guo Jiang; Qin-Yuan Li; Jia-Fa Wu; Kun Zhang; Long-Qian Jiang; Nai-Kun Shen; Cheng-Lin Jiang; Yi Jiang (Antonie van Leeuwenhoek, 2019)

The Microwave-Induced Fracturing of Hard Rock - Gao-Ming Lu; Xia-Ting Feng; Yuan-Hui Li; Xiwei Zhang (Rock Mechanics and Rock Engineering, 2019)

Paeoniflorin attenuates impairment of spatial learning and hippocampal long-term potentiation in mice subjected to chronic unpredictable mild stress - Si-Cheng Liu; Wei-Yan Hu; Wei-Yuan Zhang; Lu Yang; Yan Li; Zhi-Cheng Xiao; Ming Zhang; Zhi-Yong He (Psychopharmacology, 2019)

MdHIR4 transcription and translation levels associated with disease in apple are regulated by MdWRKY31 - Xian-Yan Zhao; Chen-Hui Qi; Han Jiang; Ming-Shuang Zhong; Chun-Xiang You; Yuan-Yuan Li; Yu-Jin Hao (Plant Molecular Biology, 2019)

Modification of the gravity increase method in slope stability analysis - Chang-ming Hu; Yi-li Yuan; Yuan Mei; Xue-yan Wang; Zheng Liu (Bulletin of Engineering Geology and the Environment, 2019)

Experimental investigation on the mechanical characteristics of gas-bearing coal considering the impact of moisture - Ming-yi Chen; Yuan-ping Cheng; Jing-chun Wang; Hao-ran Li; Ning Wang (Arabian Journal of Geosciences, 2019)

A breeding strategy targeting the secondary gene pool of bread wheat: introgression from a synthetic hexaploid wheat - Ming Hao; Lianquan Zhang; Laibin Zhao; Shoufen Dai; Aili Li; Wuyun Yang; Die Xie; Qingcheng Li; Shunzong Ning; Zehong Yan; Bihua Wu; Xiujin Lan; et al. (Theoretical and Applied Genetics, 2019)

Experimental Investigation on the Effects of Microwave Treatment on Basalt Heating, Mechanical Strength, and Fragmentation - Gao-Ming Lu; Xia-Ting Feng; Yuan-Hui Li; Ferri Hassani; Xiwei Zhang (Rock Mechanics and Rock Engineering, 2019)

A new pregnane steroid from cultures of Aspergillus versicolor - Jian-Hai Ding; Zhang-Gui Ding; Jiang-Yuan Zhao; Ming-Gang Li; Dong-Bao Hu; Xian-Jun Jiang; Dong-Sheng Zhou; Fei Wang; Meng-Liang Wen (Natural Product Research, 2019)

Genetic mapping of a major QTL promoting homoeologous chromosome pairing in a wheat landrace - Chaolan Fan; Jiangtao Luo; Shujie Zhang; Meng Liu; Qingcheng Li; Yazhou Li; Lei Huang; Xuejiao Chen; Shunzong Ning; Zhongwei Yuan; Lianquan Zhang; Jirui Wang; et al. (Theoretical and Applied Genetics, 2019)

Evaluation of the integrated multi-satellite retrievals for global precipitation measurement over the Tibetan Plateau - Lu Ma; Lin Zhao; Li-ming Tian; Li-ming Yuan; Yao Xiao; Le-le Zhang; De-fu Zou; Yong-ping Qiao (Journal of Mountain Science, 2019)

Benthic foraminiferal fauna and sediment provenance of Eocene syn-rift sequences in Taiwan: implication for onset of Asian epi-continental marginal seas off China coast - Chi-Yue Huang; Lei Shao; Ming-Huei Wang; Wei-Guang Xue; Pei-Jun Qiao; Yu-Chi Cui; Yuan-Li Hou (Marine Geophysical Research, 2019)

Identification of duplicated Cited3 genes and their responses to hypoxic stress in blunt snout bream (Megalobrama amblycephala) - Hong-Hong Guo; Yuan Sun; Xue-li Zhang; Xia-Yun Jiang; Shu-Ming Zou (Fish Physiology and Biochemistry, 2019)

Nocardioides speluncae sp. nov., a novel actinobacterium isolated from a karstic subterranean environment sample - Bao-Zhu Fang; Ming-Xian Han; Jian-Yu Jiao; Xiao-Tong Zhang; Yuan-Guo Xie; Wael N. Hozzein; Dalal Hussien M. Alkhalifah; Min Xiao; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Zircon U–Pb ages and Hf isotopic compositions of two types of supracrustal rocks in the Northeastern Sulu UHP terrane: constraints on the surface boundary between South China and North China - Yang Xu; Ming-Ling Yang; Ali Polat; Kun-Guang Yang; Yuan-Ku Meng; Ri-Hui Li; Zhong-Bo Wang (International Geology Review, 2019)

Field experiment on the effects of sepiolite and biochar on the remediation of Cd- and Pb-polluted farmlands around a Pb–Zn mine in Yunnan Province, China - Fangdong Zhan; Wenzeng Zeng; Xingchao Yuan; Bo Li; Tianguo Li; Yanqun Zu; Ming Jiang; Yuan Li (Environmental Science and Pollution Research, 2019)

Influence of rock fractures on the amplitude of dipole-source reflected shear wave - Hao Wang; Ning Li; Cai-Zhi Wang; Hong-Liang Wu; Peng Liu; Yu-Sheng Li; Ying-Ming Liu; Ye Yuan (Applied Geophysics, 2019)

Provenance of the Langjiexue Group to the south of the Yarlung-Tsangpo Suture Zone in southeastern Tibet: Insights on the evolution of the Neo-Tethys Ocean in the Late Triassic - Da-Ren Fang; Gen-Hou Wang; Ken-ichiro Hisada; Guo-Li Yuan; Fang-Lin Han; Dian Li; Yu Tang; Qiu-Ming Pei; Liang-Liang Zhang (International Geology Review, 2019)

Thermal dynamics of the permafrost active layer under increased precipitation at the Qinghai-Tibet Plateau - De-sheng Li; Zhi Wen; Qian-gong Cheng; Ai-guo Xing; Ming-li Zhang; An-yuan Li (Journal of Mountain Science, 2019)

A new cyclohexenone from the tin mine tailings-derived fungus Aspergillus flavus YIM DT 10012 - Wei-Xun Chunyu; Jiang-Yuan Zhao; Zhang-Gui Ding; Xiu-Lin Han; Yong-Xia Wang; Jian-Hai Ding; Fei Wang; Ming-Gang Li; Meng-Liang Wen (Natural Product Research, 2019)

The life cycle and development characteristics of Dermacentor everestianus (Acari: Ixodidae) under field conditions in Qinghai–Tibet Plateau - Tuo Li; Ming Liu; Tian-Tian Zhang; Yuan Li; Wen-Ying Wang; Meng-Meng Li; Zhi-Jun Yu; Jing-Ze Liu (Experimental and Applied Acarology, 2018)

Identification of the complete mitochondrial genome of Garra pingi pingi (Cypriniformes, Cyprinidae) - Yuan-Chao Zou; Mei Chen; Chuan-Jie Qin; Yong-Ming Wang; Rui Li; Ze-Min Qi; Zheng-Yong Wen (Conservation Genetics Resources, 2018)

Genome-wide identification and characterization of ALTERNATIVE OXIDASE genes and their response under abiotic stresses in Camellia sinensis (L.) O. Kuntze - Chang-Qing Ding; Sophia Ng; Lu Wang; Yu-Chun Wang; Na-Na Li; Xin-Yuan Hao; Jian-Ming Zeng; Xin-Chao Wang; Ya-Jun Yang (Planta, 2018)

A novel phenylspirodrimane dimer from cultures of the fungus Stachybotrys chartarum - Zhang-Gui Ding; Jiang-Yuan Zhao; Jian-Hai Ding; Wei-Xun Chunyu; Ming-Gang Li; Shao-Jie Gu; Fei Wang; Meng-Liang Wen (Natural Product Research, 2018)

Sex Differences in Neuropathology and Cognitive Behavior in APP/PS1/tau Triple-Transgenic Mouse Model of Alzheimer’s Disease - Jun-Ting Yang; Zhao-Jun Wang; Hong-Yan Cai; Li Yuan; Meng-Ming Hu; Mei-Na Wu; Jin-Shun Qi (Neuroscience Bulletin, 2018)

Serum Copper Homeostasis in Hypertensive Intracerebral Hemorrhage and its Clinical Significance - Ming Han; Shan Ding; Yuan Zhang; Zhexuan Lin; Kangsheng Li (Biological Trace Element Research, 2018)

Molecular cytogenetic identification of newly synthetic Triticum kiharae with high resistance to stripe rust - Xiaojuan Liu; Minghu Zhang; Xin Liu; Hongyu Li; Ming Hao; Shunzong Ning; Zhongwei Yuan; Dengcai Liu; Bihua Wu; Xuejiao Chen; Wenjie Chen; Lianquan Zhang (Genetic Resources and Crop Evolution, 2018)

Endophytic Fungal strains Specifically Modified the Biochemical Status of Grape Cells - Ming-Zhi Yang; Li-Hua Huang; Xiu-Jin Ao; An-Yun Ren; Ming-Quan Yuan; Han-Bo Zhang (Journal of Plant Biology, 2018)

BDNF/TrkB Pathway Mediates the Antidepressant-Like Role of H2S in CUMS-Exposed Rats by Inhibition of Hippocampal ER Stress - Le Wei; Li-Yuan Kan; Hai-Ying Zeng; Yi-Yun Tang; Hong-Lin Huang; Ming Xie; Wei Zou; Chun-Yan Wang; Ping Zhang; Xiao-Qing Tang (NeuroMolecular Medicine, 2018)

Social Isolation During Adolescence Induces Anxiety Behaviors and Enhances Firing Activity in BLA Pyramidal Neurons via mGluR5 Upregulation - Song Lin; Xin Li; Yi-Hua Chen; Feng Gao; Hao Chen; Neng-Yuan Hu; Lang Huang; Zheng-Yi Luo; Ji-Hong Liu; Qiang-Long You; Ya-Nan Yin; Ze-Lin Li; et al. (Molecular Neurobiology, 2018)

Integrated analysis of transcriptomic and metabolomic data reveals critical metabolic pathways involved in rotenoid biosynthesis in the medicinal plant Mirabilis himalaica - Li Gu; Zhong-yi Zhang; Hong Quan; Ming-jie Li; Fang-yu Zhao; Yuan-jiang Xu; Jiang Liu; Man Sai; Wei-lie Zheng; Xiao-zhong Lan (Molecular Genetics and Genomics, 2018)

A pair of new moisture-dynamic diagnostic parameters for heavy rain location - Kai Yuan; Zhiwei Zhu; Ming Li (Meteorology and Atmospheric Physics, 2018)

Early warning model for slope debris flow initiation - Ming-li Li; Yuan-jun Jiang; Tao Yang; Qiang-bing Huang; Jian-ping Qiao; Zong-ji Yang (Journal of Mountain Science, 2018)

Magnetic nanoparticles based cancer therapy: current status and applications - Huan Zhang; Xiao Li Liu; Yi Fan Zhang; Fei Gao; Ga Long Li; Yuan He; Ming Li Peng; Hai Ming Fan (Science China Life Sciences, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

The pre‐rRNA processing factor Nop53 regulates fungal development and pathogenesis via mediating production of reactive oxygen species - Sheng‐Nan Cao; Ye Yuan; Yu (Haity) Qin; Ming‐Zhe Zhang; Paul de Figueiredo; Gui‐Hua Li; Qing‐Ming Qin (Environmental Microbiology, 2018)
Summary Botrytis cinerea is a necrotrophic plant fungal pathogen that annually causes enormous economic losses worldwide. The ribosome is an organelle for cellular protein biosynthesis. However, little is known about how the ribosome operates as a machine to mediate microbial pathogenesis. Here, we demonstrate that Nop53, a late‐acting factor for 60S ribosomal subunit maturation, is crucial for the pathogen's development and virulence. BcNop53 is functionally equivalent to yeast nop53p. Complementation of BcNOP53 completely restored the growth defect of the yeast Δ nop53 mutant. BcNop53 is located in nuclei and disruption of BcNOP53 also dramatically impaired pathogen growth. Deletion of BcNOP53 blocked infection structure formation and abolished virulence of the pathogen, possibly due to reduced production of reactive oxygen species. Moreover, loss of BcNOP53 impaired pathogen conidiation and stress adaptation, altered conidial and sclerotial morphology, retarded conidium and sclerotium germination as well as reduced the activities of cell‐wall degradation‐associated enzymes. Sclerotium production was, however, increased. Complementation with the wild‐type BcNOP53 allele rescued defects found in the Δ Bcnop53 mutant. Our work establishes a systematic elucidation of Nop53 in regulating microbial development and pathogenesis, provides novel insights into ribosomal processes that regulate fungal pathogenesis, and may open up new targets for addressing fungal diseases.

The influence of soil properties and geographical distance on the bacterial community compositions of paddy soils enriched on SMFC anodes - Hai-Yan Yuan; Pan-Pan Liu; Ning Wang; Xiao-Ming Li; Yong-Guan Zhu; Shams Tabrez Khan; Abdulaziz A. Alkhedhairy; Guo-Xin Sun (Journal of Soils and Sediments, 2018)

Spatial trends and pollution assessment for mercury in the surface soils of the Nansi Lake catchment, China - Ming-Yi Ren; Li-Yuan Yang; Long-Feng Wang; Xue-mei Han; Jie-Rui Dai; Xu-Gui Pang (Environmental Science and Pollution Research, 2018)

Erratum to: Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2017)

Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2017)

The novel ethylene-responsive factor CsERF025 affects the development of fruit bending in cucumber - Chunhua Wang; Ming Xin; Xiuyan Zhou; Chunhong Liu; Shengnan Li; Dong Liu; Yuan Xu; Zhiwei Qin (Plant Molecular Biology, 2017)

Testing of antiviral characteristics of flammutoxin in transgenic tobacco - Li-Ping Wu; Xue-Ling Gao; Yuan-Dan Duan; Ye-Yu Bian; Tao Yang; Ming-Jia Fu (Journal of Plant Diseases and Protection, 2017)

Secretory expression of a novel human spermatozoa antigen in E. coli and its application to a protein chip - Ming-zhu Wang; Zhuo-lin Qiu; Xiang-Sheng Cai; Jing-jing Li; Miao-qin She; Yuan-feng Xu; Ying-song Wu (Biotechnology Letters, 2017)

Resveratrol Inhibits Diabetic-Induced Müller Cells Apoptosis through MicroRNA-29b/Specificity Protein 1 Pathway - Kaihong Zeng; Yuan Wang; Na Yang; Duozi Wang; Suping Li; Jian Ming; Jing Wang; Xuemei Yu; Yi Song; Xue Zhou; Bo Deng; Xiaona Wu; et al. (Molecular Neurobiology, 2017)

Down-Regulation of Neuregulin1/ErbB4 Signaling in the Hippocampus Is Critical for Learning and Memory - Jia Tian; Fei Geng; Feng Gao; Yi-Hua Chen; Ji-Hong Liu; Jian-Lin Wu; Yu-Jie Lan; Yuan-Ning Zeng; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Molecular Neurobiology, 2017)

Two new diketopiperazines from the tin mine tailings-derived fungus Schizophyllum commune YIM DT 10058 - Wei-Xun Chunyu; Zhang-Gui Ding; Jiang-Yuan Zhao; Yong-Xia Wang; Xiu-Lin Han; Ming-Gang Li; Meng-Liang Wen (Natural Product Research, 2017)

The complete mitochondrial genome of a threatened loach (Sinibotia reevesae) and its phylogeny - Yuan-Chao Zou; Bi-Wen Xie; Chuan-Jie Qin; Yong-Ming Wang; Deng-Yue Yuan; Rui Li; Zheng-Yong Wen (Genes & Genomics, 2017)

Zircon U–Pb dating of eclogite from the Qiangtang terrane, north-central Tibet: a case of metamorphic zircon with magmatic geochemical features - Qing-guo Zhai; Bor-ming Jahn; Xian-hua Li; Ru-yuan Zhang; Qiu-li Li; Ya-nan Yang; Jun Wang; Tong Liu; Pei-yuan Hu; Suo-han Tang (International Journal of Earth Sciences, 2017)

A new cycloartane-type triterpenoid from the roots of Dianella ensifolia (L.) DC - Ben-Qin Tang; Chu-Wen Li; Jian-Bo Sun; Yu Chang; Judy Yuet-Wa Chan; Simon Ming-Yuan Lee; Bao Zeng (Natural Product Research, 2017)

Overexpression of a chrysanthemum transcription factor gene DgNAC1 improves the salinity tolerance in chrysanthemum - Ke Wang; Ming Zhong; Yin-huan Wu; Zhen-yu Bai; Qian-yu Liang; Qing-lin Liu; Yuan-zhi Pan; Lei Zhang; Bei-bei Jiang; Yin Jia; Guang-li Liu (Plant Cell Reports, 2017)

Land use legacies and nitrogen fertilization affect methane emissions in the early years of rice field development - Rui Shao; Ming Xu; Renqiang Li; Xiaoqin Dai; Lixiang Liu; Ye Yuan; Huimin Wang; Fengting Yang (Nutrient Cycling in Agroecosystems, 2017)

Sodium P-Aminosalicylic Acid Improved Manganese-Induced Learning and Memory Dysfunction via Restoring the Ultrastructural Alterations and γ-Aminobutyric Acid Metabolism Imbalance in the Basal Ganglia - Chao-Yan Ou; Yi-Ni Luo; Sheng-Nan He; Xiang-Fa Deng; Hai-Lan Luo; Zong-Xiang Yuan; Hao-Yang Meng; Yu-Huan Mo; Shao-Jun Li; Yue-Ming Jiang (Biological Trace Element Research, 2017)

Responses of Dissimilatory Nitrate Reduction to Ammonium and Denitrification to Plant Presence, Plant Species and Species Richness in Simulated Vertical Flow Constructed Wetlands - Chong-Bang Zhang; Wen-Li Liu; Wen-Juan Han; Ming Guan; Jiang Wang; Shu-Yuan Liu; Ying Ge; Jie Chang (Wetlands, 2017)

Deriving characterization factors on freshwater ecotoxicity of graphene oxide nanomaterial for life cycle impact assessment - Yelin Deng; Jianyang Li; Ming Qiu; Fan Yang; Jingyi Zhang; Chris Yuan (The International Journal of Life Cycle Assessment, 2017)

NFAT5 protects astrocytes against oxygen–glucose–serum deprivation/restoration damage via the SIRT1/Nrf2 pathway - Xun Xia; Bo Qu; Yun-Ming Li; Li-Bin Yang; Ke-Xia Fan; Hui Zheng; Hai-Dong Huang; Jian-Wen Gu; Yong-Qin Kuang; Yuan Ma (Journal of Molecular Neuroscience, 2017)

Gastroprotective effect of palmatine against acetic acid-induced gastric ulcers in rats - Ling Wang; Xue Wang; Su-Li Zhang; Xiao-Ming Zhu; Yan-Qi Liu; Zi-Jing Song; Wen-Juan Du; Jun Ji; Cheng-Long Cui; Xin He; Chun-Feng Zhang; Chang-Run Guo; et al. (Journal of Natural Medicines, 2017)

Regional efforts to mitigate climate change in China: a multi-criteria assessment approach - Zhi-Fu Mi; Yi-Ming Wei; Chen-Qi He; Hua-Nan Li; Xiao-Chen Yuan; Hua Liao (Mitigation and Adaptation Strategies for Global Change, 2017)

Olfactory Dysfunction in Parkinson’s Disease Patients with the LRRK2 G2385R Variant - Ming Cao; Zhu-Qin Gu; Yuan Li; Hui Zhang; Xiao-Juan Dan; Shan-Shan Cen; Da-Wei Li; Piu Chan (Neuroscience Bulletin, 2016)

Geographic distance and amorphous iron affect the abundance and distribution of Geobacteraceae in paddy soils in China - Hai-Yan Yuan; Long-Jun Ding; Ning Wang; Song-Can Chen; Ye Deng; Xiao-Ming Li; Yong-Guan Zhu (Journal of Soils and Sediments, 2016)

Simple Method for Fabricating Slender Infusion-Recording Assembly in 30-Gauge Syringe Needle - Wen-Yi Wu; Wei-Chen Hung; Chen-Tung Yen; Ming-Yuan Min; Meng-Li Tsai (Journal of Medical and Biological Engineering, 2016)

Improved Data Preprocessing Algorithm for Time-Domain Induced Polarization Method with Digital Notch Filter - Shuang-Chao Ge; Ming Deng; Kai Chen; Bin Li; Yuan Li (Acta Geophysica, 2016)

Citricoccus lacusdiani sp. nov., an actinobacterium promoting Microcystis growth with limited soluble phosphorus - Bing-Huo Zhang; Nimaichand Salam; Juan Cheng; Min Xiao; Han-Quan Li; Jian-Yuan Yang; Dai-Ming Zha; Wen-Jun Li (Antonie van Leeuwenhoek, 2016)

One new berberine from the branches and leaves of Polyalthia obliqua Hook.f. & Thomson - Li-Jun Wu; Cai-Juan Zheng; Liu-Kai Wang; Chang-Ri Han; Xiao-Ping Song; Guang-Ying Chen; Xue-ming Zhou; Shou-yuan Wu; Xiao-bao Li; Meng Bai; Chun-xin Liu; Jun Yao (Natural Product Research, 2016)

Goatpoxvirus ATPase activity is increased by dsDNA and decreased by zinc ion - Ming-Liang Lee; Wei-Li Hsu; Chi-Young Wang; Hui-Yu Chen; Fong-Yuan Lin; Ming-Huang Chang; Hong-You Chang; Min-Liang Wong; Kun-Wei Chan (Virus Genes, 2016)

DSePA Antagonizes High Glucose-Induced Neurotoxicity: Evidences for DNA Damage-Mediated p53 Phosphorylation and MAPKs and AKT Pathways - Kun Wang; Xiao-yan Fu; Xiao-ting Fu; Ya-jun Hou; Jie Fang; Shuai Zhang; Ming-feng Yang; Da-wei Li; Lei-lei Mao; Jing-yi Sun; Hui Yuan; Xiao-yi Yang; et al. (Molecular Neurobiology, 2016)

Meta-Analysis of the COMT Val158Met Polymorphism in Major Depressive Disorder: Effect of Ethnicity - Maiqiu Wang; Yunlong Ma; Wenji Yuan; Kunkai Su; Ming D. Li (Journal of Neuroimmune Pharmacology, 2016)

Abnormal prefrontal cortex resting state functional connectivity and severity of internet gaming disorder - Chenwang Jin; Ting Zhang; Chenxi Cai; Yanzhi Bi; Yangding Li; Dahua Yu; Ming Zhang; Kai Yuan (Brain Imaging and Behavior, 2016)

VRC01 antibody protects against vaginal and rectal transmission of human immunodeficiency virus 1 in hu-BLT mice - Ming Sun; Yue Li; Zhe Yuan; Wuxun Lu; Guobin Kang; Wenjin Fan; Qingsheng Li (Archives of Virology, 2016)

Evolution of Stress Concentration and Energy Release Before Rock Bursts: Two Case Studies from Xingan Coal mine, Hegang, China - Gui-feng Wang; Si-yuan Gong; Zhen-lei Li; Lin-ming Dou; Wu Cai; Yong Mao (Rock Mechanics and Rock Engineering, 2016)

A synthetic antimicrobial peptide BTD-S expressed in Arabidopsis thaliana confers enhanced resistance to Verticillium dahliae - Feng Li; Hao Shen; Ming Wang; Kai Fan; Noreen Bibi; Mi Ni; Shuna Yuan; Xuede Wang (Molecular Genetics and Genomics, 2016)

Lead Exposure Impairs Hippocampus Related Learning and Memory by Altering Synaptic Plasticity and Morphology During Juvenile Period - Tao Wang; Rui-Li Guan; Ming-Chao Liu; Xue-Feng Shen; Jing Yuan Chen; Ming-Gao Zhao; Wen-Jing Luo (Molecular Neurobiology, 2016)

Impact of Heat Shock Protein A 12B Overexpression on Spinal Astrocyte Survival Against Oxygen-Glucose-Serum Deprivation/Restoration in Primary Cultured Astrocytes - Xun Xia; Yuan Ma; Li-bin Yang; Jing-ming Cheng; Tao Yang; Ke-xia Fan; Yun-ming Li; En-yu Liu; Lin Cheng; Hai-dong Huang; Jian-wen Gu; Yong-qin Kuang (Journal of Molecular Neuroscience, 2016)

Rutaecarpine attenuates hypoxia-induced right ventricular remodeling in rats - Wen-Qun Li; Xiao-Hui Li; Jie Du; Wang Zhang; Dai Li; Xiao-Ming Xiong; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Salusin β Within the Nucleus Tractus Solitarii Suppresses Blood Pressure Via Inhibiting the Activities of Presympathetic Neurons in the Rostral Ventrolateral Medulla in Spontaneously Hypertensive Rats - Hong-Bao Li; Yan Lu; Jin-Jun Liu; Yu-Wang Miao; Tian-Zhen Zheng; Qing Su; Jie Qi; Hong Tan; Zu-Yi Yuan; Guo-Qing Zhu; Yu-Ming Kang (Cardiovascular Toxicology, 2016)

Enhanced butanol production from cassava with Clostridium acetobutylicum by genome shuffling - Shu-Bo Li; Yi Qian; Zheng-Wu Liang; Yuan Guo; Mou-Ming Zhao; Zong-Wen Pang (World Journal of Microbiology and Biotechnology, 2016)

Hurdles of CAR-T cell-based cancer immunotherapy directed against solid tumors - Bing-Lan Zhang; Di-Yuan Qin; Ze-Ming Mo; Yi Li; Wei Wei; Yong-Sheng Wang; Wei Wang; Yu-Quan Wei (Science China Life Sciences, 2016)

Sodium Para-aminosalicylic Acid Protected Primary Cultured Basal Ganglia Neurons of Rat from Manganese-Induced Oxidative Impairment and Changes of Amino Acid Neurotransmitters - Shao-Jun Li; Yong Li; Jing-Wen Chen; Zong-Xiang Yuan; Yu-Huan Mo; Guo-Dong Lu; Yue-Ming Jiang; Chao-Yan Ou; Fang Wang; Xiao-Wei Huang; Yi-Ni Luo; Shi-Yan Ou; et al. (Biological Trace Element Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Identification of the Avulsion-Injured Spinal Motoneurons - Min Tan; Ming-zhou Yuan; Tian-yu Sun; Ying-yu Xie; Lin-Lin Liu; Ying Tang; Ze-min Ling; Ying-qin Li; Guang-yin Yu; Li Hua Zhou (Journal of Molecular Neuroscience, 2016)

Boosting BCG-primed mice with chimeric DNA vaccine HG856A induces potent multifunctional T cell responses and enhanced protection against Mycobacterium tuberculosis - Ping Ji; Zhi-Dong Hu; Han Kang; Qin Yuan; Hui Ma; Han-li Wen; Juan Wu; Zhong-Ming Li; Douglas B. Lowrie; Xiao-Yong Fan (Immunologic Research, 2016)

Investigation of the ASR family in foxtail millet and the role of ASR1 in drought/oxidative stress tolerance - Zhi-Juan Feng; Zhao-Shi Xu; Jiutong Sun; Lian-Cheng Li; Ming Chen; Guang-Xiao Yang; Guang-Yuan He; You-Zhi Ma (Plant Cell Reports, 2016)

Contribution of Variants in CHRNA5/A3/B4 Gene Cluster on Chromosome 15 to Tobacco Smoking: From Genetic Association to Mechanism - Li Wen; Keran Jiang; Wenji Yuan; Wenyan Cui; Ming D. Li (Molecular Neurobiology, 2016)

Intranasal Delivery of Granulocyte Colony-Stimulating Factor Enhances Its Neuroprotective Effects Against Ischemic Brain Injury in Rats - Bao-liang Sun; Mei-qing He; Xiang-yu Han; Jing-yi Sun; Ming-feng Yang; Hui Yuan; Cun-dong Fan; Shuai Zhang; Lei-lei Mao; Da-wei Li; Zong-yong Zhang; Cheng-bi Zheng; et al. (Molecular Neurobiology, 2016)

Combined effect of rice genotypes and soil characteristics on iron plaque formation related to Pb uptake by rice in paddy soils - Fang-Lin Li; Ching-Ming Yang; Chien-Hui Syu; Dar-Yuan Lee; Ben-Jei Tsuang; Kai-Wei Juang (Journal of Soils and Sediments, 2016)

Advanced oxidation protein products induce chondrocyte apoptosis via receptor for advanced glycation end products-mediated, redox-dependent intrinsic apoptosis pathway - Qian Wu; Zhao-Ming Zhong; Si-Yuan Zhu; Cong-Rui Liao; Ying Pan; Ji-Huan Zeng; Shuai Zheng; Ruo-Ting Ding; Qing-Song Lin; Qing Ye; Wen-Bin Ye; Wei Li; et al. (Apoptosis, 2016)

RETRACTED ARTICLE: Relationship of Serum Heart-Type Fatty Acid-Binding Protein Levels and Cerebral Infarction: a Meta-analysis - Bao-Liang Sun; Ming-Feng Yang; Xiao-Yi Yang; Jing-Yi Sun; Da-Wei Li; Zong-Yong Zhang; Lei-Lei Mao; Cun-Dong Fan; Cheng-Bi Zheng; Hong-Li Gao; Feng-Ze Wang; Feng Zhang; et al. (Molecular Neurobiology, 2015)

Paenibacillus wenxiniae sp. nov., a nifH gene -harbouring endophytic bacterium isolated from maize - Jun-lian Gao; Fan-yang Lv; Xu-ming Wang; Tian-lei Qiu; Mei Yuan; Ji-wei Li; Yi Zhou; Jian-guang Sun (Antonie van Leeuwenhoek, 2015)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

Adenovirus-mediated osteoprotegerin ameliorates cartilage destruction by inhibiting proteoglycan loss and chondrocyte apoptosis in rats with collagen-induced arthritis - Zhi-yun Feng; Zhen-nian He; Bin Zhang; Yi-qiao Li; Jian Guo; Yuan-lin Xu; Ming-yuan Han; Zhong Chen (Cell and Tissue Research, 2015)

Identification of the Avulsion-Injured Spinal Motoneurons - Min Tan; Ming-zhou Yuan; Tian-yu Sun; Ying-yu Xie; Lin-Lin Liu; Ying Tang; Ze-min Ling; Ying-qin Li; Guang-yin Yu; Li Hua Zhou (Journal of Molecular Neuroscience, 2015)

Effect of Chinese herbal medicine on vascular functions during 60-day head-down bed rest - Ming Yuan; Asmaa Alameddine; Mickael Coupé; Nastassia M. Navasiolava; Yongzhi Li; Guillemette Gauquelin-Koch; Yanqiang Bai; Shizhong Jiang; Yumin Wan; Jingyu Wang; Yinghui Li; Marc-Antoine Custaud (European Journal of Applied Physiology, 2015)

NMDAR-Mediated Hippocampal Neuronal Death is Exacerbated by Activities of ASIC1a - Su Gao; Yang Yu; Zhi-Yuan Ma; Hui Sun; Yong-Li Zhang; Xing-Tao Wang; Chaoyun Wang; Wei-Ming Fan; Qing-Yin Zheng; Chun-Lei Ma (Neurotoxicity Research, 2015)

Bacillus methylotrophicus isolated from the cucumber rhizosphere degrades ferulic acid in soil and affects antioxidant and rhizosphere enzyme activities - Yue Zhang; Xiu-Juan Wang; Shu-Yun Chen; Li-Yuan Guo; Ming-Lei Song; He Feng; Chen Li; Ji-Gang Bai (Plant and Soil, 2015)

Cloning and functional validation of molybdenum cofactor sulfurase gene from Ammopiptanthus nanus - Hao Qiang Yu; Yuan Yuan Zhang; Tai Ming Yong; Yan Ping Liu; Shu Feng Zhou; Feng Ling Fu; Wan Chen Li (Plant Cell Reports, 2015)

Effects of the size and morphology of zinc oxide nanoparticles on the germination of Chinese cabbage seeds - Lei Xiang; Hai-Ming Zhao; Yan-Wen Li; Xian-Pei Huang; Xiao-Lian Wu; Teng Zhai; Yue Yuan; Quan-Ying Cai; Ce-Hui Mo (Environmental Science and Pollution Research, 2015)

Actinomadura amylolytica sp. nov. and Actinomadura cellulosilytica sp. nov., isolated from geothermally heated soil - Jian-Yu Jiao; Lan Liu; En-Min Zhou; Da-Qiao Wei; Hong Ming; Wen-Dong Xian; Chang-Guo Yuan; Jing-Mei Zhong; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

ERK Is Involved in the Process of Acrosome Reaction In Vitro of the Chinese Mitten Crab, Eriocheir sinensis - Wen-Juan Sun; Ming Zhu; Yuan-Li Wang; Qing Li; Hong-Dan Yang; Ze-Lin Duan; Lin He; Qun Wang (Marine Biotechnology, 2015)

Different influences of field aging on nickel toxicity to Folsomia candida in two types of soil - Yu-Rong Liu; Jing Li; Ji-Zheng He; Yi-Bing Ma; Yuan-Ming Zheng (Environmental Science and Pollution Research, 2015)

Soil pH determines the alpha diversity but not beta diversity of soil fungal community along altitude in a typical Tibetan forest ecosystem - Jun-Tao Wang; Yuan-Ming Zheng; Hang-Wei Hu; Li-Mei Zhang; Jing Li; Ji-Zheng He (Journal of Soils and Sediments, 2015)

Deletion of d-ribulose-5-phosphate 3-epimerase (RPE1) induces simultaneous utilization of xylose and glucose in xylose-utilizing Saccharomyces cerevisiae - Ming-Hua Shen; Hao Song; Bing-Zhi Li; Ying-Jin Yuan (Biotechnology Letters, 2015)

Molecular and serological evidence for Seoul virus in rats (Rattus norvegicus) in Zhangmu, Tibet, China - Tingsong Hu; Quanshui Fan; Xiaobing Hu; Bo Deng; Gang Chen; Liangqi Gu; Ming Li; Ying Zheng; Guihong Yuan; Wei Qiu; Xiaomei Jiang; Fuqiang Zhang (Archives of Virology, 2015)

Human health risk assessment of soil dioxin/furans contamination and dioxin-like activity determined by ethoxyresorufin-O-deethylase bioassay - Yu Bon Man; Ka Lai Chow; Hong Sheng Wang; Xiao Lin Sun; Sheng Chun Wu; Zong Wei Cai; Yuan Kang; Hui Li; Jin Shu Zheng; John P. Giesy; Ming Hung Wong (Environmental Science and Pollution Research, 2015)

Okibacterium endophyticum sp. nov., a novel endophytic actinobacterium isolated from roots of Salsola affinis C. A. Mey - Hong-Fei Wang; Yong-Guang Zhang; Li Li; Wei-Hong Liu; Wael N. Hozzein; Ji-Yue Chen; Jian-Wei Guo; Yuan-Ming Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Isolation and characterization of pyrroline-5-carboxylate synthetase gene from perennial ryegrass (Lolium perenne L.) - Li Cao; Lei Han; Hua-li Zhang; Hai-bo Xin; Muhammad Imtiaz; Ming-Fang Yi; Zhen-Yuan Sun; Guan-Sheng Ju; Yong-Qiang Qian; Jun-Xiang Liu (Acta Physiologiae Plantarum, 2015)

Updated Findings of the Association and Functional Studies of DRD2/ANKK1 Variants with Addictions - Yunlong Ma; Wenji Yuan; Xianzhong Jiang; Wen-Yan Cui; Ming D. Li (Molecular Neurobiology, 2015)

Comparison of chemical, electrical, and combined activation methods for in vitro matured porcine oocytes - Shuai Liu; Kuiqing Cui; Hong Li Li; Jun Ming Sun; Xing Rong Lu; Kai Yuan Shen; Qing You Liu; De Shun Shi (In Vitro Cellular & Developmental Biology - Animal, 2015)

GRP78 promotes the invasion of pancreatic cancer cells by FAK and JNK - X. P. Yuan; Ming Dong; Xin Li; J. P. Zhou (Molecular and Cellular Biochemistry, 2015)

The genus Codonopsis (Campanulaceae): a review of phytochemistry, bioactivity and quality control - Jing-Yu He; Na Ma; Shu Zhu; Katsuko Komatsu; Zhi-Yuan Li; Wei-Ming Fu (Journal of Natural Medicines, 2015)
Codonopsis , in the family Campanulaceae, is a genus containing 42 species of dicotyledonous herbaceous perennial plants, predominantly found in Central, East and South Asia. Several Codonopsis species are widely used in traditional medicine and are considered to have multiple medicinal properties. Among the Codonopsis species, Codonopsis pilosula (Franch.) Nannf. and C. lanceolata (Sieb. et Zucc.) Benth. & Hook. f. ex Trautv. are more popular than others according to the findings, especially phytochemical and bioactive studies. Phytochemical research shows that Codonopsis species contain mainly polyacetylenes, phenylpropanoids, alkaloids, triterpenoids and polysaccharides, which contribute to multiple bioactivities. However, the mechanisms of their bioactivities need to be further elucidated. The less popular Codonopsis species remain to be studied and exploited. In addition, although a series of methods for the quality evaluation of Codonopsis species have been developed, a feasible and reliable approach to the efficacious and safe use of various Codonopsis species is still needed, with considering botanical origin, chemical constituents and bioactive effects. This review aims to provide up-to-date and comprehensive information on the phytochemistry, bioactivity and quality control of medicinal plants in the genus Codonopsis and to highlight current gaps in knowledge, which is useful for the wider development of the Codonopsis genus.

Spatiotemporal Dynamics of Salt Marsh Vegetation regulated by Plant Invasion and Abiotic Processes in the Yangtze Estuary: Observations with a Modeling Approach - Zhen-Ming Ge; Li-Quan Zhang; Lin Yuan (Estuaries and Coasts, 2015)

Variovorax guangxiensis sp. nov., an aerobic, 1-aminocyclopropane-1-carboxylate deaminase producing bacterium isolated from banana rhizosphere - Jun-lian Gao; Mei Yuan; Xu-ming Wang; Tian-lei Qiu; Ji-wei Li; Hong-can Liu; Xiu-ai Li; Jian Chen; Jian-guang Sun (Antonie van Leeuwenhoek, 2015)

Labedella endophytica sp. nov., a novel endophytic actinobacterium isolated from stem of Anabasis elatior (C. A. Mey.) Schischk - Hong-Fei Wang; Yong-Guang Zhang; Juan Cheng; Wael N. Hozzein; Wei-Hong Liu; Li Li; Ji-Yue Chen; Jian-Wei Guo; Yuan-Ming Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

The evolution of permeability and gas composition during remote protective longwall mining and stress-relief gas drainage: a case study of the underground Haishiwan Coal Mine - Wei Li; Yuan-ping Cheng; Pin-kun Guo; Feng-hua An; Ming-yi Chen (Geosciences Journal, 2014)

A convenient four-component one-pot synthesis of 2-amino-1,3,4-thiadiazoles in water - Peng Liu; Ao-Ze Su; Yuan-Qiang Wang; Ze-Mei Ge; Tie-Ming Cheng; Run-Tao Li (Molecular Diversity, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

The expression profile and promoter analysis of β-N-acetylglucosaminidases in the silkworm Bombyx mori - Yuan-fen Zhai; Ming-xia Huang; Yu Wu; Guo-dong Zhao; Jie Du; Bing Li; Wei-de Shen; Zheng-guo Wei (Molecular Biology Reports, 2014)

Recycling of sediment into the mantle source of K-rich mafic rocks: Sr–Nd–Hf–O isotopic evidence from the Fushui complex in the Qinling orogen - Hao Wang; Yuan-Bao Wu; Chao-Ran Li; Tian-Yu Zhao; Zheng-Wei Qin; Liu-Qin Zhu; Shan Gao; Jian-Ping Zheng; Xiao-Ming Liu; Lian Zhou; Yang Zhang; Sai-Hong Yang (Contributions to Mineralogy and Petrology, 2014)

Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) prevents apoptosis induced by hydrogen peroxide in basilar artery smooth muscle cells - Jia-Wei Zeng; Xue-Lin Zeng; Fei-Ya Li; Ming-Ming Ma; Feng Yuan; Jie Liu; Xiao-Fei Lv; Guan-Lei Wang; Yong-Yuan Guan (Apoptosis, 2014)

Vanillin derivatives as the selective small molecule inhibitors of FtsZ - Juan Sun; Ming-Hui Li; Xin-Yi Wang; Yang Zhang; Rong-Ju Yuan; Han-Yu Liu; Hai-Liang Zhu (Medicinal Chemistry Research, 2014)

Molecular modeling studies of JNK3 inhibitors using QSAR and docking - Xiang-Xiang Wu; Da-Shun Dai; Xin Zhu; Xiao-Fei Li; Juan Yuan; Xue-Fen Wu; Ming-San Miao; Hua-Hui Zeng; Chun-Lei Zhao (Medicinal Chemistry Research, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Sensitive time-resolved fluoroimmunoassay for quantitative determination of clothianidin in agricultural samples - Ming Li; Enze Sheng; Yulong Yuan; Xiaofeng Liu; Xiude Hua; Minghua Wang (Environmental Science and Pollution Research, 2014)

Deregulation of microRNA expression in thyroid tumors - Zi-ming Yuan; Zhi-li Yang; Qi Zheng (Journal of Zhejiang University-SCIENCE B, 2014)

Stripe rust resistance and genes in Chinese wheat cultivars and breeding lines - Qing-Dong Zeng; De-Jun Han; Qi-Lin Wang; Feng-Ping Yuan; Jian-Hui Wu; Li Zhang; Xiao-Jie Wang; Li-Li Huang; Xian-Ming Chen; Zhen-Sheng Kang (Euphytica, 2014)
Stripe rust, caused by Puccinia striiformis f. sp. tritici ( Pst ), is one of the most important diseases on wheat in China. To assess resistance in wheat cultivars and breeding lines in China, 330 leading cultivars and 164 advanced breeding lines were evaluated with stripe rust. In the greenhouse tests, seedlings of the entries were inoculated separately with several Pst pathotypes. In the field tests, the entries were evaluated for stripe rust resistance in Yangling, Shaanxi Province artificially inoculated and in Tianshui, Gansu Province under natural infection of Pst . The oversummering/wintering and spring epidemic zones of resistance genes were postulated using molecular markers for Yr5 , Yr9 , Yr10 , Yr15 , Yr17 , Yr18 , and Yr26 , in combination with resistance spectra. Out of the 494 wheat entries, 16 (3.24 %) entries had all-stage resistance (ASR) in all race tests, 99 (20.04 %) had adult-plant resistance (APR), 28 (5.67 %) were considered to have slow-rusting (SR), and 351 (71.05 %) were susceptible to one or more races in both seedling and adult-plant stages. Advanced breeding lines had a higher percentage (37.2 %) of resistant entries (The sum of ASR, APR and SR) than leading cultivars (24.85 %). Among the epidemic regions, southern Gansu had a higher percentage of resistant entries than any other regions. Based on stripe rust reactions and molecular markers, two cultivars were found to possibly have Yr5 while no entries have Yr10 or Yr15 . Resistance genes Yr9 , Yr17 , Yr18 , and Yr26 were found in 134 (29.4 %), 45 (9.1 %), 10 (2 %), and 15 (3 %) entries, respectively.

Two rescue therapies in lamivudine-resistant patients with chronic hepatitis B in the central China: adefovir monotherapy and adefovir plus lamivudine - Ming Wang; Leyong Yuan; Bin Qiao; Yan Li (Virus Genes, 2014)

New briarane-type diterpenoids from gorgonian Ellisella dollfusi from the South China Sea - Yuan-Ming Zhou; Chang-Lun Shao; Hui Huang; Xiu-Li Zhang; Chang-Yun Wang (Natural Product Research, 2014)

Artificial antigen synthesis and the development of polyclonal antibody-based immunoassay for citreoviridin determination - Zhen Hong Zhuang; Shan Jin Que; Yue Ming Gao; Jun Yuan; Zhou Ye; Min Du; Guang Mei Lin; Li Cai Liu; Shi Hua Wang (World Journal of Microbiology and Biotechnology, 2014)

A novel set pair analysis method based on variable weights for liquefaction evaluation - Ming-Wu Wang; Peng Xu; Jian Li; Kui-Yuan Zhao (Natural Hazards, 2014)

Linkage between community diversity of sulfate-reducing microorganisms and methylmercury concentration in paddy soil - Yu-Rong Liu; Yuan-Ming Zheng; Li-Mei Zhang; Ji-Zheng He (Environmental Science and Pollution Research, 2014)

Molecular characterization of sawtooth oak (Quercus acutissima) germplasm based on randomly amplified polymorphic DNA - Yuan-Yan Zhang; Yan-Ming Fang; Mu-Kui Yu; Xiao-Li Zhou (Plant Systematics and Evolution, 2013)

Microbial Diversity and Succession in the Chinese Luzhou-Flavor Liquor Fermenting Cover Lees as Evaluated by SSU rRNA Profiles - Ke Li; Qing Zhang; Xiao-Ting Zhong; Bi-Hong Jia; Chun-Hong Yuan; Sen Liu; Zhen-Ming Che; Wen-Liang Xiang (Indian Journal of Microbiology, 2013)

Streptomyces fukangensis sp. nov., a novel alkaliphilic actinomycete isolated from a saline-alkaline soil - Yong-Guang Zhang; Hong-Fei Wang; Qing Liu; Wael N. Hozzein; Mohammed A. M. Wadaan; Juan Cheng; Yue-Ji Chen; Yuan-Ming Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

A Fractal-Based Model for Fracture Deformation Under Shearing and Compression - Ming-Yao Wei; Hui-Hai Liu; Lian-Chong Li; En-Yuan Wang (Rock Mechanics and Rock Engineering, 2013)

Overexpression of a novel chrysanthemum Cys2/His2-type zinc finger protein gene DgZFP3 confers drought tolerance in tobacco - Qing-Lin Liu; Ke-Dong Xu; Ming Zhong; Yuan-Zhi Pan; Bei-Bei Jiang; Guang-Li Liu; Yin Jia; Hai-Qing Zhang (Biotechnology Letters, 2013)

Structure and dynamics of the bacterial communities in fermentation of the traditional Chinese post-fermented pu-erh tea revealed by 16S rRNA gene clone library - Ming Zhao; Wei Xiao; Yan Ma; Tingting Sun; Wenxia Yuan; Na Tang; Donglian Zhang; Yongxia Wang; Yali Li; Hongjie Zhou; Xiaolong Cui (World Journal of Microbiology and Biotechnology, 2013)

Population persistence of a Tertiary relict tree Tetracentron sinense on the Ailao Mountains, Yunnan, China - Cindy Q. Tang; Ming-Chun Peng; Long-Yuan He; Masahiko Ohsawa; Chong-Yun Wang; Tian-Hua Xie; Wen-Shun Li; Jia-Ping Li; Hong-Yu Zhang; Yong Li; Xian-Ming Yang; Guo-Song Li (Journal of Plant Research, 2013)

Vulnerability of 208 endemic or endangered species in China to the effects of climate change - Xinhai Li; Huidong Tian; Yuan Wang; Renqiang Li; Zengming Song; Fengchun Zhang; Ming Xu; Dianmo Li (Regional Environmental Change, 2013)

Factors underlying the association of body mass index with serum ALT in Chinese hypertensive adults without known hepatic diseases - Yan Zhang; Xian-hui Qin; Jian-ping Li; Yi-min Cui; Ze-yuan Liu; Zhi-gang Zhao; Jun-bo Ge; De-ming Guan; Jian Hu; Yan-ni Wang; Fu-min Zhang; Xin Xu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Inhibition of hepatocellular carcinoma growth and angiogenesis by dual silencing of NET-1 and VEGF - Yuan-Yuan Wu; Li Chen; Gui-Lan Wang; Yi-Xin Zhang; Jia-Ming Zhou; Song He; Jing Qin; Yuan-Yuan Zhu (Journal of Molecular Histology, 2013)

Interactions between the P6 and P5-1 proteins of southern rice black-streaked dwarf fijivirus in yeast and plant cells - Jing Li; Jin Xue; Heng-Mu Zhang; Jian Yang; Ming-Fang Lv; Li Xie; Yuan Meng; Pei-Pei Li; Jian-Ping Chen (Archives of Virology, 2013)

Short-chain chlorinated paraffins (SCCPs) in surface soil from a background area in China: occurrence, distribution, and congener profiles - Xue-Tong Wang; Yuan Zhang; Yi Miao; Ling-Ling Ma; Yuan-Cheng Li; Yue-Ya Chang; Ming-Hong Wu (Environmental Science and Pollution Research, 2013)

Priming of Anti-Herbivore Defense in Tomato by Arbuscular Mycorrhizal Fungus and Involvement of the Jasmonate Pathway - Yuan Yuan Song; Mao Ye; Chuan You Li; Rui Long Wang; Xiao Chen Wei; Shi Ming Luo; Ren Sen Zeng (Journal of Chemical Ecology, 2013)

Sonic Hedgehog (Shh) Regulates the Expression of Angiogenic Growth Factors in Oxygen–Glucose-Deprived Astrocytes by Mediating the Nuclear Receptor NR2F2 - Yanan Li; Yuanpeng Xia; Yong Wang; Ling Mao; Yuan Gao; Quanwei He; Ming Huang; Shengcai Chen; Bo Hu (Molecular Neurobiology, 2013)

Astrocyte-Derived Sonic Hedgehog Contributes to Angiogenesis in Brain Microvascular Endothelial Cells via RhoA/ROCK Pathway After Oxygen–Glucose Deprivation - Quan-Wei He; Yuan-Peng Xia; Sheng-Cai Chen; Yong Wang; Ming Huang; Yan Huang; Jian-Yong Li; Ya-Nan Li; Yuan Gao; Ling Mao; Yuan-Wu Mei; Bo Hu (Molecular Neurobiology, 2013)

Expression of CIDE proteins in clear cell renal cell carcinoma and their prognostic significance - Ming Yu; Hui Wang; Jun Zhao; Yuan Yuan; Chao Wang; Jing Li; Lijun Zhang; Liying Zhang; Qing Li; Jing Ye (Molecular and Cellular Biochemistry, 2013)

Expression patterns of As-ClC gene of Artemia sinica in early development and under salinity stress - Qiaozhi Zhang; Ming Hou; Qiuying Li; Lulu Han; Zhe Yuan; Jian Tan; Bin Du; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2013)

TGFβ1 Treatment Reduces Hippocampal Damage, Spontaneous Recurrent Seizures, and Learning Memory Deficits in Pilocarpine-Treated Rats - Liang-Yong Li; Jia-Lin Li; Hui-Min Zhang; Wen-Ming Yang; Kai Wang; Yuan Fang; Yu Wang (Journal of Molecular Neuroscience, 2013)

Halalkalicoccus paucihalophilus sp. nov., a halophilic archaeon from Lop Nur region in Xinjiang, northwest of China - Bing-Bing Liu; Shu-Kun Tang; Yong-Guang Zhang; Xin-Hua Lu; Li Li; Juan Cheng; Yuan-Ming Zhang; Li-Li Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Halomonas nanhaiensis sp. nov., a halophilic bacterium isolated from a sediment sample from the South China Sea - Mei-Rong Long; Dao-Feng Zhang; Xin-Yi Yang; Xiao-Mei Zhang; Yong-Guang Zhang; Yuan-Ming Zhang; Honghui Zhu; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Effects of super absorbent polymers on soil microbial properties and Chinese cabbage (Brassica chinensis) growth - Xi Li; Ji-Zheng He; Yu-Rong Liu; Yuan-Ming Zheng (Journal of Soils and Sediments, 2013)

Succession of plant and soil microbial communities with restoration of abandoned land in the Loess Plateau, China - Jun-Jian Li; Yuan-Ming Zheng; Jun-Xia Yan; Hong-Jian Li; Ji-Zheng He (Journal of Soils and Sediments, 2013)

A pharmaco-fMRI study on pain networks induced by electrical stimulation after sumatriptan injection - Wang Yuan; Li Dan; Rana Netra; Ma Shaohui; Jin Chenwang; Zhang Ming (Experimental Brain Research, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Coexpression of ScNHX1 and ScVP in Transgenic Hybrids Improves Salt and Saline-Alkali Tolerance in Alfalfa (Medicago sativa L.) - Liang Liu; Xiu-Duo Fan; Fa-Wei Wang; Nan Wang; Yuan-Yuan Dong; Xiu-Ming Liu; Jing Yang; Yan-Fang Wang; Hai-Yan Li (Journal of Plant Growth Regulation, 2013)

Changes in the BAG1 Expression of Schwann Cells After Sciatic Nerve Crush - Hao Wu; Yonghua Liu; Yuan Zhou; Long Long; Xinghai Cheng; Lei Ji; Hai Weng; Tao Ding; Jiao Yang; Haixiang Wei; Ming Li; Weipeng Huan; et al. (Journal of Molecular Neuroscience, 2013)

Simulated microgravity alters the metastatic potential of a human lung adenocarcinoma cell line - De Chang; Huiwen Xu; Yinghua Guo; Xuege Jiang; Yan Liu; Kailong Li; Chunxiao Pan; Ming Yuan; Junfeng Wang; Tianzhi Li; Changting Liu (In Vitro Cellular & Developmental Biology - Animal, 2013)

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

Association of CASP9, CASP10 gene polymorphisms and tea drinking with colorectal cancer risk in the Han Chinese population - He Liu; Xia Jiang; Ming-wu Zhang; Yi-feng Pan; Yun-xian Yu; Shan-chun Zhang; Xin-yuan Ma; Qi-long Li; Kun Chen (Journal of Zhejiang University-SCIENCE B, 2013)

Anti-human hepatoma Hep-G2 proliferative, apoptotic, and antimutagenic activity of tagitinin C from Tithonia diversifolia leaves - May-Hua Liao; Yuan-Nuan Tsai; Chi-Yu Yang; Chi-Long Juang; Ming-Yi Lee; Li-Hsueh Chang; Hsiao-Chuan Wen (Journal of Natural Medicines, 2013)

Reduction of distortion and improvement of efficiency for gridding of scattered gravity and magnetic data - Chen Zhang; Chang-Li Yao; Yong-Mao Xie; Yuan-Man Zheng; Hu-Liang Guan; Dong-Ming Hong (Applied Geophysics, 2012)

Susceptibilities to Amphotericin B, Fluconazole and Voriconazole of Trichosporon Clinical Isolates - Moan Shane Tsai; Yun Liang Yang; An Huei Wang; Lih Shinn Wang; Daniel C. T. Lu; Ci Hong Liou; Li Yun Hsieh; Chi Jung Wu; Ming Fang Cheng; Zhi Yuan Shi; Hsiu Jung Lo (Mycopathologia, 2012)

Calreticulin Mediates Nerve Growth Factor-Induced Neuronal Differentiation - Yu-Yin Shih; Akira Nakagawara; Hsinyu Lee; Hsueh-Fen Juan; Yung-Ming Jeng; Dong-Tsamn Lin; Yung-Li Yang; Yeou-Guang Tsay; Min-Chuan Huang; Chien-Yuan Pan; Wen-Ming Hsu; Yung-Feng Liao (Journal of Molecular Neuroscience, 2012)

Human influence on the population decline and loss of genetic diversity in a small and isolated population of Sichuan snub-nosed monkeys (Rhinopithecus roxellana) - Zong Fei Chang; Mao Fang Luo; Zhi Jin Liu; Jing Yuan Yang; Zuo Fu Xiang; Ming Li; Linda Vigilant (Genetica, 2012)

Production of cloned transgenic cow expressing omega-3 fatty acids - Xia Wu; Hongsheng Ouyang; Biao Duan; Daxin Pang; Li Zhang; Ting Yuan; Lian Xue; Daibang Ni; Lei Cheng; Shuhua Dong; Zhuying Wei; Lin Li; et al. (Transgenic Research, 2012)

The different expression of immune-related cytokine genes in response to velogenic and lentogenic Newcastle disease viruses infection in chicken peripheral blood - Wen-Quan Liu; Ming-Xing Tian; Yuan-Ping Wang; Yang Zhao; Nian-Li Zou; Fang-Fang Zhao; San-Jie Cao; Xin-Tian Wen; Ping Liu; Yong Huang (Molecular Biology Reports, 2012)

Sucrose treatment alters floral induction and development in vitro in gloxinia - Ming-Zhe Zhang; Li-Ling Wang; Dan Ye; Xi Chen; Zhi-Yi Wu; Xiao-Jia Lin; Wu-Jian Chen; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (In Vitro Cellular & Developmental Biology - Plant, 2012)

Optimisation of preparation conditions and properties of phytosterol liposome-encapsulating nattokinase - Xu-Yan Dong; Fan-Pi Kong; Gang-You Yuan; Fang Wei; Mu-Lan Jiang; Guang-Ming Li; Zhan Wang; Yuan-Di Zhao; Hong Chen (Natural Product Research, 2012)

Knockdown of Microplitis mediator Odorant Receptor Involved in the Sensitive Detection of Two Chemicals - Ke-Ming Li; Li-Yan Ren; Yong-Jun Zhang; Kong-Ming Wu; Yu-Yuan Guo (Journal of Chemical Ecology, 2012)

Advances in study of ginsenoside biosynthesis pathway in Panax ginseng C. A. Meyer - Juan Wang; Wen-Yuan Gao; Jian Zhang; Bei-Mei Zuo; Li-Ming Zhang; Lu-Qi Huang (Acta Physiologiae Plantarum, 2012)

Temperature reconstruction from tree-ring maximum latewood density of Qinghai spruce in middle Hexi Corridor, China - Feng Chen; Yu-jiang Yuan; Wen-shou Wei; Shu-long Yu; Zi-ang Fan; Rui-bo Zhang; Tong-wen Zhang; Qin Li; Hua-ming Shang (Theoretical and Applied Climatology, 2012)

Production of ginsenoside and polysaccharide by two-stage cultivation of Panax quinquefolium L. cells - Juan Wang; Wen-Yuan Gao; Jian Zhang; Bei-Mei Zuo; Li-Ming Zhang; Lu-Qi Huang (In Vitro Cellular & Developmental Biology - Plant, 2012)

Ginsenoside-Rd potentiates apoptosis induced by hydrogen peroxide in basilar artery smooth muscle cells through the mitochondrial pathway - Shi-Yang Li; Xiao-Guang Wang; Ming-Ming Ma; Yun Liu; Yan-Hua Du; Xiao-Fei Lv; Jia-Guo Zhou; Yong-Bo Tang; Yong-Yuan Guan (Apoptosis, 2012)

Effect of dirhamnolipid on the removal of phenol catalyzed by laccase in aqueous solution - Zhi-Feng Liu; Guang-Ming Zeng; Hua Zhong; Xing-Zhong Yuan; Hai-Yan Fu; Mei-Fang Zhou; Xiao-Ling Ma; Hui Li; Jian-Bing Li (World Journal of Microbiology and Biotechnology, 2012)

Type 17 T-helper cells might be a promising therapeutic target for osteoporosis - Feng-Lai Yuan; Xia Li; Wei-Guo Lu; Yi-Qing Zhao; Cheng-Wan Li; Jian-Ping Li; Jun-Ming Sun; Rui-Sheng Xu (Molecular Biology Reports, 2012)

Genes and Pathways Co-associated with the Exposure to Multiple Drugs of Abuse, Including Alcohol, Amphetamine/Methamphetamine, Cocaine, Marijuana, Morphine, and/or Nicotine: a Review of Proteomics Analyses - Ju Wang; Wenji Yuan; Ming D. Li (Molecular Neurobiology, 2011)

IKKβ downregulation is critical for triggering JNKs-dependent cell apoptotic response in the human hepatoma cells under arsenite exposure - Yi Li; Yi Hao; Ming Gao; Wen Dong; Meiru Hu; Shengtao Yuan; Lun Song (Molecular and Cellular Biochemistry, 2011)

Isolation and performance evaluation of halotolerant phosphate solubilizing bacteria from the rhizospheric soils of historic Dagong Brine Well in China - Wen-liang Xiang; Hua-zhong Liang; Sen Liu; Fan Luo; Jie Tang; Ming-yuan Li; Zhen-ming Che (World Journal of Microbiology and Biotechnology, 2011)

Response of denitrification genes nirS, nirK, and nosZ to irrigation water quality in a Chinese agricultural soil - Zhi-Feng Zhou; Yuan-Ming Zheng; Ju-Pei Shen; Li-Mei Zhang; Ji-Zheng He (Environmental Science and Pollution Research, 2011)

Induction of DIMBOA accumulation and systemic defense responses as a mechanism of enhanced resistance of mycorrhizal corn (Zea mays L.) to sheath blight - Yuan Yuan Song; Man Cao; Li Jun Xie; Xiao Ting Liang; Ren Sen Zeng; Yi Juan Su; Jing Hua Huang; Rui Long Wang; Shi Ming Luo (Mycorrhiza, 2011)

Physiology and cell biology of acupuncture observed in calcium signaling activated by acoustic shear wave - Geng Li; Jie-Ming Liang; Pei-Wen Li; Xiaoqiang Yao; Peter Zhong Pei; Wei Li; Qi-Hua He; Xifei Yang; Queenie C. C. Chan; Paul Y. S. Cheung; Qi Yuan Ma; Siu Kam Lam; et al. (Pflügers Archiv - European Journal of Physiology, 2011)

A Novel PrP Partner HS-1 Associated Protein X-1 (HAX-1) Protected the Cultured Cells Against the Challenge of H2O2 - Yuan-Yuan Jing; Xiao-Li Li; Qi Shi; Zhao-Yun Wang; Yan Guo; Ming-Ming Pan; Chan Tian; Shu-Ying Zhu; Cao Chen; Han-Shi Gong; Jun Han; Chen Gao; et al. (Journal of Molecular Neuroscience, 2011)

Impact of simulated microgravity on microvascular endothelial cell apoptosis - Chun-Yan Kang; Lin Zou; Ming Yuan; Yang Wang; Tian-Zhi Li; Ye Zhang; Jun-Feng Wang; Yan Li; Xiao-Wei Deng; Chang-Ting Liu (European Journal of Applied Physiology, 2011)

Dinosaur-bearing strata and K/T boundary in the Luanchuan-Tantou Basin of western Henan Province, China - XiaoJun Jiang; YongQing Liu; ShuAn Ji; XingLiao Zhang; Li Xu; SongHai Jia; JunChang Lü; ChongXi Yuan; Ming Li (Science China Earth Sciences, 2011)

A double-blind, placebo-controlled study of traditional Chinese medicine sarsasapogenin added to risperidone in patients with negative symptoms dominated schizophrenia - Shi-Fu Xiao; Hai-Bo Xue; Xia Li; Chao Chen; Guan-Jun Li; Cheng-Mei Yuan; Ming-Yuan Zhang (Neuroscience Bulletin, 2011)

Regulation of expression of trehalose-6-phosphate synthase during cold shock in Arthrobacter strain A3 - Xi-Ming Chen; Ying Jiang; Yuan-Ting Li; Hai-Hong Zhang; Jie Li; Xing Chen; Qi Zhao; Jing Zhao; Jing Si; Zhi-Wei Lin; Hua Zhang; Paul Dyson; et al. (Extremophiles, 2011)

Comparison of cardioprotective and anti-inflammatory effects of ischemia pre- and postconditioning in rats with myocardial ischemia–reperfusion injury - Jun Xiong; Qiang Wang; Fu-Shan Xue; Yuan-Jing Yuan; Shan Li; Jian-Hua Liu; Xu Liao; Yan-Ming Zhang (Inflammation Research, 2011)

Phylogenetic analysis of the E2 gene of classical swine fever virus from the Guangxi Province of southern China - Ting Rong Luo; Su-huan Liao; Xian-shi Wu; Li Feng; Zhao-Xia Yuan; Hui Li; Jing-Jing Liang; Xian-Ming Meng; Hong-Yun Zhang (Virus Genes, 2011)

The complete mitochondrial genomes of three cestode species of Taenia infecting animals and humans - Guo-Hua Liu; Rui-Qing Lin; Ming-Wei Li; Wei Liu; Yi Liu; Zi-Guo Yuan; Hui-Qun Song; Guang-Hui Zhao; Kou-Xing Zhang; Xing-Quan Zhu (Molecular Biology Reports, 2011)

Cytosolic PrP Induces Apoptosis of Cell by Disrupting Microtubule Assembly - Xiao-Li Li; Gui-Rong Wang; Yuan-Yuan Jing; Ming-Ming Pan; Chen-Fang Dong; Rui-Min Zhou; Zhao-Yun Wang; Qi Shi; Chen Gao; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Mapping quantitative trait loci for seed size traits in soybean (Glycine max L. Merr.) - Yu Xu; He-Nan Li; Guang-Jun Li; Xia Wang; Li-Guo Cheng; Yuan-Ming Zhang (Theoretical and Applied Genetics, 2011)

Genetic analysis of starch paste viscosity parameters in glutinous rice (Oryza sativa L.) - Chang-Jie Yan; Zhi-Xi Tian; Yu-Wei Fang; Ya-Chun Yang; Jian Li; Sheng-Yuan Zeng; Shi-Liang Gu; Chen-Wu Xu; Shu-Zhu Tang; Ming-Hong Gu (Theoretical and Applied Genetics, 2011)

Immunomodulative effects of mesenchymal stem cells derived from human embryonic stem cells in vivo and in vitro - Zhou Tan; Zhong-yuan Su; Rong-rong Wu; Bin Gu; Yu-kan Liu; Xiao-li Zhao; Ming Zhang (Journal of Zhejiang University-SCIENCE B, 2011)

Dynamic Changes of Heme Oxygenase-1 in the Hippocampus of Rats After Acute Carbon Monoxide Poisoning - Li Guan; Yan-Lin Zhang; Tao Wen; Xi-Fu Wang; Ming-Xia Zhu; Jin-Yuan Zhao (Archives of Environmental Contamination and Toxicology, 2011)

A web-based platform for rice microarray annotation and data analysis - DiJun Chen; Fan Zhang; ChunHui Yuan; Jing Lu; Xia Li; Ming Chen (Science China Life Sciences, 2010)

Tobacco microtubule-associated protein, MAP65-1c, bundles and stabilizes microtubules - Qiutao Meng; Jizhou Du; Jiejie Li; Xiaomei Lü; Xian Zeng; Ming Yuan; Tonglin Mao (Plant Molecular Biology, 2010)

Differential miRNA expression and their target genes between NGX6-positive and negative colon cancer cells - Xiao-Yan Wang; Ming-Hua Wu; Fen Liu; Yu Li; Nan Li; Gui-Yuan Li; Shou-Rong Shen (Molecular and Cellular Biochemistry, 2010)

Secondary metabolites from the red mould rice of Monascus purpureus BCRC 38113 - Ming-Jen Cheng; Ming-Der Wu; Ih-Sheng Chen; Chung-Yi Chen; Wen-Li Lo; Gwo-Fang Yuan (Natural Product Research, 2010)

Regeneration pattern of primary forest species across forest-field gradients in the subtropical Mountains of Southwestern China - Xiao-Shuang Li; Wen-Yao Liu; Jun-Wen Chen; Cindy Q. Tang; Chun-Ming Yuan (Journal of Plant Research, 2010)

The catalytic efficiency of trehalose-6-phosphate synthase is effected by the N-loop at low temperatures - Ying Jiang; Xi-Ming Chen; Ya-Jie Liu; Yuan-Ting Li; Hai-Hong Zhang; Paul Dyson; Hong-Mei Sheng; Li-Zhe An (Archives of Microbiology, 2010)

All-trans retinoic acid promotes smooth muscle cell differentiation of rabbit bone marrow-derived mesenchymal stem cells - Zhong-yuan Su; Ying Li; Xiao-li Zhao; Ming Zhang (Journal of Zhejiang University-SCIENCE B, 2010)

Effects of mercury on the activity and community composition of soil ammonia oxidizers - Yu-Rong Liu; Yuan-Ming Zheng; Ju-Pei Shen; Li-Mei Zhang; Ji-Zheng He (Environmental Science and Pollution Research, 2010)

Involvement of anion exchanger-2 in apoptosis of endothelial cells induced by high glucose through an mPTP-ROS-Caspase-3 dependent pathway - Qi-Ren Huang; Qing Li; Yuan-Hong Chen; Li Li; Li-Li Liu; Shui-Hong Lei; He-Ping Chen; Wei-Jie Peng; Ming He (Apoptosis, 2010)

Cr(III) oxidation coupled with Mn(II) bacterial oxidation in the environment - Ji-Zheng He; You-Ting Meng; Yuan-Ming Zheng; Li-Mei Zhang (Journal of Soils and Sediments, 2010)

Validation of Candidate Reference Genes for the Accurate Normalization of Real-Time Quantitative RT-PCR Data in Rice During Seed Development - Qian-Feng Li; Samuel S. M. Sun; Ding-Yang Yuan; Heng-Xiu Yu; Ming-Hong Gu; Qiao-Quan Liu (Plant Molecular Biology Reporter, 2010)

Overexpression of Soybean (Glycine max (L.) Meer.) L34 Gene Leads to Reduced Survival to Cold Stress in Transgenic Arabidopsis - Li-Bao Cheng; Shu-Yan Li; Guang-Xiao Yang; Xin-Ming Jing; Guang-Yuan He; Namela G. Mones (Plant Molecular Biology Reporter, 2010)

Heterologous expression of taro cystatin protects transgenic tomato against Meloidogyne incognita infection by means of interfering sex determination and suppressing gall formation - Yuan-Li Chan; Ai-Hwa Yang; Jen-Tzu Chen; Kai-Wun Yeh; Ming-Tsair Chan (Plant Cell Reports, 2010)

TCF7L2 genetic variants and progression to diabetes in the Chinese population: pleiotropic effects on insulin secretion and insulin resistance - Yi-Cheng Chang; Yen-Feng Chiu; Larry Low-Tone Ho; Chih-Tai Ting; Kuang-Chung Shih; J. David Curb; Yii-Der Ida Chen; Hung-Yuan Li; Lee-Ming Chuang (Journal of Molecular Medicine, 2010)

Increased serum interleukin 17 in patients with systemic lupus erythematosus - Xue-Fei Zhao; Hai-Feng Pan; Hui Yuan; Wen-Hui Zhang; Xiang-Pei Li; Gui-Hong Wang; Guo-Cui Wu; Hong Su; Fa-Ming Pan; Wen-Xian Li; Lian-Hong Li; Guo-Ping Chen; et al. (Molecular Biology Reports, 2010)

Numerical modeling of coupled fluid flow and thermal and reactive biogeochemical transport in porous and fractured media - Gour-Tsyh Yeh; Yilin Fang; Fan Zhang; Jiangtao Sun; Yuan Li; Ming-Hsu Li; Malcolm D. Siegel (Computational Geosciences, 2010)

Effects of exogenous annexin-1 on lipopolysaccharide-induced proliferation and reactive oxygen species production partially through modulation of CRAC channels but independent of NF-κB pathway - Lei-Ming Xu; Sheng-Wei Jin; Xiao-Yan Zhou; Ping Wu; Yong-Sheng Li; Li Zhang; Yuan-Yuan Lin; Ying Chen; Du-Yun Ye (Inflammation Research, 2009)

Adaptation of the externally feeding bug Elasmucha necopinata (Hemiptera: Acanthosomatidae) to its fig host - Guang-Chang Ma; Hao-Yuan Hu; Li-Ming Niu; Yue-Guan Fu; Zheng-Qiang Peng; Wen-Jun Bu; Da-Wei Huang (Symbiosis, 2009)

Profiling Gene Expression During Gland Morphogenesis of a Glanded and a Glandless Upland Cotton - Ying-Fan Cai; Min Chen; Quan Sun; Yong-Fang Xie; Sheng-Wei Li; Ming-Feng Jiang; Jian-Chuan Mo; You-Lu Yuan; Yu-Zhen Shi; Huai-Zhong Jiang; Zheng Pan; Yun-Ling Gao; et al. (Journal of Plant Biology, 2009)

Two new N -oxide Lycopodium alkaloids from Huperzia serrata - Heng-Bin Wang; Chang-Heng Tan; Jun-Jie Tan; Shi-Jin Qu; Yi-Lei Chen; Yi-Ming Li; Shan-Hao Jiang; Da-Yuan Zhu (Natural Product Research, 2009)

Molecular Cloning and Expression of cDNA Encoding the Cysteine Proteinase Inhibitor from Upland Cotton - Ming-feng Jiang; Sheng-wei Li; Min Chen; Ying-fan Cai; Yong-fang Xie; Biao Li; Quan Sun; Huai-zhong Jiang; Zheng Pan; Yun-ling Gao; You-Lu Yuan; Yu-zheng Shi (Journal of Plant Biology, 2009)

Relationships among Avena species as revealed by consensus chloroplast simple sequence repeat (ccSSR) markers - Wei-Tao Li; Yuan-Ying Peng; Yu-Ming Wei; Bernard R. Baum; You-Liang Zheng (Genetic Resources and Crop Evolution, 2009)

Association of polymorphisms at restriction enzyme recognition sites of apolipoprotein B and E gene with dyslipidemia in children undergoing primary nephrotic syndrome - Peng Hu; Yuan Han Qin; Cheng Xue Jing; Feng Ying Lei; Ping Chen; Ming Fang Li (Molecular Biology Reports, 2009)

FAS −1,377 G/A polymorphism is associated with cancer susceptibility: evidence from 10,564 cases and 12,075 controls - Li-Xin Qiu; Jian Shi; Hui Yuan; Xin Jiang; Kai Xue; Hai-Feng Pan; Jin Li; Ming-Hua Zheng (Human Genetics, 2009)

Expressions of cardiac sympathetic norepinephrine transporter and β1-adrenergic receptor decreased in aged rats - He Li; Xiao-qing Ma; Fan Ye; Jing Zhang; Xin Zhou; Zhi-hong Wang; Yu-ming Li; Guo-yuan Zhang (Journal of Zhejiang University-SCIENCE B, 2009)

Arabidopsis microtubule-associated protein AtMAP65-2 acts as a microtubule stabilizer - Hua Li; Xian Zeng; Zi-Qiang Liu; Qiu-Tao Meng; Ming Yuan; Tong-Lin Mao (Plant Molecular Biology, 2009)

Expression and purification of bioactive high-purity human midkine in Escherichia coli - Zhong-hui Zhang; Li-juan Du; Di Xiang; Shun-ying Zhu; Ming-yuan Wu; Hui-li Lu; Yan Yu; Wei Han (Journal of Zhejiang University-SCIENCE B, 2009)

Nitrous Oxide Emissions from Wetland Rice–Duck Cultivation Systems in Southern China - Chengfang Li; Cougui Cao; Jingping Wang; Ming Zhan; Weiling Yuan; Shahrear Ahmad (Archives of Environmental Contamination and Toxicology, 2009)

Abundance and community composition of methanotrophs in a Chinese paddy soil under long-term fertilization practices - Yong Zheng; Li-Mei Zhang; Yuan-Ming Zheng; Hongjie Di; Ji-Zheng He (Journal of Soils and Sediments, 2008)

Association of MYF5 and MYOD1 Gene Polymorphisms and Meat Quality Traits in Large White × Meishan F2 Pig Populations - Min Liu; Jian Peng; De-Quan Xu; Rong Zheng; Feng-E Li; Jia-Lian Li; Bo Zuo; Ming-Gang Lei; Yuan-Zhu Xiong; Chang-Yan Deng; Si-Wen Jiang (Biochemical Genetics, 2008)

Heregulin-β promotes matrix metalloproteinase-7 expression via HER2-mediated AP-1 activation in MCF-7 cells - Guogang Yuan; Lu Qian; Lun Song; Ming Shi; Dan Li; Ming Yu; Meiru Hu; Beifen Shen; Ning Guo (Molecular and Cellular Biochemistry, 2008)

Multiple quantitative trait loci Haseman–Elston regression using all markers on the entire genome - Yuan-Ming Zhang; Hai-Yan Lü; Li-Li Yao (Theoretical and Applied Genetics, 2008)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)

Nitrogen losses from integrated rice–duck and rice–fish ecosystems in southern China - Li Cheng-fang; Cao Cou-gui; Wang Jin-ping; Zhan Ming; Yuan Wei-ling; Shahrear Ahmad (Plant and Soil, 2008)

Development of thirteen microsatellite loci for Impatiens lateristachys (Balsaminaceae) - Lin-Feng Li; Guo-Qing Chen; Yong-Ming Yuan; Xue-Jun Ge (Conservation Genetics, 2008)

Effect of SPLUNC1 protein on the Pseudomonas aeruginosa and Epstein-Barr virus - Hou-De Zhou; Xiao-Ling Li; Gui-Yuan Li; Ming Zhou; Hua-Ying Liu; Yi-Xing Yang; Tan Deng; Jian Ma; Shou-Rong Sheng (Molecular and Cellular Biochemistry, 2008)

Quantitative trait loci for carcass traits on pig chromosomes 4, 6, 7, 8 and 13 - Jing Hu Zhang; Yuan Zhu Xiong; Bo Zuo; Ming Gang Lei; Si Wen Jiang; Feng E Li; Rong Zheng; Jia Lian Li; Quan De Xu (Journal of Applied Genetics, 2007)

Quantitative analyses of the abundance and composition of ammonia‐oxidizing bacteria and ammonia‐oxidizing archaea of a Chinese upland red soil under long‐term fertilization practices - Ji‐zheng He; Ju‐pei Shen; Li‐mei Zhang; Yong‐guan Zhu; Yuan‐ming Zheng; Ming‐gang Xu; Hongjie Di (Environmental Microbiology, 2007)

A mixture model approach to the mapping of QTL controlling endosperm traits with bulked samples - Xuefeng Wang; Zhiqiu Hu; Wei Wang; Yuling Li; Yuan-Ming Zhang; Chenwu Xu (Genetica, 2007)

Retention capacities of several bryophytes for Hg(II) with special reference to the elevation and morphology of moss growth - Shou-Qin Sun; Ding-Yong Wang; Ming He; Xian-Yuan Li; Cheng Zhang (Environmental Monitoring and Assessment, 2007)

BRD7 suppresses the growth of Nasopharyngeal Carcinoma cells (HNE1) through negatively regulating β-catenin and ERK pathways - Cong Peng; Hua Ying Liu; Ming Zhou; Li Ming Zhang; Xiao Ling Li; Shou Rong Shen; Gui Yuan Li (Molecular and Cellular Biochemistry, 2007)

Quantitative analyses of the abundance and composition of ammonia‐oxidizing bacteria and ammonia‐oxidizing archaea of a Chinese upland red soil under long‐term fertilization practices - Ji‐zheng He; Ju‐pei Shen; Li‐mei Zhang; Yong‐guan Zhu; Yuan‐ming Zheng; Ming‐gang Xu; Hongjie Di (Environmental Microbiology, 2007)
Summary The abundance and composition of soil ammonia‐oxidizing bacteria (AOB) and ammonia‐oxidizing archaea (AOA) were investigated by using quantitative real‐time polymerase chain reaction, cloning and sequencing approaches based on amoA genes. The soil, classified as agri‐udic ferrosols with pH (H 2 O) ranging from 3.7 to 6.0, was sampled in summer and winter from long‐term field experimental plots which had received 16 years continuous fertilization treatments, including fallow (CK0), control without fertilizers (CK) and those with combinations of fertilizer nitrogen (N), phosphorus (P) and potassium (K): N, NP, NK, PK, NPK and NPK plus organic manure (OM). Population sizes of AOB and AOA changed greatly in response to the different fertilization treatments. The NPK + OM treatment had the highest copy numbers of AOB and AOA amoA genes among the treatments that received mineral fertilizers, whereas the lowest copy numbers were recorded in the N treatment. Ammonia‐oxidizing archaea were more abundant than AOB in all the corresponding treatments, with AOA to AOB ratios ranging from 1.02 to 12.36. Significant positive correlations were observed among the population sizes of AOB and AOA, soil pH and potential nitrification rates, indicating that both AOB and AOA played an important role in ammonia oxidation in the soil. Phylogenetic analyses of the amoA gene fragments showed that all AOB sequences from different treatments were affiliated with Nitrosospira or Nitrosospira‐ like species and grouped into cluster 3, and little difference in AOB community composition was recorded among different treatments. All AOA sequences fell within cluster S (soil origin) and cluster M (marine and sediment origin). Cluster M dominated exclusively in the N, NP, NK and PK treatments, indicating a pronounced difference in the community composition of AOA in response to the long‐term fertilization treatments. These findings could be fundamental to improve our understanding of the importance of both AOB and AOA in the cycling of nitrogen and other nutrients in terrestrial ecosystems.

Acetylene-Substituted Two-Photon Absorbing Molecules With Rigid Elongated Pi-Conjugation: Synthesis, Spectroscopic Properties and Two-Photon Fluorescence Cell Imaging Applications - Bo Liu; Hai-Li Zhang; Jun Liu; Zhen-Li Huang; Yuan-Di Zhao; Qing-Ming Luo (Journal of Fluorescence, 2007)

Gene Cloning, Expression, and Substrate Specificity of an Imidase from the Strain Pseudomonas putida YZ-26 - Ya-wei Shi; Li-fang Cui; Jing-ming Yuan (Current Microbiology, 2007)

The central role of osteoblasts in the metastasis of prostate cancer - Michel B. Choueiri; Shi-Ming Tu; Li-Yuan Yu-Lee; Sue-Hwa Lin (Cancer and Metastasis Reviews, 2007)

BRD2 is one of BRD7-interacting proteins and its over-expression could initiate apoptosis - Ming Zhou; Xiao-Jie Xu; Hou-De Zhou; Hua-Ying Liu; Jia-Jin He; Xiao-Ling Li; Cong Peng; Wei Xiong; Song-Qing Fan; Jian-Hong Lu; Jue Ouyang; Shou-Rong Shen; et al. (Molecular and Cellular Biochemistry, 2006)

Silicon’s organic pool and biological cycle in moso bamboo community of Wuyishan Biosphere Reserve - Zhen-ji Li; Peng Lin; Jian-yuan He; Zhi-wei Yang; Yi-ming Lin (Journal of Zhejiang University-SCIENCE B, 2006)

Nitrogen response efficiency increased monotonically with decreasing soil resource availability: a case study from a semiarid grassland in northern China - Zhi-You Yuan; Ling-Hao Li; Xing-Guo Han; Shi-Ping Chen; Zheng-Wen Wang; Quan-Sheng Chen; Wen-Ming Bai (Oecologia, 2006)

Purification, enzymatic properties of a recombinant d-hydantoinase and its dissociation by zinc ion - Ya-Wei Shi; Li-Xi Niu; Xia Feng; Jing-Ming Yuan (World Journal of Microbiology and Biotechnology, 2006)

Detection of Two Fungal Biocontrol Agents against Root-knot Nematodes by RAPD Markers - Ming Liang Zhu; Ming He Mo; Zhen Yuan Xia; Yun Hua Li; Shu Jun Yang; Tian Fei Li; Ke Qin Zhang (Mycopathologia, 2006)

Seasonal Variation of Virioplankton in a Eutrophic Shallow Lake - Yan-Ming Liu; Qi-Ya Zhang; Xiu-Ping Yuan; Zheng-Qiu Li; Jian-Fang Gui (Hydrobiologia, 2006)

Characterization of a bioflocculant from a newly isolated Vagococcus sp. W31 - Jie Gao; Hua-ying Bao; Ming-xiu Xin; Yuan-xia Liu; Qian Li; Yan-fen Zhang (Journal of Zhejiang University-SCIENCE B, 2006)

Tissue distribution of the secretory protein, SPLUNC1, in the human fetus - Hou-De Zhou; Song-Qin Fan; Jin Zhao; Dong-Hai Huang; Ming Zhou; Hua-Ying Liu; Zhao-Yang Zeng; Yi-Xing Yang; He Huang; Xiao-Ling Li; Shou-Rong Shen; Gui-Yuan Li (Histochemistry and Cell Biology, 2006)

Identification of a Lactose-Responsive Element Upstream of the Promoter of Bacillus megaterium β-Galactosidase-Encoding Gene mbgA - Jen-Ming Li; Chih-Yung Chiou; Tian-Ren Lee; Yuan-Shou Chen; Gwo-Chyuan Shaw (Current Microbiology, 2005)

Transgenic tomato plants expressing an Arabidopsis thionin (Thi2.1) driven by fruit-inactive promoter battle against phytopathogenic attack - Yuan-Li Chan; Venkatesh Prasad; Sanjaya; Kuei Hung Chen; Po Chang Liu; Ming-Tsair Chan; Chiu-Ping Cheng (Planta, 2005)

Soil characteristics and nitrogen resorption in Stipa krylovii native to northern China - Zhi-You Yuan; Ling-Hao Li; Xing-Guo Han; Jian-Hui Huang; Gao-Ming Jiang; Shi-Qiang Wan (Plant and Soil, 2005)

Gene stacking in Phalaenopsis orchid enhances dual tolerance to pathogen attack - Yuan-Li Chan; Kuang-Hung Lin; Sanjaya; Li-Jen Liao; Wen-Huei Chen; Ming-Tsair Chan (Transgenic Research, 2005)

FPF1 transgene leads to altered flowering time and root development in rice - Ming-Li Xu; Jia-Fu Jiang; Lei Ge; Yun-Yuan Xu; Hui Chen; Yuan Zhao; Yu-Rong Bi; Jiang-Qi Wen; Kang Chong (Plant Cell Reports, 2005)

Soluble Expression and Affinity Purification of Functional Domain of Human Acetylcholine Receptor ?-subunit by the Modulation of Maltose Binding Protein - Zhuo-Yu Li; Yan-Jun Li; Chen-Yun Guo; Ye-Wei Shi; Ming-Qun Xu; Wolfgang E. Trommer; Jing-Ming Yuan (Biotechnology Letters, 2004)

Single-column purification of recombinant human neurotrophin-3 (hNT3) by using the intein mediated self-cleaving system - Zhuo-Yu Li; Jun-Hu Fan; Jing-Ming Yuan (Biotechnology Letters, 2002)

Beneficial effect of HCL-31D in murine models of endotoxaemia - Tz-Chong Chou; Chi-Yuan Li; Tzong-Ming Wu; Shang-Tao Tang; An-Rong Lee; Yu-An Ding (Naunyn-Schmiedeberg's Archives of Pharmacology, 2001)

THE CULTURE OF FIBROBLASTS FROM DIAPHRAGM OF GIANT PANDA - Zhi-Ming Han; Da-Yuan Chen; Jin-Song Li; Qing-Yuan Sun; Peng-Yang Wang; Yang Huang; Jun Du (In Vitro Cellular & Developmental Biology - Animal, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)